Metabolic redirection and capacity expansion in heterotroph-reinforced microalgae-methanotroph systems under high ammonia stress - Yong-Ze Lu; Jia-Sen Yang; Xin-Ya Tan; Yi-Ru Wang; Hong-Yin Sha; Hao-Yu Wang; Shao-Jie Zong; Guang-Can Zhu (Bioresource Technology, 2027)

Disruption of retinol saturase enhances Polyunsaturated Fatty Acid (PUFA) biosynthesis in grass carp (Ctenopharyngodon idella) via upregulation of fads2 - Ru Zhang; Ran Yang; Jiang Zeng; Xiao Xiao; Houpeng Wang; Yongming Li; Xiaosi Wang; Jian Gao; Mudan He; Yonghua Sun (Aquaculture, 2027)

Lightweight real-time detection of sweet potato virus disease by a hybrid CNN–Transformer network - Ru Han; Lei Shu; Grzegorz Cielniak; Yan Zhu; Xing Yang; Fan Yang; Kai Huang (Computers and Electronics in Agriculture, 2026)

Porosity inversion and determination in gob unconsolidated materials based on acoustic signal response - Shuai-Jing Ren; Le-Xiang-Qian Zhang; Jun Deng; Jin-Rui Wang; Cai-Ping Wang; Yang Xiao; Fu-Ru Kang; Hai-Jian Li; Long-Hui Dou (Fuel, 2026)

Structure and characteristics of quercetin-loaded starch nanoparticles and their surface charges for protein corona formation with gastrointestinal digestive enzymes - Yu-Ru Wu; Zhi-Yuan Yang; Shan-Dan Zhao; Dan-Yang Shen; Ya-Jun Lin; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2026)

Trem2 regulates macrophage phenotype via the JAK2/STAT3 signaling pathway to ameliorate ventricular remodeling after acute myocardial infarction - Zefeng He; Jing Feng; Ru Yan; Peng Wu; Baozhen Zhu; Huifang Li; Taoyu Yang; Yaxin Lu; Baotong He; Xueping Ma; Shaobin Jia; Guangzhi Cong (Molecular Biology Reports, 2026)

PbrFEN-1 positively regulates pear pollen tube growth and is involved in the self-incompatibility response - Zhi-Heng Sui; Yi-Peng Ye; Ju-Yang Yao; Ya-Ru Wang; Ying Xu; Ce-Xian Cui; Shao-Ling Zhang; Chao Gu (Plant Reproduction, 2026)

A novel inversion method for assessing pipe corrosion condition based on upstream-downstream water quality variation in drinking water distribution systems - Yun-Qiao Zeng; Tian-Yang Zhang; Zhen-Ning Luo; Ling Hu; Bing Geng; Renjie Pan; Zhu Peng; Dai-Xu Zhang; Yi-Ru Chen; Huan He; Mohamed Gamal El-Din; Bin Xu (Water Research, 2026)

Insulin-like peptide 3 facilitates sheep oocytes in vitro maturation and subsequent early embryo development - Qi Yang; Rui-Feng Zhang; Zhao-Yu Jiang; Dui Sun; Rui-Hao Tang; Xiao-Yi Zhang; Yi-Tong Li; Wen-Ying Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Theriogenology, 2026)

Characterization of phosphorylated whey protein and its hydrolytic insoluble peptide aggregates - Hui Yang; Ru Lin; Yinuo Xiao; Xuan Shang; Shanshan Bai (International Dairy Journal, 2026)

Polymer-specific oxidative biotransformation of polyethylene and polypropylene microplastics by the stored-grain pest Tribolium castaneum - Sakhawat Shah; Jin-Ru Zhao; Ze-Yu Liu; Yi-Jia Chen; Jie Tang; Karam Khamis Elgizawy; Qiu-Ying Huang; Elvis Genbo Xu; Feng-Lian Yang (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Copper and zinc isotopes reveal redox-driven nutrient cycles in the Mesoproterozoic ocean - Kexin Song; Dandan Li; Chengshuai Yuan; Yang Liu; Yuan-Ru Qu; Sheng-Ao Liu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Asymmetric introgression and reticulate evolution result from palaeoclimate-driven range dynamics of the Smilax hispida group in North and Central America - Xin-Yi Fan; Han-Yang Lin; Ya-Lu Ru; Yun-Peng Zhao (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Mechanisms of typical antibiotic degradation and suppression of resistance gene propagation in a biological manganese oxidation reactor - Huaqing Liu; Xin-Ru Jia; Chong-Yang Ren; Xiaoqiang Cao; He-Ping Zhao; Jian Zhang (Journal of Water Process Engineering, 2026)

Benzene-modified carbon nitride with enhanced π–π adsorption for efficient lignin C–C bond photocleavage - Yunyi Wang; Ru Yang; Xiang Li; Haiping Wang; Ting Wu; Guigan Fang (Journal of Environmental Chemical Engineering, 2026)

Lattice carbon-induced electronic regulation of AlCo2O4 spinels for boosting toluene oxidation - Dadao Wang; Xueqin Yang; Mimi Wu; Menglan Xiao; Yanhu Zhang; Mianmian Zhang; Xiuhong Zhu; Guangxin Ru; Yucong Guo; Bo Shi; Xiaolin Yu; Maofa Ge (Journal of Environmental Chemical Engineering, 2026)

O-B modified starch emulsions as novel additives enhancing 3D printing adaptability and quality of Dosidicus gigas surimi gels - Luhan You; Kaina Duan; Yi Hu; Jie-Ting Geng; Wenge Yang; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2026)

Structural and functional responses of myofibrillar proteins from yellow croaker to plasma-activated buffer: evidence from a simulated PAW system - Fangqi Yuan; Quanyou Guo; Zuofeng Shi; Huawei Wu; Wenge Yang; Tao Huang; Ru Jia; Huamao Wei (Food Research International, 2026)

Effects of clay jar and stainless steel fermentation on microbial succession and flavor formation in spontaneously fermented Cabernet Sauvignon wine - Fan Yang; Lin Pan; Ru Zhai; Fuqi Li; Wen Li; Kaixiong Li (Food Bioscience, 2026)

Effects of long-term exposure to 2,6-di-tert-butylhydroxytoluene and its transformation product 2,6-di-tert-butylbenzoquinone on development and reproduction in zebrafish - Ze Li; Junya Song; Liqiang Yang; Yufeng Gong; Shaoguo Ru; Weiwei Wang (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

Oral self-assembled nanomedicine orchestrates hierarchical regulation of the lipid–ROS–inflammation cascade for comprehensive therapy of non-alcoholic fatty liver disease - Jia-Jian Zhang; Yin-Sheng Tan; Chen-Lei Zhang; Yan Gui; Fan-Zhi Yan; Jie Hou; Xiang-Xuan Liu; Hua Kong; Meng-Ru Guo; Yang-Feng Cui; Xian-He Lin; Tao-Tao Fan; et al. (Chemical Engineering Journal, 2026)

Thermotolerant Chlorella vulgaris sustains flue gas carbon capture and nitrogen oxide and sulfur oxide mitigation through thylakoid remodelling, proteostasis, and antioxidant defense - Ru-Yin Yang; Hsiang-Hui Chou; Hsiang-Yen Su; Te-Jin Chow; Jo-Shu Chang; Tse-Min Lee (Bioresource Technology, 2026)

Integration of niche evolution and pre-adaptation shaped the diversity of Cypripedium (Orchidaceae) in subtropical and temperate regions since mid-Miocene times - Liu-Qiong Wei; Peng Zhou; Pei-Yang Zhang; Si-Xian Li; Bo-Ni Lai; Ru-Yang Ye; Ji-Hong Li; Yan Luo; Xiao-Hong Zeng; Yi-Zhen Liu; Xiao-Guo Xiang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Kosakonia oryziphila KC516 mediated growth promotion of Cosmos bipinnatus in phosphogypsum by modulating rhizosphere geochemistry and root transcriptome - Jing Zhang; Hao-Tian Dong; Yuan-Chun Yang; Rui Liu; Shuai Wang; Ao-Li Zhang; Yuan Su; Ming-Hua Dong; Yan-Ru Cao; Hua-Li Zhang (Environmental Geochemistry and Health, 2026)

Dynamic changes in structural characteristics and biological activities of polysaccharides from Lentinus edodes during postharvest storage - Ru Li; Zhihan Zheng; Yilong Zou; Jingxiao Li; Yi Wu; Hailong Yang; Hang Qu; Bo Chen (Postharvest Biology and Technology, 2026)

Sublethal cinnamon essential oil induces oxidative stress-driven metabolic reprogramming and attenuates spoilage potential in Psychrobacter faecalis - Yueping Yang; Ru Song; Pengcheng Li; Ye Tao; Xiaoyu Zou; Yan Xu; Rongbian Wei (Food Research International, 2026)

A macin family antimicrobial peptide from Atrina pectinata exhibiting dual functions in direct bactericidal activity and hemocyte immune modulation - Yan-ru Chen; Kun-yu Zhao; Shun-xin Hu; Ding-long Yang; Xue-peng Li; Li-zhu Chen; Jian-min Zhao (Fish & Shellfish Immunology, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Quercetin restores oocyte maturation and embryo development in DEHP-exposed mice via mitochondrial protection and apoptosis inhibition - Dui Sun; Qi Yang; Zhi-Hui Gong; Meng-Lei Feng; Zhi-Wen Jia; Bin-Shuo Yang; Zhao-Yu Jiang; Chun-Ru Song; Fang-Rui Xue; Xiao-Jie Zhang; Hao-Yang Zhang; Chun-Lan Zhang; et al. (Chemico-Biological Interactions, 2026)

Multiomics, pharmacogenomic, and structural characterization of NCCRP1 as a candidate therapeutic target in ovarian cancer - Dahlak Daniel Solomon; Yung-Kuo Lee; Sachin Kumar; Kai-Fu Chang; Chung-Hsien Lin; Ching-Chung Ko; Ngoc Uyen Nhi Nguyen; Do Thi Minh Xuan; Neethu Palekkode; Chih-Yang Wang; Hui-Ru Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2026)

Kit Ligand enhances in vitro oocyte maturation and early embryonic development in sheep - Qi Yang; Dui Sun; Zhao-Yu Jiang; Rui-Hao Tang; Rui-Feng Zhang; Xiao-Yi Zhang; Wen-Ying Li; Yi-Tong Li; Ao Liu; Chun-Lan Zhang; Zhi-Wen Jia; Meng-Lei Feng; et al. (Animal Reproduction Science, 2026)

Endothelial Cell TRIM47 Triggers Blood–Brain Barrier Disruption via CYLD Ubiquitination Degradation in an Intracerebral Hemorrhage Model - Qian Li; Xue Ru; Chenyang Li; Yaying He; Baohui Yang; Xuemei Li; Xuan Zhai (Neuroscience Bulletin, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

Comparative study on combustion characteristics of dual-fire sources in naturally ventilated tunnels: Effects of fuel type and spacing - Wenhao Xue; Yuan Wang; Yang Lou; Xinlei Liu; Ru Zhou; Min Hao; Juncheng Jiang (Tunnelling and Underground Space Technology, 2026)

Mechanical degradation mechanisms of colorful clay subjected to dry-wet cycling - Yin-Lei Sun; Qing-Ru Du; Xin-Yao Yang; Wei Luo; Xiang Qian; Xian-Wei Zhang (Transportation Geotechnics, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

Bioactivity assay coupled with molecular networking for the discovery of antioxidants from purslane - Yan-Xi Li; Mei-Ru Wang; Long-Gao Xiao; Huan Yan; Shan-Shan Ling; Hui Liu; Tao-Bin He; Wei Ni; Xin Fang; Hai-Yang Liu (Food Research International, 2026)

Early microbial succession and matrix destabilization guide long-term preservation of refrigerated kelp - Neng-Pai Shi; Si-Chuang Tu; Bing-Bing Wu; Ru-Meng Xiao; Hai-Bin Pan; Sheng-Nan Lin; Roger Ruan; Xue-Mei Hou; Xiang-Yang Lin (Food Chemistry, 2026)

Food-Derived Phycocyanin from Spirulina Promotes Longevity and Lipid-Metabolic Transcriptional Remodeling in Caenorhabditis elegans - Siang-Ru Huang; Yoshikazu Nishikawa; Jiue-in Yang; Hiroshi Tanaka; Chih-Jen Lai; Chien-Sen Liao (Food Bioscience, 2026)

Stable leaf pH of grassland community under nitrogen inputs ensured by contrasting intra- and inter-specific variations - Xiao-Hua Yang; Cong Ding; Xiao-Sa Liang; Yuan-Xiu Wu; Xiao-Ru Zhang; Xiao-Jing Zhang; Liang-Chao Jiang; Xing-Guo Han; Xiao-Tao Lü (Plant and Soil, 2026)

The SP1/NEDD4L Axis Suppresses the Breast Cancer Progression by Downregulating SNAI2 Expression - Baile Zuo; Xiaoyan Li; Mengke Wang; Zhuoya Yin; Yifan Guo; Liping Zhao; Ru Yang; Binghua Tong; Zhenni Guo; Meiqing Sun; Jin Zhao; Huina Zhang; et al. (Biochemical Genetics, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Triazine herbicide prometryn impaired trophic link between phytoplankton and zooplankton Brachionus plicatilis by diminishing polyunsaturated fatty acids contents - Wei Liang; Yilei Li; Ziang Zhao; Dongchu Zhao; Yue Wang; Liqiang Yang; Shaoguo Ru; Xiaona Zhang (Marine Pollution Bulletin, 2026)

Curcumol induces autophagy-dependent hepatic stellate cell death through methionine metabolism disruption - Yi-jie Gao; Ya Zhou; Yi-ning Li; Kai-yao Yang; Si-wei Xia; Meng-ru Hu; Yang Li; Li Chen; Fei-xia Wang; Shuai Lu; Na-qi Lian; Shi-zhong Zheng; et al. (Toxicology and Applied Pharmacology, 2026)

Scenario-based synergistic assessment of crop straw allocation for GHG mitigation and sustainable resource use in China - Yan Ru Fang; Zhongshi Tang; Xuefang Wu; Pingjian Yang (Sustainable Production and Consumption, 2026)

Deep carbon cycling in continental subduction zones - Sheng-Ao Liu; Wan-Yu Sun; Yuan-Ru Qu; Hong-Li Yang (Lithos, 2026)

pH-programmed precipitation with post-upgrading for integrated recovery of Be, Al, and ammonium sulfate from Be-bearing smelting residue - Shan Zhong; Bingqian Zhang; Lu Yang; Zengxian Wei; Qian Zhang; Xuan Ru; Zongchen Li; Lishan Zhang (Journal of Environmental Management, 2026)

Intensified drought and vegetation-specific responses in the Tianshan Mountains, Central Asia - Huaijun Wang; Yaning Chen; Liang Ren; Zhi Li; Ru Feng; Zhiguo Ren; Yuanqiao Li; Yaxue Yang; Yingping Pan (CATENA, 2026)

Motion Response Prediction and Hull-Form Optimization for a Wigley Ship in Regular Waves - Yukun Shi; Basharat Ullah; Zhijing Wu; Ru Wang; Sheng Yang; Shurui Wen (Journal of Marine Science and Engineering, 2026)
This study consists of two main components. The first part establishes a seakeeping assessment method, while the second part focuses on hull-form optimization with seakeeping performance as the objective. For the seakeeping analysis, the Lewis conformal mapping method is used to calculate the sectional hydrodynamic coefficients. Strip theory is then applied to obtain the global hydrodynamic coefficients of the hull. The coupled heave and pitch motion responses are calculated and compared with nonlinear time-domain simulation results and experimental data, showing good agreement. A multivariate linear regression model is established to approximate the relationship between the principal hull-form parameters and the heave and pitch RAOs. The comparison between the regression model and strip theory results shows that the prediction error remains within 5%, indicating that the regression model can provide an efficient surrogate objective function for hull-form optimization. The particle swarm optimization (PSO) algorithm is then employed to optimize the hull form, with the ship length, breadth, draft, and block coefficient considered as design variables. To further evaluate the optimized hull, additional calculations are conducted under different Froude numbers and encounter angles. Under head sea conditions with varying Froude numbers, the optimized hull reduces the peak heave RAO by 11.6–31.1% and the peak pitch RAO by 8.6–17.9%. Under different encounter angles at Fr = 0.3, the reductions in peak heave and pitch RAOs are 31.1–33.9% and 16.5–18.8%, respectively. These results demonstrate that the proposed regression assisted PSO optimization framework can effectively reduce the heave and pitch responses of the Wigley hull under the investigated regular wave conditions.

Chrs-Net: A Dual-Stream YOLO Network for Underwater RGB–Sonar Object Detection - Chuheng Zhang; Hongli Xu; Pangyi Xiao; Han Wang; Jingyu Ru; Hongxu Yang (Journal of Marine Science and Engineering, 2026)
Underwater RGB–sonar object detection remains challenging due to severe optical degradation, strong sonar noise, and spatial misalignment between heterogeneous modalities. Existing multimodal detectors usually rely on simple feature aggregation or limited structural coupling, which cannot effectively model global cross-modal dependencies or address modality-specific degradation. To address these challenges, we propose Chrs-Net, a YOLOv12-based dual-stream framework for underwater RGB–sonar object detection. The proposed network integrates three key components: a Transformer-based Cross-Modal Communication Fusion module (C-mcf) for global cross-modal interaction and semantic alignment, a Multi-Layer Feature Enhancement module (MLFE) for degraded optical feature enhancement, and a Pinwheel-Shaped Convolution module (PConv) for sonar-side structural feature extraction. In addition, an RGB–sonar object detection dataset is constructed for experimental evaluation by relabeling part of the RGBS benchmark, combining simulator-collected samples, and introducing style-transfer-based augmentation to improve data diversity. Experiments on the constructed dataset yield 94.91% mAP@0.5 and 61.10% mAP@0.5:0.95 on the RGB branch, and 94.00% and 57.13% on the sonar branch, respectively, with an inference speed of 53.6 FPS. Compared with representative single-modality and multimodal detectors, Chrs-Net consistently yields superior detection accuracy and localization performance. These results demonstrate that the combination of global cross-modal communication and modality-specific enhancement is effective for robust underwater RGB–sonar object detection in complex environments.

Integrative analysis of lncRNAs associated with disulfidptosis-related genes for prognostic risk evaluation and tumor immune microenvironment assessment in laryngeal squamous cell carcinoma - Qinghua Liu; Zesheng Zhang; Yingli Xie; Ru Tang; Ge Gao; Zhe Yang; Duanshali Liu; Yilun Zou; Yongxia Zhang; Mingbo Liu (Human Cell, 2026)

Mechanisms of flow-induced noise and control in underwater grille-cavity systems: Effects of grille number and inclination - Qing-Shuang Zhang; Yong-Liang Xiong; Ru-Nan Hua; Guo-Cang Sun; Dan Yang (Ocean Engineering, 2026)

Non-biodegradable microplastics amplify antibiotic resistance and pathogen spread in bay plastisphere - Zhi-Wei Wei; Huan-Qin Li; Xin-Hong Wang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Population genomics reveals environmental reservoirs and antifungal resistance mechanisms in major non-albicans Candida species - Yuhang Zhang; Xiao-Ru Yang; Shuang Wang; Jian-Qiang Su; Yong-Guan Zhu (Journal of Environmental Sciences, 2026)

Mask-CDKD: A source-free and label-free cross-domain knowledge distillation framework from SAM for satellite onboard VHR land-cover mapping - Daoyu Shu; Zhan Zhang; Xiao Huang; Ru Wang; Nan Jia; Xinzhe Fu; Bingnan Yang; Fang Wan; Jianzhong Lu; Jianya Gong (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Carboxymethylated PGA/ASK composite: Synergistic mechanism for stabilizing protein network and improving freeze resistance of shrimp gel - Kaina Duan; Zijing Liu; Luhan You; Jie-ting Geng; Wenge Yang; Huamao Wei; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2026)

Interventional mechanisms of antioxidants on flavor profile modification in the fermented egg white powder system - Ru-yi Zhang; Zhi-shuo Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Terbium chloride post-treatment for highly efficient and stable Sb2(S,Se)3 solar cells - Shengquan Shan; Jihao Ma; Yang Chen; Lun Zhang; Chengyang Wang; Yanrui Yang; Ru Zhou; Mei Lyu; Jun Zhu (Chemical Engineering Journal, 2026)

Cyanobacteria-driven morphology and adaptive microbial succession: Resilience mechanisms in algal-bacterial granular sludge under tripartite stress - Qingyue Shen; Jiu-Qiang Xiong; Qian Wang; Liqiang Yang; Zhonghua Shen; Zhongfang Lei; Shaoguo Ru (Bioresource Technology, 2026)

Enhancing camptothecin biosynthesis in Camptotheca acuminata through CrLAMT transfer from Catharanthus roseus - Ru Huang; Wen-Hui Ma; Bing-Run Yang; Fang Yu; Ping Kou (Biotechnology Letters, 2026)

Functional homogenization of terrestrial mammals outside protected areas in the Hengduan Mountains, China - Xueyou Li; Wenqiang Hu; Kenneth Otieno Onditi; Quan Li; Zhechang Hu; Ru Bai; Yang Liu; Hongjiao Wang; Xuelong Jiang (Conservation Biology, 2026)
Despite the crucial role of human impacts on biodiversity loss, many assessments of this loss focus on single metrics, such as species richness, and overlook the multidimensional effects of human activities. Because of its importance to ecosystem functioning, we investigated the functional diversity of medium‐ and large‐sized mammal assemblages in protected and unprotected mountain forests in the Hengduan Mountains of southwest China. We hypothesized that anthropogenic pressures outside protected areas (PAs) favor generalist species and lead to functionally homogenized assemblages compared with assemblages inside PAs. Using generalized dissimilarity models, we also examined the key drivers shaping patterns of functional β diversity in these landscapes. Outside PAs, functional richness was markedly lower, trait space was significantly more homogeneous, and nestedness β diversity was more prevalent (57.6%) than inside PAs, clear indications of functional homogenization. Anthropogenic variables consistently outweighed environmental gradients and spatial distance in explaining variation in functional β diversity. Our results demonstrate that anthropogenic pressure affects trait composition in ways that species counts alone do not fully capture, emphasizing the importance of conservation strategies that protect both functional integrity and taxonomic diversity.

Brain Serotonin Deficiency Impairs Ovarian Reserve Function via the Hypothalamic-Pituitary-Ovarian Axis - Shuang-Shuang Cui; Zhuo-Nan Yang; Jin Xiao; Jin-Ping Qiao; Yue-Ming Zhang; Ling-Ge Shi; Hui-Ru Cheng; Si-Min Ding; Meng-Yao Wang; Dong-Mei Ji; Tao Zhang; Dan Liang; et al. (Neuroscience Bulletin, 2026)

Exploring the characteristics of smoke back-layering during lithium-ion battery fires in confined tunnel spaces - Yuan Wang; Wenhao Xue; Zhaojie Zhu; Yang Lou; Ru Zhou; Min Hao; Juncheng Jiang (Process Safety and Environmental Protection, 2026)

Synergistic inhibition of advanced glycation end products and enhancement of flavor by the combination of oligomeric proanthocyanidins and glycated yeast proteins - Jing-jing Fu; Bo-wen Ru; Qi-cheng Zhang; Yu-jun Wu; Hai-yang Feng; Lian-ping Zheng; Yue-wen Chen (Food Research International, 2026)

Single-cell transcriptomics reveal PRRC1 as a malignant cell enriched driver of DNA repair and therapy resistance in glioblastoma - Sachin Kumar; Ming-Cheng Tsai; Dahlak Daniel Solomon; Juan Lorell Ngadio; Do Thi Minh Xuan; Ching-Chung Ko; Hung-Yun Lin; Meng-Chi Yen; I-Jeng Yeh; Yung-Kuo Lee; Hui-Ru Lin; Jian-Ying Chuang; et al. (DNA Repair, 2026)

Molecular epidemiology reveals co-circulation of five Anaplasma species with zoonotic potential in sheep and goats from Henan province, China - Jia-Run Yang; Wei-Hao Tan; Jie-Yue Liang; Jing-Rong Li; Yu-Ru Cao; Wan-Yu Li; Jian-Wei Shao (Comparative Immunology, Microbiology and Infectious Diseases, 2026)

Coir and sisal Fiber-based woven pressure sensors: 3D reinforced architectures, synergistic interfacial modulation, and wrinkle-response low-cost monitoring - Renyan Yang; Shaofeng Ru; Yifan Zhang; Xueliang Zhang; Songmei Yang (Chemical Engineering Journal, 2026)

Study of enhancing analgesic potential of μ-conotoxins from the computational and pharmacological insights - Fan Zhao; Yunxia Liu; Ying Cui; Yushan Ding; Liu Ru; Ting Meng; Hongtao Yang; Yongbo Song (Molecular Diversity, 2026)

Accelerating carbon neutrality intensifies trade-offs in China’s energy-water-food nexus - Zhongshi Tang; Tao Wang; Sandylove Afrane; Nihed Benani; Yan Ru Fang; Pingjian Yang (Resources, Conservation and Recycling, 2026)

Insights into frozen quality preservation and energy conservation of salted swamp eel (Monopterus albus) fillets - Hongwei Song; Yajin Zhang; Hong Yang; Ru Liu; Tao Yin; Liu Shi; Juan You (International Journal of Refrigeration, 2026)

Distinguishing the contributions of organic matter and iron (oxyhydr)oxides to zinc availability in paddy soils surrounding lead-zinc mines - Yecheng Li; Zebin Hong; Yan Ru; Guojun Chen; Xiaomin Li; Shiwen Hu; Yang Yang; Chao Guo; Shan Wang; Pengfei Cheng; Qi Wang; Tongxu Liu (Environmental Pollution, 2026)

Identification of key factors influencing monthly runoff simulation through the integration of deep learning and physically-based hydrological models - Jiyu Zhang; Yufeng Wang; Liangjie Zhao; Ru Sun; Jiayu Sun; Shufei Wang; Shiqin Xu; Zhe Yang (Environmental Modelling & Software, 2026)

Drivers of urban street blocks thermal pleasure: SHAP interpretation of psychological, environmental perception, and microclimate factors - Xiaodong Xuan; Ru Liu; Zixu Zhang; Leiming Yang; Yihe Zheng; Yongjian Liu (Energy and Buildings, 2026)

Multi-channel carbon nanofibers with enhanced ion diffusion and ultra-stability for flexible supercapacitors at commercial-scale mass loading - Guangjie Yang; Yulong Yang; Jian Song; Zhenye Yin; Qian Zhang; Zhenlu Liu; Haoqi Yang; Min Ru; Shaochun Tang; Shuijian He (Chemical Engineering Journal, 2026)

Anodic potential and conductive carrier synergistically drive nitrite-free extracellular electron transfer-dependent anaerobic ammonium oxidation (Anammox) in mixed microbial communities - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Fei-Fan Shi; Ru Fan; Jia-Ying Xu (Bioresource Technology, 2026)

Coronary CT Angiography-Based Prediction Model for Hemodynamically Significant Coronary Stenosis Integrating Morphological and Plaque Characteristics - Chenxi Wang; Shuang Leng; Ru-San Tan; Ping Chai; Jiang Ming Fam; Adrian Fatt Hoe Low; Lohendran Baskaran; Lynette Teo; Felix Yung Jih Keng; Chee Yang Chin; Ching Ching Ong; John C. Allen; et al. (Cardiovascular Engineering and Technology, 2026)

Protist‐Bacteria Trophic Interactions Contribute to Higher Community Stability in Subsoils Than Topsoils - Suo Liu; Jingyi Ru; Sihang Deng; Jiesi Lei; Zhencheng Ye; Yu Tang; Changchun Zhai; Shiqiang Wan; Yunfeng Yang (Global Change Biology, 2026)
Climate change is reshaping ecosystem components and functions across soil profiles. In this study, we examined the effects of altered precipitation and nighttime warming on soil microbial communities in both topsoils (0–20 cm in depth) and subsoils (20–50 cm in depth) in a long‐term field experiment in Inner Mongolia, China. Unexpectedly, moisture, belowground net primary production, and NO 3 − content in subsoils were all affected more by climate changes than topsoils. Moreover, using multiple resistance metrics, including α‐diversity, β‐diversity, microbial network complexity, and network robustness, we found that both bacterial and protistan communities in subsoils exhibited greater resistance to climate change than those in topsoils, while fungal communities showed no consistent pattern. Enhanced bacterial resistance in subsoils was associated with lower 16S rRNA gene operon ( rrn ) copy number, reduced GC content, lower genome and cell size, and other oligotrophic traits, collectively supporting adaptation to nutrient‐poor and stressful environments. Protistan resistance in subsoils tracked bacterial resistance and was reinforced by stronger trophic interactions and functional traits such as protective shells, greater motility, and reduced cell size, reflecting a bottom‐up control, as soil protists are primarily phagotrophs shaped by bacterial prey supply. Abundant bacteria enhanced resistance through oligotrophic adaptations and positive intra‐community interactions, while abundant protists reduced resistance, potentially due to the dominance of negative intra‐community interactions. Partial least squares analyses revealed that microbial community resistance modulated soil heterotrophic respiration (R h ), connecting community resistance to carbon cycling. Together, these findings demonstrate that the often‐overlooked resistance of subsoil microbiomes could buffer ecosystem functions under future climate conditions, suggesting that traits (e.g., rrn copy number) and trophic interactions can outweigh diversity for community stability.

Studies on secondary metabolites and anti-inflammatory activity of fungus Penicillium citreosulfuratum YFC-1 from Sphagneticola trilobata - Zhao-xia Chen; Wen-xing Li; Ru-tong Chen; Yang Hui; Zhen-fan Sun; Wen-hao Chen (Natural Product Research, 2026)

Novel biodiversity and biogeography insights of filamentous Bangiales (Rhodophyta) from China - Yan-De Wang; Yin-Yin Deng; Cui-Cui Tian; Han-Ru Ge; Wei Zhou; Nan-Jing Ji; Li-En Yang (Algae, 2026)
The taxonomy of filamentous Bangiales was challenging due to its plastic and simple morphology. Molecular approaches play a significant role in revealing cryptic biodiversity and resolving phylogenetic relationships. Nonetheless, the biodiversity of filamentous Bangiales in many regions, including China, has not been thoroughly investigated yet using updated methods. In this study, we investigated the biodiversity of filamentous Bangiales in China, employing a more comprehensive and detailed sampling approach. The rbcL and 18S gene sequences (partial or complete) of 49 specimens collected from 37 sites were obtained. Phylogenetic analysis resolved these specimens into four clades, including Bangia, ‘Bangia’ 1, ‘Bangia’ 2, and Pseudoganglia. Seven putative species were delineated using empirical methods, including Automatic Barcode Gap Discovery (ABGD), General Mixed Yule Coalescent (GMYC), and Bayesian Poisson tree processes (bPTP), as well as genealogical analysis. Among them, four were species previously reported, two were cryptic species, and the other was a new record in China. The distribution of these molecularly delineated species was mapped along China’s coastline. Similar to the bladed Bangiales, antitropical, transoceanic, and thermal-gradient distribution patterns were also observed for filamentous Bangiales on a global scale. The ancestral region was retraced by incorporating species data from China into existing datasets using BioGeoBEARS with BAYAREALIKE + J as the best-supported model. Under this model, East Asia shows the highest marginal probability as the ancestral area for the crown clade, though uncertainty remains across alternative regions. A most parsimonious expansion scenario of Bangiales from east Gondwana to other regions of the world was proposed.

Rotavirus induces mucosal B-cell responses through the TLR3/TRIF and MAVS pathways - Rong-Rong Zhang; Yong-Yi Yang; Man Wang; Wen-Ru Yang; Riaz Muhammad Azeem; Fu-Xuan Niu; Ya-Xin Yang; Man-Jie Hu; Chun-Wei Shi; Gui-Lian Yang; Hai-Bin Huang; Jian-Zhong Wang; et al. (Veterinary Microbiology, 2026)

The role of artificial intelligence in advancing population-based cancer registration - Shuai Ding; Mingyuan Liu; Hao Wang; Cheng Song; Luyue Zhao; Zhihao Yang; Yue Wang; Yifan Wang; Haitao Cui; Zihao Liu; Dongrun Liu; Tomohiro Matsuda; et al. (Science Bulletin, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Exploratory analysis of epigenetic dynamics and small extracellular vesicles in Penaeus vannamei hemocytes under inactivated Vibrio parahaemolyticus priming - Yu-Ru Lin; Guan-Lin Lai; Yu-Hsuan Sun; Ta-Jeng Yang; Ting-Yu Huang; Huu-The Nguyen; Muhammad Ar Rozzaaq Nugraha; Novi Rosmala Dewi; Yeh-Fang Hu; Fan-Hua Nan (Journal of Invertebrate Pathology, 2026)

Temperature-driven regime shifts in riverine bacterial communities: Machine learning identifies key thresholds and seasonal management implications - Ru Liu; Peng Wang; Wang Shu; Mingjun Ding; Minghua Nie; Gaoxiang Huang; Hua Zhang; Qinwei Chen; Wei Yang (Journal of Environmental Sciences, 2026)

Preparation of indicator cards for freshness detection of rice with four different processing degrees during storage based on olfactory visualization technology - Wan-ru Liu; Yang Yang; Yue Xu; Bing Wang; Guang Zhang; Xin-yu Xu; Yuan-yuan Wang; Chun-min Ma; Na Zhang (Food Chemistry, 2026)

Mechanism of the influence of single-phase dynamic gelation process on the structure and properties of bigels - Yanlei Gao; Qing Xiong; Shilin Zhao; Qilin Huang; Yang Hu; Ru Liu (Food Hydrocolloids, 2026)

Mechanism of adsorption and biodegradation of typical antibiotics by sediments in mariculture tailwater system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Zhi-Wei Zhou; Ze-Dong Lu; Xiao-Yan Fan (Environmental Research, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Short-duration electrical pulse stimulation induces myokines and mitochondrial adaptations in C2C12 myotubes - Shih-Hua Fang; Ming-Ru Chiang; Chia-Yang Li; Pei-Ying Li; Zong-Jia Wu; Hsin-Hua Li (Journal of Muscle Research and Cell Motility, 2026)

Bridging Aquaculture and Human Medicine: A Comprehensive Review of Zebrafish Models for Chronic Kidney Disease - Feng‐Yi Guo; Hao‐Yu Yang; Lan‐Chen Zhang; Xiang‐Ru Liu; Pan‐Pan Jia; De‐Sheng Pei (Reviews in Aquaculture, 2026)
Chronic kidney disease (CKD) poses a significant global health burden, necessitating robust animal models for mechanistic studies and drug discovery. Zebrafish offers unique advantages as a powerful models in kidney disease, including high‐throughput compatibility, optical transparency, and significant genetic and nephron homology with both humans and farmed teleosts. However, challenges, such as the species' potent regenerative capacity and a lack of standardized diagnostic thresholds, hinder their broad application. This review systematically summarizes four principal induction strategies: environmental stress, nephrotoxic chemical exposure, CRISPR/Cas‐based gene editing, and transgenesis. We further outline a validation pipeline that integrates functional assays, morphometrics, and histopathology, while advocating for cross‐laboratory harmonization. Additionally, we compare risk factors for CKD and CKD of unknown etiology (CKDu), emphasizing environmental contributors. Collectively, we propose zebrafish as a reproducible platform for aquaculture applications, specifically for nephropathy early‐warning systems and functional feed assessment, and for human therapeutic research. These standardized models hold great promise for high‐throughput drug screening and elucidating disease mechanisms, facilitating the translation of findings to both aquaculture and clinical medicine.

Incorporating NH4+–N volatilization and adsorption into a prediction model of soil nitrogen transport for surface runoff based on soil mixing layer theory using an ensemble Kalman filter approach - Ziyao Ru; Juxiu Tong; Yang Gu (Journal of Hydrology, 2026)

Sand flux patterns derived from static morphology and migration behavior of barchan dunes in the Taklamakan Desert - Yuan Wang; Peng Liang; Xiaoping Yang; Jiwei Wu; Tinglin Ru; Zihan Wu (Geomorphology, 2026)

Quantifying contributions of iron (oxyhydr)oxides and organic matter to chromium dynamics in paddy soils - Guojun Chen; Yang Yang; Ke Zhang; Yan Ru; Zebin Hong; Xiaomin Li; Taicheng An; Pei Wang; Songxiong Zhong; Qi Wang; Shiwen Hu; Fangbai Li; et al. (Geochimica et Cosmochimica Acta, 2026)

The protective effects of alkaloids from Stephania tetrandra S. Moore on H9C2 cardiomyocytes - Yan-nan Ji; Ran Zhou; Zhi-hui Zhang; Xing-ru Gao; Si-qian Yang; Pu-yu Yang; Zi-shan Chen; Jun-li Sha; Jing-yu He; Yue-feng Zhang; Tie-jun Zhang; Yu-cheng Gu; et al. (Natural Product Research, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Optimizing the spatial configuration of scallop suspended cultivation net cages by leveraging seston flux variables based on the lattice Boltzmann hydrodynamics - Gangqin Tu; Haifei Liu; Zhiming Ru; Tao Sun; Wei Yang; Wei Huang; Li Cheng (Aquaculture, 2026)

Near-full-component sewage sludge valorization via integrated alkali-mediated pyrolysis and sub-boiling temperature crystallization of hierarchical carbon-zeolite composites from carbonaceous and inorganic constituents - Zhihang Yuan; Houmin Yin; Jicui Cui; Changfu Yang; Zhou Zhen; Xiaohan Cui; Yumeng Jin; Lifeng Lin; Long Kong; Ruina Zhang; Ruyi Wang; Lei Che; et al. (Water Research, 2026)

Changes in tree composition and diversity of streetscapes and their impact on allergenic risk of pollen during urban expansion: a case study in Chengdu, China - Ming-kun Chen; Zhen-ru Yang; He Li; Hua Zong; Chen Jiao (Landscape and Urban Planning, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Strength enhancement and microstructural observation of cement-stabilized calcareous sand by optimizing the preparation process - Weishen Li; Yang Wu; Xue Li; Han Ma; Yifei Ru; Xiangxing Ye (Journal of Cleaner Production, 2026)

Effects of nighttime warming and nitrogen addition on phytoplankton biomass in a submerged macrophytes-dominated freshwater wetland - Yaru Lyu; Jiayin Feng; Wenjing Ma; Chao Wang; Mengyu Yan; Zixuan Yang; Yunpeng Guo; Jinhua Zhang; Hongpeng Wang; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Journal of Environmental Sciences, 2026)

Biofilm-mediated mitigation of nitrous oxide emissions in anammox-based wastewater treatment - Zhiman Lin; Jinfan Zhang; Ru Wang; Jingmin Ou; He Zhang; Zihua Wang; Fangyuan Zheng; Xiantao Sun; Xin Wei; Yiming Huang; Zhenguo Chen; Mark C.M. van Loosdrecht; et al. (International Biodeterioration & Biodegradation, 2026)

Longitudinal monitoring of global prevalence, genomic characterization and transmission routes of Salmonella Derby strains from food, humans and the environment - Min-Ge Wang; Dong-Xiao Ru; Ying-Xin Ruan; Ying Chu; Peng-Yu Zhang; Sheng Chen; Ruan-Yang Sun (Food Research International, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Quantitative resolution analysis in seismic imaging: From classical theory to cutting-edge advances - Jidong Yang; Jianping Huang; Hejun Zhu; Jiaxing Sun; Li-yun Fu; George McMechan; Houzhu Zhang; Ru-Shan Wu (Earth-Science Reviews, 2026)

Built-in electric field and surface adsorption enhanced gas detection of muti-interface MXene/TiO2/Bi2MoO6 integrated heterostructure - Yan Liang; Peipei Yan; Xiaojian Zhao; Chunbo Ru; Lu Tang; Yu Jiang; Yong Yang (Chemical Engineering Journal, 2026)

Soil respiration and its temperature sensitivity on croplands in response to biotic and abiotic factors under straw and nitrogen fertilizer management - Ru Guo; Ruixuan Hao; Xiaoyi Yang; Rui Qian; Zijun Ma; Yunyun Yang; Peng Zhang; Zhikuan Jia; Yuncheng Liao; Xiaolong Ren; Xiaoli Chen (CATENA, 2026)

Behaviors and adaptive strategies of anammox microbiota in response to typical ionic liquid: Metabolic compensation and gene regulation - Dong-Jun Hou; Wei-Lin Guo; Hong-Wei Yang; Qian-Ru Liu; Nian-Si Fan; Ren-Cun Jin (Bioresource Technology, 2026)

Reconstructing historical cloud ice water fraction using machine learning and multi-source satellite data from 1983 to 2009 - Dezhi Xiao; Chunsong Lu; Sinan Gao; Jiashan Zhu; Yang Li; Ru Zhou; Junjun Li; Jing Yang; Naifu Shao (Atmospheric Research, 2026)

Continuous Removal of Fluoride by Fe/Al-Anchored Bamboo Charcoal in Fixed Bed Column and Prediction of Breakthrough Curve using Artificial Neural Network Model - Shuqin Bai; Ru Ya; Wei Ding; Xiaohua Xie; Mingjun Zhou; Guojing Zhao; Tianxu Yang (Water, Air, & Soil Pollution, 2026)

Microglial Activation Mediates Drp1-Dependent Mitochondrial Fission and Neuronal Apoptosis in a Lipopolysaccharide-Induced Model of Cognitive Dysfunction - Meng-Jie Chen; Jia-Qi Ning; Jia-Xi Liu; Jian-Sheng Luo; Ru-Yu Yan; Yu-Xuan Yang; Xiang Li; Ling-Ling Ding (Molecular Neurobiology, 2026)

Fluorescent aptasensor based on magnetic bead–assisted displacement reaction for monitoring vancomycin in plasma - Cheng-Shiuan Hsieh; Hsu-Yun Tsai; Ting-Chien Tsai; Yang-Chun Wang; Yi-Tung Cheng; Jing-Ru Liou; Meng-Yu Liu; Yen-Ling Chen; Chien-Chin Chen (Analytica Chimica Acta, 2026)

Assessing the atmospheric deposition of inorganic nitrogen and phosphorus over the Yellow Sea - Limin Yu; Ru Li; Chong Zhang; Hao Sun; Zhe Zhang; Pengfei Zhao; Pengji Zhang; Fan Yang (Regional Studies in Marine Science, 2025)

Omics-based investigation of microplastic effects on aquatic life: A comprehensive review - Adolf Acheampong; Zhi-Wei Wei; Le-Yang Yang; Qiu-Xia Geng; Xin-Hong Wang; Xiao-Ru Yang (Journal of Environmental Chemical Engineering, 2025)

An intelligent and active polyvinyl alcohol hydrogel packaging incorporating alizarin and Zn-MOF for shrimp freshness monitoring and preservation - Min Zhang; Enguang Zuo; Xiaoxi Wu; Yuanjia Wang; Wenxue Xiao; Huamao Wei; Ru Jia; Tao Huang; Wenge Yang; Zhaohui Qiao (Food Chemistry, 2025)

Electrostatic spray drying enhances transferrin hydrophilicity for improved rosmarinic acid binding: Insights into biological activity and molecular mechanism - Ru-yi Zhang; Zhi-shuo Zhang; Ting-ting Tang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Yan-jun Yang; Cui-hua Chang (Food Chemistry, 2025)

Fermented Broussonetia papyrifera leaves on growth performance, immune responses, and resistance to Vibrio of shrimp - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Effects of feed supplementation with fermented Broussonetia papyrifera leaves on non-specific immune responses, resistance to Vibrio parahaemolyticus, growth, intestinal histology, and microbiota of white shrimp (Penaeus vannamei) - Guan-Lin Lai; Yu-Ru Lin; Ta-Jeng Yang; Yu-Ting Chu; Fan-Hua Nan; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

Sustainable extraction of high-quality coconut husk fibers: A comparative study of chemical, boiling, and physical methods - Shaofeng Ru; Xueliang Zhang; Renyan Yang; Yifan Zhang; Songmei Yang (Food and Bioproducts Processing, 2025)

Performance and toxicity assessment of photocatalytic degradation of sulfanilamide by g-C3N4 nanosheets constructed using temperature gradient regulated etching - Yujie Jiao; Yaqi Mao; Fei Fu; Yongxia Ma; Ru Li; Qikai Liu; Jiali Lei; Sujin Lu; Yang Liu (Environmental Research, 2025)

Exploring the potential of radar vegetation indices for soil parameters retrieval: a case study of remote sensing soil salinity mapping - Aihepa Aihaiti; Ilyas Nurmemet; Yu Qin; Bilali Aizezi; Yang Xiang; Meimei Zhang; Yixin Zhang; Ru Feng (CATENA, 2025)

Pyrolysis behavior of local environmentally harmful Erigeron Canadensis L.: a kinetic model using thermogravimetric analysis and multi-prediction - Tianrui Han; Ke Xie; Xiaolei Ye; Lei Gao; Shenghui Guo; Haohang Ji; Juanjian Ru; Botao Gao; Li Yang (Biomass and Bioenergy, 2025)

Correction: The correlation of fibrinogen‑like protein‑1 expression with the progression and prognosis of hepatocellular carcinoma - Nanni Hua; Anxian Chen; Chen Yang; Hui Dong; Xianglei He; Guoqing Ru; Xiangmin Tong; Feifei Zhou; Shibing Wang (Molecular Biology Reports, 2025)

Low-intensity pulsed ultrasound promotes proliferation and differentiation of neural stem cells to enhance spinal cord injury recovery - Ye-Hui Liao; Min-Hao Tian; Wen-Yang Zhou; Bao-Qiang He; Chao Tang; Qiang Tang; Ru-Pei Ye; De-Jun Zhong (Molecular Biology Reports, 2025)

Refining Middle–Upper Ordovician Conodont Biostratigraphy in the Hatuke Creek Section, Western North China Craton: Evidence from Bedding Plane Assemblages and Implications for Shale Gas Exploration - Xiuchun Jing; Yang Shen; Ru Fan; Shengju Yin; Jingjing Fan; Jitao Chen (Journal of Earth Science, 2025)

Nitrogen enrichment offsets the stimulation of soil respiration by increased precipitation in temperate grasslands - Ru Tian; Jiatao Zhang; Yan Shen; Lan Du; Jinbao Zhang; Shijia Yang; Zhongxiang Liu; Mengle Wang; Zhuwen Xu (Agricultural and Forest Meteorology, 2025)

Mechanism of Permeability Evolution in Coral Reef Limestone Under Variable Confined Pressure Using Nuclear Magnetic Resonance Technology - Yang Mo; Haifeng Liu; Yongtao Zhang; Shun Zhai; Peishuai Chen; Ru Qu; Fuquan Ji (Journal of Marine Science and Engineering, 2025)
The development of underground space in the South China Sea islands is an important way to enhance their protection capabilities. This study focuses on the stress loading and unloading conditions of surrounding rock during the excavation of underground caverns in island reefs. Laboratory variable confining pressure permeability tests were conducted to quantify the stress sensitivity of permeability in coral reef limestone based on Darcy’s law and the stress sensitivity index model equation for permeability. In addition, the use of nuclear magnetic resonance technology reveals the microscopic mechanism of coral reef limestone permeability evolution. The results of the experiments show that the permeability of coral reef limestone sample is mainly controlled by the advantaged permeable channels formed by large pores. During the stress loading stage, the pore structure inside the sample changes, with compression of large pores and generation of smaller pores, resulting in a decrease in effective permeable pathways and a decrease in permeability. When the stress loading reaches 4 MPa, the damage rate of the sample’s permeability is 19.6%. During the stress unloading stage, the recovery of the sample’s permeability shows a significant hysteresis effect. Due to the irreversible damage caused by the compression and collapse of the pore structure during the loading stage, the permeability of the sample cannot fully recover when unloaded to the initial stress state. Based on the experimental results, calculations show that the stress sensitivity coefficient of coral reef limestone permeability is 1.1 × 10−1 MPa−1, which is higher than that of conventional land-based rocks. The conclusions of this study can provide important design references for the stability control of surrounding rocks and geological hazard prevention during the excavation of underground chambers on the islands.

The function of salt responsive promoter of Suaeda salsa SsCLCb explains why the species can accumulate large amount of nitrate from saline soils - Chenyang Li; Runtai Zhao; Ru Liu; Ruiqi Zhang; Xiaolei Yang; Chaoran Shi; Lei Wang; Jie Song (Marine Pollution Bulletin, 2025)

Metagenome-assembled genomes reveal Pseudogracilibacillus amylolyticus sp. nov., a functional uncultured microorganism in high-temperature Daqu - Ai-Ping Lv; Ying-Han; Bao-Zhu Fang; Guo-Zheng Wang; Man-Chun Liu; Bing-Ru Bian; Zhuo-Huan Zheng; Kai Li; Bing-Yu Li; Jian-Yu Jiao; Lan Liu; Lei Dong; et al. (Systematic and Applied Microbiology, 2025)

Schwertmannite maintains effective stabilization of arsenic in flooded paddy soil: Insights from a two-season rice experiment and underlying mechanisms - Ru Wang; Yang Song; Yinglin Guo; Nan Ge; Xiaomeng Wang; Lixiang Zhou; Guanyu Zheng (Journal of Hazardous Materials, 2025)

NCOA4-dependent ferritinophagy drives perfluorooctanoic acid-triggered renal ferroptosis in chicken embryos - Jie Yang; Xue Wen; Yi-Tong Fu; Chao Li; Hai-Long Chang; Yao-Yao Lu; Xue-Ru Li; Rui-Feng Fan (Journal of Hazardous Materials, 2025)

Machine learning-enhanced prediction of size-resolved gas-particle partitioning quotient: Implication for health risk assessment of polycyclic aromatic hydrocarbons - De-Qi Wang; Wan-Li Ma; Ru-Peng Wang; Pu-Fei Yang; Peng-Tuan Hu; Shi-Ming Jia; Meng Qin (Journal of Hazardous Materials, 2025)

Effects of pressure cooker treatment-induced protein oxidation of cereals on human gut microbiota using an in vitro fermentation model - Keying Chu; Xiaojie Cui; Yuhui Yang; Qiong Wu; Ru Liu; Yanli Xie (Food Research International, 2025)

Molecular insights into freeze–induced quality deterioration in surimi: Mechanisms and mitigation strategies - Zhijun Yang; Qing Xiong; Tao Yin; Juan You; Shanbai Xiong; Ru Liu (Food Chemistry, 2025)

Effects of EGCG/TGase on the physicochemical properties and in vitro dynamic digestion characteristics of water-saving rinsed surimi gels - Qin Yang; Weixia Zhou; Die Hu; Chuan Li; Lu Zhang; Yongqiang Zhao; Shengbi Zou; Ru Liu; Youming Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Insights into cell wall metabolism and remodeling process of postharvest Coprinus comatus fruiting body - Yilong Zou; Yaru Zhang; Ru Li; Huabin Zhou; Hang Qu; Hailong Yang (Food Chemistry, 2025)

Insights into the synergistic cross-linking effect of EGCG and TGase on surimi gels - Qin Yang; Jinling Li; Wentao Ma; Ru Liu; Shengbi Zou; Yongqiang Zhao; Shanbai Xiong; Jianhua Rong; Yang Hu (Food Chemistry, 2025)

A novel thermophilic α-glucan phosphorylase enables molecular weight-tunable amylose biosynthesis from cellobiose via a dual-enzyme cascade system - Wei Gao; Ru Yang; Mengli Li; Ming Miao; Tao Zhang (Food Bioscience, 2025)

PcSRB cooperates with TLR2 and promotes phagocytosis and antimicrobial peptides expression - Meng-Ke Shan; Jing-Xin Dai; Wen-Ya Li; Jing-Ru Zhu; Gui-Wen Yang; Hui-Ting Yang (Fish & Shellfish Immunology, 2025)

Enrichment of Feammox microflora utilizing in-situ iron in excess activated sludge: substrate metabolism, gene variation, and microbial communities - Maoxia Chen; Jing Ru; Yan Yi; Yang Li; Liang Wu; Huiling Jiang (Bioresource Technology, 2025)

Multi-omics decodes exercise-induced geroprotection: betaine unlocks aging delay via TBK1 inhibition - Yang Li; Liang Guo; Ru Wang (Science China Life Sciences, 2025)

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Salicylic acid promotes arsenic uptake in Pteris vittata via regulation of key genes and elevated nitric oxide and spermidine - Zhi-Hua Dai; Ze-Chao Li; Xi Chen; Ru Huang; Jian-Hua Sun; Chen-Jing Liu; Lena Q. Ma; Ru-Yi Yang (Journal of Hazardous Materials, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Multi-omics insights into micro-oxygen-regulated microbial decolorization and metabolic pathways during hydrolysis and acidification of textile wastewater - Jiehui Ren; Qian Peng; Zhejun Du; Xiaoxin Yang; Jiayao Hui; Ru Li; Wen Cheng (Journal of Cleaner Production, 2025)

Protein structural transitions and cryo-stability of shrimp gel: Effects of setting time at 30 °C in a novel processing system - Kaina Duan; Lechang Sun; Jie-ting Geng; Wenge Yang; Huamao Wei; Tao Huang; Ru Jia (Innovative Food Science & Emerging Technologies, 2025)

Structural characterization, interaction mechanism and thermal stability of dual-fibrous complexes formed by rice glutelin fibrils and cellulose nanocrystals - Yi-Xuan Jiang; Ya-Ru Wang; Qin Yang; Xiao-Hong Yu; Han-Qing Chen (Food Chemistry, 2025)

Mitigating fishy odor in surimi gels: Interactions between myofibril proteins and chito-oligosaccharides - Huifang Yang; Jing Qiu; Ramy M. Khoder; Shanbai Xiong; Ru. Liu; Yueqi. An (Food Hydrocolloids, 2025)

Uncertainty quantification of ensemble inverse analysis for rainfall-induced slope failure using mixture probabilistic programming - Qi Li; Yifei Ru; Ziyu Tao; Yang Wu (Engineering Geology, 2025)

Fabrication of self-supported amorphous layered double hydroxides/bamboo biochar electrode for boosting its performance as symmetric supercapacitors - Zhuo Wang; Xiao Li; Qing Cai; Zhao-Yang Pan; Li Li; Yuan-Ru Guo; Qing-Jiang Pan (Chemical Engineering Journal, 2025)

In/S co-decorated SnSe encapsulated in a dual carbon layer for sodium ion storage - Ya Ru Pei; Yong Jin Xia; Lei Ming Wang; Rui Li; Jun Xi Peng; Xue Jing Yang; Jian Li; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2025)

Corrigendum to “Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices” [Chem. Eng. J. 510 (2025) 161390/CEJ 161390] - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

The industrial biocide benzisothiazolinone impairs pathogen resistance in larval zebrafish by inducing microbiota dysbiosis - Meiping Guo; Yue Wang; Yang Yang; Lei Shao; Shuhui Wei; Liqiang Yang; Pengfei Cui; Shaoguo Ru; Xiaona Zhang (Aquatic Toxicology, 2025)

Interactions between soil and phyllosphere microbiomes modulate flavor formation of Qingxiang Tieguanyin Oolong Tea - Zhao Zhang; Xin-Rong Huang; Ming-Kang Jin; Le-Yang Yang; Jing-Jun Deng; Hu Li; Zhi-Ming Chen; Huo-Gui Su; Liang-De Xiao; Jin-Long Tang; Shun Li; Roy Neilson; et al. (Plant and Soil, 2025)

Anti-inflammatory and antinociceptive effects, toxicity, and phytochemical analysis of Beaumontia grandiflora Wall. - Rui Yang; Dan Teng; Ming-rui Yang; Yi-huan Li; Jian-fen Xiao; Qian-ru Zhang; Hong-ping He; Hua-yi Jiang (Natural Product Research, 2025)

Bigels as novel fat substitutes: fat simulation characteristics, quality regulation, future trends and challenges - Yanlei Gao; Qing Xiong; Qilin Huang; Yang Hu; Ru Liu (Trends in Food Science & Technology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

STING inhibition suppresses butachlor-induced splenic macrophage pyroptosis and M1 polarization via cGAS-STING signaling - Ru-Yang Zhao; Mu-Zi Li; Qi-Qian Wang; Fu-Wei Jiang; Yi Zhao; Jin-Long Li (Journal of Hazardous Materials, 2025)

Cross-view geo-localization with panoramic street-view and VHR satellite imagery in decentrality settings - Panwang Xia; Lei Yu; Yi Wan; Qiong Wu; Peiqi Chen; Liheng Zhong; Yongxiang Yao; Dong Wei; Xinyi Liu; Lixiang Ru; Yingying Zhang; Jiangwei Lao; et al. (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Comparison of hydroxylated flavonoids and their interaction with protein-based carriers - Zhi-Yuan Yang; Shan-Dan Zhao; Yu-Ru Wu; Qian Zhou; Wei Wang; Yi-Bin Zhou; Kang Liu (Food Chemistry, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

Design of 2D/2D Pt SA-MoS2/ZnIn2S4 photocatalysts for boosting hydrogen production - Xue-Lu Chen; Miao Ni; Yan-Ru Li; Yi-An Pan; Chen Chi; Yi Yang; Si-Meng Li; Sudip Biswas; Yi-Bai Sun; Xing-Hua Xia (Chemical Engineering Journal, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Facile blending modification and high-voltage activation strategy enabled long-cycle performance of single crystalline nickel-rich cathode materials - Honglei Liu; Yong Wu; Deli Li; Chengzhi Hu; Lei Zou; Tao Xu; Qiang Wang; Weijian Tang; Dongxu Liu; Ranlin Dong; Ru Song; Zeheng Yang; et al. (Chemical Engineering Journal, 2025)

Hafnium metal-organic frameworks coupling with DNAzyme-driven bipedal DNA walkers as dual-mode aptasensing platform for sensitive detection of ochratoxin A - Zhuangzhuang Ru; Jingui Chen; Luyang Lv; Ning Gao; Xiang Ren; Yu Du; Lei Yang; Qin Wei (Chemical Engineering Journal, 2025)

Overcoming the bottleneck in one-electron reduction of CO2 with mechanical energy-driven triboelectric plasma-enabled catalysis - Qinglong Ru; Bao Zhang; Sumin Li; Jiao Wang; Wei Jiang; Nannan Liu; Hui Hu; Yongcui Yang; Taifeng Liu; Qianhong Gao; Yifei Zhu; Yu Jia; et al. (Chemical Engineering Journal, 2025)

Construction and optimization of low carbon-to-nitrogen ratio-adapted Chlorococcum-Bacteria symbiosis for energy-efficient wastewater remediation - Ru Yan; Han Ji; Zhuo-Chao Liu; Mei-Qi Ren; Shuai Wang; Li-Ming Yang; Dan Cui (Bioresource Technology, 2025)

Human-mediated introductions mitigate climate vulnerability of mangrove species by releasing their ecological potential - Wen-Xun Lu; Wen-Qin Tu; Bing-Huang Zhang; An-Ru Lou; Sheng-Chang Yang (Biological Conservation, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Transcriptome Profiling of the Primary and Crown Root in Response to Nitrate in Foxtail Millet (Setaria italica) - Xueting Kang; Jian-Hong Hao; Jiayi Chen; Xuan Zhou; Dan-Ying Chen; Rui Zhao; Ru Meng; Shuqi Dong; Xiangyang Yuan; Xiaorui Li; Lulu Gao; Guanghui Yang; et al. (Journal of Plant Growth Regulation, 2025)

Microbial life-history strategies mediate temperature effects on organic carbon pools in black soils - Lihui Lyu; Chaoqun Wang; Kunkun Fan; Jiasui Li; Teng Yang; Guifeng Gao; Ru Sun; Jiao Wang; Xiyuan Xu; Yuxiao Zhang; Yuying Ma; Jiabao Zhang; et al. (Soil Ecology Letters, 2025)

Architectural features and antioxidative biofunctionality of a novel pectin from Angelica keiskei Koidz - Si-Ru Chen; Yu-Ru Zhu; Li-Ting He; Hong-Liang Sun; Jing Huang; Yan-Zi Yang; Hua-Jun Zhao; Bo Yang; Meng-Xia Yan (Natural Product Research, 2025)

Oncolytic avian reovirus regulates the TLR3-IRF3-IFN-γ-JAK-STAT1 and TLR3-NF-κB-IFN-γ-JAK-STAT1 pathways inducing autophagy in murine melanoma cells - Chao-Yu Hsu; Zi-Yang Lo; Yi-Ying Wu; Wei-Ru Huang; Tz-Chuen Ju; Kuo-Pin Chuang; Lon-Fye Lye; Muhammad Munir; Hung-Jen Liu (Veterinary Microbiology, 2025)

UGPase: A novel molecule that regulates LPS synthesis, virulence, and immunogenicity of Brucella melitensis - Si Chen; Yuxin Liu; Yang Gao; Dong Zhang; Ru Zhang; Fei Tu; Nan Li; Qingkui Jiang; Linna Liu; Yanling Yang (Veterinary Microbiology, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

The heading stage: A critical period for schwertmannite in reducing arsenic accumulation in rice (Oryza sativa L.) - Yan Dong; Jiawei Yang; Ru Wang; Bo Zhou; Mingjiang Zhang; Guanyu Zheng; Lixiang Zhou (Journal of Environmental Sciences, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Responses of coastal phytoplankton communities to herbicide exposure: enhanced resistance coupled with reduced resilience - Yunsheng Wang; Ziang Zhao; Xiukai Song; Xiangyang Jiang; Jiuqiang Xiong; Shaoguo Ru; Liqiang Yang (Environmental Research, 2025)

Tracing anthropogenic imprints on polybrominated and polychlorinated dibenzo-p-dioxin/furans in soil: A comprehensive field study in an urban agglomeration of China - Ming-Yang Liu; Hui-Ru Li; Ping-An Peng; Ai-Min Song; Yang Li; Fei-Xiang Xie; Yong-Hong Zhang; Jian-Fang Hu (Environmental Research, 2025)

Nepenthes-inspired liquid-infused membranes with capillary-enhanced thermal efficiency anti-scaling, and anti-fouling for direct contact membrane distillation - Rishun Li; Ru Liu; Volker Abetz; Lizhi Zhao; Zhenzhen Zhang; Xiaoniu Yang (Chemical Engineering Journal, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Different responses of phytoplankton taxa to water N and P inputs in a freshwater wetland: A mesocosm study - Wenjing Ma; Jiayin Feng; Jinhua Zhang; Hongpeng Wang; Yunpeng Guo; Yaru Lyu; Chao Wang; Zixuan Yang; Mengyu Yan; Jingyi Ru; Xueli Qiu; Shiqiang Wan (Marine Pollution Bulletin, 2025)

Antiviral prenylated C6–C3 derivatives containing a methylenedioxyl group from the roots of Illicium brevistylum - Jing-Yu Zhang; Qian-Ru Wang; Hui-Lin Yang; Rong-Mei Gao; Mi Li; Jia Yang; Yu-Huan Li; Li Li; Shuang-Gang Ma (Phytochemistry, 2025)

Identification of major fungal diseases in sorghum and screening of broad-spectrum resistance germplasms in Southwest China - Zhi-Fan Yu; Yam Bahadur Kami; Jing-Yang Xia; Xin-Ya Chang; Jin-Yang Li; Jun-Ru Han; Jun Lin; Yuan-Tao Sun; Li-Cheng Wang; Xian-Lin Ni; Wen-Ming Wang; Ji-Wei Zhang (Physiological and Molecular Plant Pathology, 2025)

Phylogenomics provides new insight into the phylogeny and diversification of Asian Lappula (Boraginaceae) - Dan-Hui Liu; Quan-Ru Liu; Komiljon Sh. Tojibaev; Alexander P. Sukhorukov; Hafiz Muhammad Wariss; Yue Zhao; Lei Yang; Wen-Jun Li (Molecular Phylogenetics and Evolution, 2025)

Constructing asymmetric D′-A-D" imine covalent organic frameworks to optimize exciton effect and enhance photocatalytic reduction of U(VI) - Yang-Xing He; Xiao-Juan Chen; Rui Zhang; Hao-Xuan He; Cheng-Peng Niu; Cheng-Rong Zhang; Zhi-Hai Peng; Yuan-Jun Cai; Zhen-Wen Zhang; Ru-Ping Liang; Jian-Ding Qiu (Journal of Hazardous Materials, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Explore the synergistic effects of Lactobacillus plantarum fermentation and tea polyphenols on the deodorization of egg white powder from the perspective of protein site competition - Ru-yi Zhang; Yan-jun Yang; Wei-jian Zhang; Jun-hua Li; Yu-jie Su; Lu-ping Gu; Cui-hua Chang (Food Chemistry, 2025)

Designing fish scale gelatin microgel network by moderate pre-dispersion: A new attempt to construct a bigels-based pig fat analog - Yanlei Gao; Qing Xiong; Ruonan Li; Huixian Yang; Ru Liu (Food Hydrocolloids, 2025)

Unveiling a new hemocyte subpopulation in white shrimp (Penaeus vannamei) and the characterization of immune response in hemocyte subpopulation - Novi Rosmala Dewi; Ari Widodo; Muhammad Ar Rozzaaq Nugraha; Min-Da Yang; Ta-Jeng Yang; Yu-Ru Lin; Yeh-Fang Hu (Fish & Shellfish Immunology, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Fluorinated Amino-acid-doped microarray-based biochemical patches Deciphers in-situ spatiotemporal dynamics amidst intricate Bio-Interfaces - Ru Zhang; Ran Duan; Deqi Yang; Haofan Wu; Bingfang Wang; Zhiqiang Chang; Jing Chen; Jing Dai; Yingying Lv; Yi Liu; Menahem Y. Rotenberg; Dandan Liang; et al. (Chemical Engineering Journal, 2025)

Glutaminolysis and α-ketoglutarate-stimulated KCa3.1 expression contribute to β-adrenoceptor activation-induced myocardial fibrosis in mice - Ru-Yue Bai; Lin-Hong Wu; Yan Wang; Chen Guo; Gang She; Zheng-Da Pang; Jing-Jing Li; Xin-Yi Zhao; Meng-Zhuan Han; Xia-Xia Hai; Yi-Yi Yang; Yi Zhang; et al. (Science China Life Sciences, 2025)

Experimental evidence for viral impact on microbial community, nitrification, and denitrification in an agriculture soil - Hu Li; Sha Zhao; Meng-Ke Gao; Yanyan Zhou; Bo Xu; Le-Yang Yang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2025)

Advancements in emerging non-thermal preservation techniques for aquatic products: A comprehensive review of mechanisms, applications, and future directions - Zhijun Yang; Qing Xiong; Tao Yin; Juan You; Shanbai Xiong; Ru Liu (Innovative Food Science & Emerging Technologies, 2025)

Structural evaluation and formation regularities of garlic clove-like meat in prefabricated grass carp - Qin Yang; Junhong Xie; Yuting Zhang; Yiling Tian; Liang Song; Yongqiang Zhao; Jian Xiong; Ru Liu; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2025)

Co-encapsulation and stability evaluation of myricetin and epicatechin in the oxidized starch-coated edible dock protein hydrogels - Si-Qi Li; Zhi-Yuan Yang; Ming Yang; Wei Wang; Yu-Ru Wu; Yi-Bin Zhou; Kang Liu (Food Hydrocolloids, 2025)

High-performance multi-particle color electrophoretic display: A novel dual-charged particle strategy - Yue Zhang; Debo Zeng; Junjie He; Hailiang Sheng; Tao Zhou; Jintao Shi; Lisha Peng; Xinzao Wu; Bo-Ru Yang (Chemical Engineering Journal, 2025)

Efficient catalyst-free CO2 reduction by CO2— radical anions at gas–liquid interface under ambient conditions - Nannan Liu; Qinglong Ru; Wei Jiang; Hui Hu; Yongcui Yang; Kailan Ma; Zuliang Du; Yu Jia; Xiaojing Yang; Bao Zhang; Gang Cheng (Chemical Engineering Journal, 2025)

Chemical constituents from the aerial parts of Clematis peterae - Pan-Pan Yu; Meng-Ya Chen; Ya-Ru Wu; Yong-Qi Guo; Ying-Zhen Tang; Zi-Han Zhu; Yang-Yang Ma; Shi-Hui Qian; Nan Yao; Zhen-Lin Li (Biochemical Systematics and Ecology, 2025)

Asymbiotic Nitrogen Fixation in the Phyllosphere of Urban Green Spaces - Jian-Feng Li; Le-Yang Yang; Zhao Zhang; Xin-Rong Huang; Hu Li; Shun Li; Xiao-Ru Yang (Current Microbiology, 2025)

Daily Evolution of Three-Dimensional Structure of a Subsurface Anticyclonic Eddy and Eddy-Induced Swirl Transport in the Canada Basin - Fan Xu; Haiyan Li; Ru Wang; Zhiqiang Wen; Kun Yang; Menghao Zhang (Journal of Ocean University of China, 2025)

Analysis of Wind–Wave Relationship in Taiwan Waters - Kai-Ho Cheng; Chih-Hsun Chang; Yi-Chung Yang; Yu-Hao Tseng; Chung-Ru Ho; Tai-Wen Hsu; Dong-Jiing Doong (Journal of Marine Science and Engineering, 2025)
The relationship between wind and waves has been extensively studied over time. However, understanding the local wind and wave relationship remains crucial for advancing renewable energy development and optimizing ocean management strategies. This study used wind and wave data collected by the ten weather buoys in the waters surrounding Taiwan to analyze regional sea states. The relationship between wind speed and significant wave height (SWH) was examined using regression analysis. Additionally, machine learning techniques were employed to assess the relative importance of features contributing to SWH growth. The regression analysis revealed that SWH in the waters surrounding Taiwan was not fully developed, with notable discrepancies observed between the waters east and west of Taiwan. According to the power law formula describing the relationship between wind speed and SWH, the eastern waters exhibited a larger prefactor coupled with a smaller scaling exponent, while the western waters manifested a converse parametric configuration. Through an evaluation of four machine learning algorithms, it was determined that wind speed is the most influential factor driving these regional differences, especially in the waters west of Taiwan. Beyond wind speed, air pressure or temperature emerged as the secondary feature factor governing wind–wave interactions in the waters east of Taiwan.

How do different ant species mediate CH4 fluxes in slash-burn tropical forest soils? - Lingling Xie; Shaojun Wang; Mei Lu; Bo Xiao; Zhengjun Wang; Zhipeng Guo; Xiaofei Guo; Shuang Luo; Ru Li; Jiahui Xia; Shengqiu Yang; Mengjie Lan (Soil and Tillage Research, 2025)

Functional analysis of Ophraella communa Lesage OcomOBP11 in recognition of Ambrosia artemisiifolia L. volatiles - Yang Yue; Chao Ma; Yan Zhang; Wei-hua Ma; Jing-jing Wang; Zhen-ya Tian; Guang-mei Chen; Ru-wen Li; Jin-hua Li; Jing-fang Yang; Zhong-shi Zhou (Pesticide Biochemistry and Physiology, 2025)

Calculation and analysis of wave loads and hydrodynamic coefficients on submerged floating tunnels with various cross-sections - Hong-Fei Mao; Wei-Jiang Zheng; Qin-Ru Yang; Zhong-Bing Zhou; Zheng-Lin Tian; Long Han; Guang-Lin Wu; Jin-Bo Lin (Ocean Engineering, 2025)

Mathematical modelling the variation of sodium chloride (NaCl) diffusion behavior and quality of grass carp fillets during salting - Kun Yang; Runlin Wu; Ramy M. Khoder; Shanbai Xiong; Ru Liu (Journal of Food Engineering, 2025)

Recent progress in protein-based high internal-phase Pickering emulsions: Composition, stabilization, applications, and future trends - Wei Liang; Xiaofeng Zhan; Pengkai Wang; Chuan Li; Lu Zhang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Research International, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Effects of proteolysis pretreatment on the formation, structural changes and emulsifying properties of rice glutelin amyloid-like fibrils - Yi-Xuan Jiang; Ya-Ru Wang; Qin Yang; Xiao-Hong Yu; Han-Qing Chen (Food Chemistry, 2025)

Impact of typhoon on nutrient contaminants, antibiotic resistance genes and microbial communities in mariculture tailwater treatment system - Jun-Ru Zhao; Xing Li; Yan-Ling Yang; Xiao-Yan Fan (Environmental Research, 2025)

Role of earthworms and their excretion products in reducing antimicrobial resistance and putative pathogens during vermicomposting - Ning Liu; David W. Graham; Yi Zhao; Xiao-Ru Yang; Gang Li; Yong-Guan Zhu (Chemical Engineering Journal, 2025)

Corrigendum: Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Repeated measurements of urinary bisphenol A and its analogues in relation to sperm DNA damage - Yang-Juan Li; A-Xue Liu; Jia-Yue Zeng; Yu Miao; Min Zhang; Xiao-Ying Liu; Wu Yang; Ru-Cheng Li; Jin-Qin Zhu; Chang-Jiang Liu; Qiang Zeng (Journal of Hazardous Materials, 2025)

Preparation of two-step cold-set low oleogel-microgels phase bigels and its application in tender fish balls: Pork fat substitute and cryoprotectant - Yanlei Gao; Qing Xiong; Qilin Huang; Yang Hu; Ru Liu (Food Research International, 2025)

Generation characteristics of polybrominated and polychlorinated dibenzo-p-dioxins/furans (PBDD/Fs and PCDD/Fs) under varying incineration conditions of municipal solid waste - Ming-Yang Liu; Ai-Min Song; Hui-Ru Li; Sheng-Tao Ma; Ren-Jie Shang; Yao Xiao; Ping-An Peng; Jian-Fang Hu (Environmental Pollution, 2025)

Engineered zwitterionic hydrogel with extreme environment resilience: High ionic conductivity, subzero tolerance, and potential for multimodal sensing and optical applications across devices - Yan-Na Lu; Kai Mo; Mingwei Gu; Jia-Sen Xie; Ying Yang; Lin Zheng; Xiang-Ru Liu; Yunjie Lu; Jun-Shuai Chen; Jin Ge (Chemical Engineering Journal, 2025)

Endophytes and soil microorganisms participate in the germination of Sinojackia xylocarpa Hu by degrading the pericarp - Zi-Hao Li; Xin-Yi Ma; Huan Yang; Run-Guo Zang; Jia-Ru Li (Acta Physiologiae Plantarum, 2025)

Sediment Provenance and Facies Analysis of the Huagang Formation in the Y-Area of the Central Anticlinal Zone, Xihu Sag, East China Sea - Xiao Ma; Wei Yan; Yi Yang; Ru Sun; Yue Chao; Guoqing Zhang; Chao Yang; Shudi Zhang; Dapeng Su; Guangxue Zhang; Hong Xu (Journal of Marine Science and Engineering, 2025)
Recent breakthrough exploration wells in the Huagang Formation in the Y-area of the central anticlinal zone of the Xihu Sag have confirmed the significant exploration potential of structure–lithology complex hydrocarbon reservoirs. However, limited understanding of the provenance system, sedimentary facies, and microfacies has hindered further progress in complex hydrocarbon exploration. Analysis of high-precision stratigraphic sequences and seismic facies data, mudstone core color, grain-size probability cumulative curves, core facies, well logging facies, lithic type, the heavy-mineral ZTR index, and conglomerate combinations in drilling sands reveals characteristics of the source sink system and provenance direction. The Huagang Formation in the Y-area represents an overall continental fluvial delta sedimentary system that evolved from a braided river delta front deposit into a meandering river channel large-scale river deposit. The results indicate that the primary provenance of the Huagang Formation in the Y-area of the Xihu Sag is the long-axis provenance of the Hupi Reef bulge in the northeast, with supplementary input from the short-axis provenance of the western reef bulge. Geochemical analysis of wells F1, F3, and G in the study area suggests that the prevailing sedimentary environment during the period under investigation was characterized by anoxic conditions in nearshore shallow waters. This confirms previous research indicating strong tectonic reversal in the northeast and a small thickness of the central sand body unrelated to the flank slope provenance system. The aforementioned findings deviate from conventional understanding and will serve as a valuable point of reference for future breakthroughs in exploration.

Photoelectrocatalytic Coupling of Chlorine Radicals Enhances Sulfonamide Antibiotic Degradation in Saline-Alkaline Waters in Cold-Water Fish Aquaculture - Qikai Liu; Yang Liu; Yaqi Mao; Ru Li; Yujie Jiao; Jiali Lei; Fenzhen Zhang (Fishes, 2025)
The degradation of organic matter using TiO2 nanotube photocatalytic technology is limited by the short lifetime and diffusion radius of the generated hydroxyl radicals, decreasing the removal efficiency. This study developed a chlorine radical-coupled photoelectrocatalytic system, significantly enhancing the performance of TiO2 nanotube arrays in removing sulfonamide antibiotics (SAs) from cold-water aquaculture systems. The highest degradation rates were observed at 5 mM NaCl and 15 mM NaNO3. When SA concentrations were 0.1–10 mg/L, degradation efficiency decreased with higher initial concentrations. The best degradation was achieved at an initial pH of 3 for SA. Humic acid and sodium acetate, natural organic matter in the water column, served as low-concentration promoters and high-concentration inhibitors. In our study, three degradation intermediates were identified, and hydrolysis and nitration reactions are proposed as the primary pathways for SA degradation. We confirmed that oxygen radicals play a major role in this system. Furthermore, toxicology experiments revealed the weakening of the toxicity of the degraded products. This study provides an efficient method for treating organic matter in cold-water fish culture water in chloride-containing saline and alkaline waters.

Location optimization of unmanned aerial vehicle (UAV) drone port for coastal zone management: The case of Guangdong coastal zone in China - Jia Sun; Sijing Shu; Hongda Hu; Yingbin Deng; Zhao Li; Shengnan Zhou; Yue Liu; Minwen Dang; Wumeng Huang; Zhiwei Hou; Xiaoling Yin; Ru Zhang; et al. (Ocean & Coastal Management, 2025)

Seasonal variation of diurnal rainfall characteristics over Vietnam - Wan-Ru Huang; Hai Bui-Manh; Tzu-Yang Chiang; Suranjith Bandara Koralegedara (Science of The Total Environment, 2025)

Urinary biomarkers of drinking water disinfection byproducts in relation to blood-based liver function parameters among reproductive-aged Chinese women - Ping-Ping Gui; Yan-Ling Deng; Min Zhang; Yu Miao; Peng-Hui Liu; Jia-Yue Zeng; Yang Wu; Cheng-Ru Li; Xiao-Ying Liu; Yang-Juan Li; Jin-Qin Zhu; A-Xue Liu; et al. (Science of The Total Environment, 2025)

The Arabidopsis heterotrimeric G protein α subunit binds to and inhibits the inward rectifying potassium channel KAT1 - Jiang-Fan Guo; Hui Zhou; Zhuo-Ran Hu; Ya-Lan Yang; Wen-Bin Wang; Yan-Ru Zhang; Xue Li; Nuerkaimaier Mulati; Ying-Xin Li; Lu Wu; Yu Long; Jun-Min He (Plant Science, 2025)

A dual-functional vertical oriented C/TiO2 nanotubes for superior solar evaporation of sewage treatment - Lifen Su; Haoming Xie; Xiaoyu Liu; Bin Yang; Jibin Miao; Ru Xia; Jiasheng Qian; Lei Miao (Journal of Water Process Engineering, 2025)

Efficient fluconazole degradation by activating peroxymonosulfate with LDH-coated nickel foam: Synergism of radical and non-radical pathways - Xiang-Yang Li; Ling-Xi Zhao; Meng Xie; Ning Liu; Xiang-Feng Chen; Ru-Song Zhao (Journal of Water Process Engineering, 2025)

Performances and mechanisms of granular activated carbon enhancing n-caproate production via chain elongation - Ru Zhang; Wei Fang; Qingyan Wang; Ziyi Fang; Jinsong Liang; Le Chen; Jianning Chang; Yajie Zhang; Wenjing Yang; Panyue Zhang; Guangming Zhang (Journal of Environmental Management, 2025)

Mechanism of enhanced quality of Acetes chinensis powder-Alaska Pollock surimi: Gel properties, rheological properties, micro-structure - Qianqian Li; Jiehui Feng; Ru Jia; Huamao Wei; Tao Huang; Jinjie Zhang; Dalun Xu; Wenge Yang; Gaoshang Li (Food Research International, 2025)

Molecular networking and Paterno-Büchi reaction guided glycerides characterization and antioxidant activity assessment of Ganoderma lucidum spore oil - Qing-Xuan Ren; Rui Wang; Qin-Ru Mu; Ling Chen; Min Chen; Li-Jiang Wang; Ping Li; Hua Yang; Wen Gao (Food Chemistry, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Dissimilatory nitrate reduction to ammonium driven by different electron donors: Mechanisms, recent advances, and future perspectives - Wan-Ru Wen; Tian-Chen Liu; Sheng-Qiang Fan; Xin Tan; Yang Lu; De-Feng Xing; Bing-Feng Liu; Nan-Qi Ren; Guo-Jun Xie (Chemical Engineering Journal, 2025)

Modeling Li isotope fractionation during the coal-combustion process and evaluating its capacity as an environmental tracer - Jing Chen; Yilin Xiao; Jack Geary Murphy; Dong-Bo Tan; Yang-Yang Wang; Biao Fu; Guijian Liu; Ru-Wei Wang; Xiaoxia Wang; Feng-Tai Tong (Chemical Geology, 2025)

Drug–drug interaction of phenytoin sodium and methylprednisolone on voriconazole: a population pharmacokinetic model in children with thalassemia undergoing allogeneic hematopoietic stem cell transplantation - Yun Wu; Lu-lu Niu; Ya-yun Ling; Si-ru Zhou; Tian-min Huang; Jian-ying Qi; Dong-ni Wu; Rong-da Cai; Ting-qing Wu; Yang Xiao; Taotao Liu (European Journal of Clinical Pharmacology, 2025)

Two new phenolic glycosides from the rhizomes of Paris yunnanensis - Yu-Rui Xie; Shan-Shan Ling; Yan-Xi Li; Mei-Ru Wang; Hai-Yang Liu (Phytochemistry Letters, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Insights into the source characterization, risk assessment and ozone formation sensitivity of ambient VOCs at an urban site in the Fenwei Plain, China - Huan Zhang; Chen Zhang; Shasha Liu; Shijie Yin; Siqing Zhang; Hongji Zhu; Fengyu Yan; Hua Yang; Xiaoning Ru; Xingang Liu (Journal of Hazardous Materials, 2025)

Equilibrium boron isotope fractionation during kaolinite adsorption and applications to chemical weathering processes - Yin-Chuan Li; Ya-Ru Zhou; Hai-Zhen Wei; Martin R. Palmer; Fa-Yang Guo; Yong-Hui Li; Yong-An Qi; Da-Ping Xia (Geochimica et Cosmochimica Acta, 2025)

Insight into the mechanism of setting temperature and time on gel properties of Solenocera crassicornis surimi - Jiafang Lu; Jingjing Tong; Dalun Xu; Huamao Wei; Tao Huang; Wenge Yang; Ru Jia (Food Research International, 2025)

A strategy for the quality control in Polyrhachis dives: Identification and quantification of specific peptides using untargeted and targeted mass spectrometry approaches - Xialin Chen; Dandan Li; Rongrong He; Jiajia Wang; Ru Yang; Mengyu Qian; Liang Cao; Yongwen Zhang; Zhenzhong Wang; Wei Xiao (Food Research International, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Polysaccharide modified fish gelatin intelligent hydrogels for reliable monitoring freshness of shrimp (Litopenaeus vannamei) - Qingfang Ying; Shengnan Zhan; Qiuyu Lu; Wenge Yang; Ru Jia; Gaoshang Li; Tao Huang (Food Hydrocolloids, 2025)

One-step open-ring strategy for constructing sandwich-like metal–organic framework with highly selective removal of thorium - Meng-Jie Yang; An-Min Song; Qing Yang; Zhi Wu; Bin Lin; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Efficient adsorption and separation of glyphosate in aqueous solution by amino-functionalized Poly(glycidyl methacrylate) - Qiyu Meng; Yupei Wang; Meng Rong; Huifang Xing; Ru-An Chi; Congmei Chen; Huizhou Liu; Liangrong Yang (Chemical Engineering Journal, 2025)

Impact of carbon/nitrogen ratio on sequencing batch biofilm reactors initiated with different seed sludges for treating actual mariculture effluents - Xiao-Yan Fan; Shi-Long Zhou; Yanling Yang; Shen-Bin Cao; Yue Niu; Meng-Yuan Zheng; Jun-Ru Zhao (Bioresource Technology, 2025)

Data imbalance causes underestimation of high ozone pollution in machine learning models: A weighted support vector regression solution - Ling Zhen; Baihua Chen; Lin Wang; Lin Yang; Wei Xu; Ru-Jin Huang (Atmospheric Environment, 2025)

Environmentally-Relevant Concentrations of Atrazine Had Minor Impacts on Gut Microbiota and Liver Metabolite in Juvenile Turtles - Huo-Bin Tang; Xin-Ru Qian; Wan-Qiu Yang; Jia-Meng Yang; Jin-Hui Zhang; Hong-Liang Lu (Archives of Environmental Contamination and Toxicology, 2025)

Evaluation on the antibacterial activity of glycyrrhizin against Pseudomonas plecoglossicida in ayu fish (Plecoglossus altivelis) - Fan Tao; Jia-Feng Cao; Yan-Jun Liu; Ru-Yi Chen; Jin-Jin Shi; Chang-Yun Li; Jian-Fei Lu; Guan-Jun Yang; Jiong Chen (Aquaculture, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Recycled fish oil and lard: Influences on the textural and structural properties of Surimi Gels - Jingyan Zhang; Ramy M. Khoder; Hong Yang; Tao Yin; Ru Liu; Juan You (Food Structure, 2025)

Carboxymethyl chitosan-assisted formation of stable soy protein isolate emulsions and their impact on the properties of squid (Dosidicus gigas) surimi gel - Siqi Liu; Zhufen Wang; Wenge Yang; Tao Huang; Jie-Ting Geng; Huamao Wei; Yuanpei Gao; Ru Jia (Food Hydrocolloids, 2025)

Quantitative estimation of three-dimensional fracture density: Insights from the stereological relationship between borehole and universal elliptical DFN - Kun Xiao; Ru Zhang; Li Ren; Anlin Zhang; Jing Xie; Ziwen Luo; Zetian Zhang; Chendi Lou; Zeqian Yang (Engineering Geology, 2025)

Leveraging Bio-Waste onion skin for High-Performance triboelectric nanogenerators - Po-Yen Chang; Ting-Ying Huang; Chien-Hung Yang; Chia-Hsien Lee; Ru-Jong Jeng; Chih-Ping Chen; Meng-Fang Lin (Chemical Engineering Journal, 2025)

Effects of imidacloprid on Orius similis: assessing growth, development, and reproduction through age-stage two-sex life table analysis under contact and stomach toxicity treatments - Bo Zhang; Yi-Ru Li; Jin-Long Zhang; Guo-Hua Chen; Nian Yang; Ji-Huan Liu; Guo-Ting Yuan; Xiao-Ming Zhang (Journal of Pest Science, 2025)

Design and experimental analysis of real-time detection system for The seeding accuracy of rice pneumatic seed metering device based on the improved YOLOv5n - He Xing; Yikai Wan; Peng Zhong; Junjiang Lin; Mingtao Huang; Ru Yang; Ying Zang (Computers and Electronics in Agriculture, 2024)

A comprehensive unraveling of the mystery of reduced-salt surimi gels: From molecular mechanism to future prospects - Qiqi Li; Shengjun Chen; Juan You; Yang Hu; Tao Yin; Ru Liu (Trends in Food Science & Technology, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Promotion of antibiotic-resistant genes dissemination by the micro/nanoplastics in the gut of snail Achatina fulica - Yan-Mei Da; Xiao-Ru Yang; Ming-Jun Li; Shun-Shun Li; Ze-Ping Gao; Ying Zhang; Jian-Qiang Su; Guo-Wei Zhou (Science of The Total Environment, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Discovery of a polyurethane-degrading enzyme from the gut bacterium of plastic-eating mealworms - Jiakang Ru; Xuan Chen; Xuena Dong; Lin Hu; Jianli Zhang; Yu Yang (Journal of Hazardous Materials, 2024)

Ovalbumin/sodium alginate Pickering emulsion: Structural characteristics and its contribution to enhancing the gel properties of Hairtail (Trichiurus haumela) surimi - Zhufen Wang; Siqi Liu; Wenge Yang; Jie-Ting Geng; Tao Huang; Huamao Wei; Zhaohui Qiao; Ru Jia (Food Chemistry, 2024)

The impact of the addition of vitamin C, NaCl, clove oil on the muscle of live blunt-snout bream during transportation - Yu Chen; Ramy M. Khoder; Jun Mei; Hong Yang; Qilin Huang; Juan You; Tao Yin; Ru Liu (Food Bioscience, 2024)

Evaluating the multi-seasonal impacts of urban blue-green space combination models on cooling and carbon-saving capacities - Fei Yang; Dongdong Yang; Ying Zhang; Ru Guo; Jiaying Li; Hongcheng Wang (Building and Environment, 2024)

Effect of Bacillus subtilis Supplemented Diet on Broiler’s Intestinal Microbiota and TLRs Gene Expression - Salman Khan; Anam Khalid; Ru Yang; Fatima Khalid; Muhammad Hamza Zahid; Haozhe Liu; Yunhua Zhang; Zaigui Wang (Probiotics and Antimicrobial Proteins, 2024)

Post translational modifications of connexin 43 in ventricular arrhythmias after myocardial infarction - Fan Yang; Xiao-Lu Zhang; Huan-Huan Liu; Ling-Ling Qian; Ru-Xing Wang (Molecular Biology Reports, 2024)

TP53 to mediate immune escape in tumor microenvironment: an overview of the research progress - Kai-li Zhu; Fei Su; Jing-ru Yang; Ruo-wen Xiao; Rui-yue Wu; Meng-yue Cao; Xiao-ling Ling; Tao Zhang (Molecular Biology Reports, 2024)
Increasing evidence suggests that key cancer-causing driver genes continue to exert a sustained influence on the tumor microenvironment (TME), highlighting the importance of immunotherapeutic targeting of gene mutations in governing tumor progression. TP53 is a prominent tumor suppressor that encodes the p53 protein, which controls the initiation and progression of different tumor types. Wild-type p53 maintains cell homeostasis and genomic instability through complex pathways, and mutant p53 (Mut p53) promotes tumor occurrence and development by regulating the TME. To date, it has been wildly considered that TP53 is able to mediate tumor immune escape. Herein, we summarized the relationship between TP53 gene and tumors, discussed the mechanism of Mut p53 mediated tumor immune escape, and summarized the progress of applying p53 protein in immunotherapy. This study will provide a basic basis for further exploration of therapeutic strategies targeting p53 protein.

MiR-3571 modulates traumatic brain injury by regulating the PI3K/AKT signaling pathway via Fbxo31 - Yang Zhang; Zongying He; Qiongfang Hu; Huali Liu; Rongai Wen; Na Ru; Jinghua Yu; Shaokun Lv; Rui Tao (Cell Biochemistry and Biophysics, 2024)

Effect of Sodium Alginate and Calcium Chloride on the Physicochemical Characteristics of Shrimp (Penaeus Vannamei) Surimi Gels - Ziyan Wang; Jiehui Feng; Qianqian Li; Ru Jia; Tao Huang; Huamao Wei; Wenge Yang (Journal of Ocean University of China, 2024)

Reproduction induces variation of digestive function in the sea cucumber Apostichopus japonicus - Xiaoshang Ru; Beini Deng; Libin Zhang; Hongsheng Yang (Aquaculture International, 2024)

Devosia lacusdianchii sp. nov., an attached bacterium inhibited by metabolites from its symbiotic Microcystis - Qing-Lin Deng; Yao Xiao; Ru Jia; Xin Xie; Le Wang; Xin Wang; Jian-Yuan Yang; Qi-Gen Guo; Bing-Huo Zhang (Antonie van Leeuwenhoek, 2024)

Effects of Hydroxypropyl Distarch Phosphate on Surimi Gel Properties Under ’Setting–Freezing–Reheating’ Procedure During Frozen Storage - Shutong Zhang; Min Mao; Xinxin Zhang; Zhufen Wang; Siqi Liu; Yuanpei Gao; Wenge Yang; Ru Jia (Journal of Aquatic Food Product Technology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

A novel strategy for waste activated sludge treatment: Recovery of structural extracellular polymeric substances and fermentative production of volatile fatty acids - Wei Fang; Ru Zhang; Wenjing Yang; Henri Spanjers; Panyue Zhang (Water Research, 2024)

Revisiting the impact of temperature on ground-level ozone: A causal inference approach - Baihua Chen; Ling Zhen; Lin Wang; Haobin Zhong; Chunshui Lin; Lin Yang; Wei Xu; Ru-Jin Huang (Science of The Total Environment, 2024)

Response of anammox to organics with different degradation characteristics and exposure time: Performance, sludge characteristics and bacterial community - Shuai Zhang; Long-Yun Lai; Tian-Xiang Wang; Wei-Lei Jin; Ru-Ru Yi; Dong-Zhi Chen; Ren-cun Jin; Guang-feng Yang (Science of The Total Environment, 2024)

Responses of coastal phytoplankton communities to seasonal herbicide inputs: Tolerance or degeneration? - Yunsheng Wang; Ying Chen; Fuwei Zhang; Lingxiao Li; Shaoguo Ru; Liqiang Yang (Journal of Hazardous Materials, 2024)

Proteomic analysis revealed the deterioration of surimi gelling capability to fish stress during transportation - Zhiying Xiang; Tao Yin; Zenan Huang; Ziaur Rahman; Yongsawatdigul Jirawat; Tanye Xu; Qilin Huang; Juan You; Ru Liu; Hong Yang (Food Research International, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Heterogeneous degradation kinetics of typical pyrimidine pesticides toward OH radicals - Ru Chen; Dandan Chen; Qiang Niu; Lu Fan; Mingchao Sun; Zhengzheng Yang; Changgeng Liu (Atmospheric Environment, 2024)

Assessing the role of urban green infrastructure in mitigating summertime Urban Heat Island (UHI) effect in metropolitan Shanghai, China - Hao Zhang; Meng-yuan Kang; Zhen-ru Guan; Rui Zhou; Ai-lian Zhao; Wen-jia Wu; Hao-rong Yang (Sustainable Cities and Society, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

ESR chronology of the Quaternary sedimentary sequence of the Shinaimiao borehole in Hebi City, Henan Province, China - Hao Ji; Zhong-shan Shen; Chun-Ru Liu; Xiong-Nan Huang; Xiao-Ping Yang; Chuan-Yi Wei; Xin-Xiu Li; Qing Zhou; Gong-Ming Yin (Quaternary Geochronology, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Development of easy-to-swallow and lipid-enhanced 3D printed surimi based on high internal phase emulsions - Wei Liang; Yuhang Wang; Chuan Li; Pengkai Wang; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Bond performance and constitutive model of steel bar in G-UHPC under cyclic loading - Ting Yang; Shenchun Xu; Pengcheng Yuan; Dayang Wang; Ru Liao; Yekai Yang; Ruizhe Shao; Chengqing Wu (Engineering Structures, 2024)

Bi2O3/Bi@CSs achieved by shock-type heating for fast and long-lasting sodium ion battery - Ya Ru Pei; Xue Jing Yang; Wu Bin Wan; Hai Ming Huang; Chun Cheng Yang; Qing Jiang (Chemical Engineering Journal, 2024)

Enhancing osseointegration and angiogenesis of Titanium implants through KMnO4-Modified Montmorillonite nano-clay coating - Lifeng Xiong; Binwei Dai; Baodi Yin; Kendrick Hii Ru Yie; Haobo Sun; Yang Liu; Zheyuan Liu; Ahmed S. Mahany; Huan Cheng; Lihua Xu; Peng Gao; Lei Lu; et al. (Chemical Engineering Journal, 2024)

Lowering Schottky barrier in MoC-based cocatalyst via heteroatoms tunning for enhanced photocatalytic hydrogen evolution - Ru-zhou Miao; Yu-long Bao; Guang Yang; Ying-jie Sun; Xiao-jing Wang; Jun Zhao; Hui-ying Mu; Fa-tang Li (Chemical Engineering Journal, 2024)

High-transmittance, fast-response, colored smart windows based on lateral-driving electrophoretic display - Yue Zhang; Jinglan Yang; Feng Xiong; Debo Zeng; Tao Zhou; Jintao Shi; Bo-Ru Yang (Chemical Engineering Journal, 2024)

Identification and fine mapping of a QTL-rich region for yield- and quality-related traits on chromosome 4BS in common wheat (Triticum aestivum L.) - Jinghui Li; Huanhuan Zhao; Minghu Zhang; Chan Bi; Xiaoyuan Yang; Xintian Shi; Chaojie Xie; Baoyun Li; Guangbin Ma; Zhengang Ru; Tiezhu Hu; Mingshan You (Theoretical and Applied Genetics, 2024)

Protective effects of nordalbergin against LPS-induced endotoxemia through inhibiting MAPK/NF-κB signaling pathway, NLRP3 inflammasome activation, and ROS production - Pin-Rong Chen; Chia-Yang Li; Taha Yazal; I-Chen Chen; Po-Len Liu; Yi-Ting Chen; Ching-Chih Liu; Jung Lo; Tzu-Chieh Lin; Ching-Tang Chang; Hsin-En Wu; Yuan-Ru Chen; et al. (Inflammation Research, 2024)

Long-term exposure to prometryn damages the visual system and changes color preference of female zebrafish (Danio rerio) - Shuhui Wei; Yixin Yang; Yao Zong; Yang Yang; Meiping Guo; Zhenzhong Zhang; Rui Zhang; Shaoguo Ru; Xiaona Zhang (Chemosphere, 2024)

Synthesis and application of gelatin-based controlled-release antibacterial films containing oregano essential oil/β-cyclodextrin microcapsules for chilling preservation of grass carp fillets - Tianhao Ying; Chenghong Jiang; Sadia Munir; Ru Liu; Tao Yin; Juan You; Jianhua Rong; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

High yield, good eating quality, and high N use efficiency for medium hybrid indica rice: From the perspective of balanced source-sink relationships at heading - Haibing He; Chao Hu; Haochong Xu; Ru Yang; Cuicui You; Jian Ke; Qiangqiang Zhang; Liquan Wu (European Journal of Agronomy, 2024)

Development and efficacy evaluation of nanoliposomes targeting CAFs-LCSCs communication for hepatocellular carcinoma treatment - Liang Kong; Yang Yu; Ru Yang; Rui-bo Guo; Lu Zhang; Jia-hua Wang; Yang Liu; Juan Zang; Chen Yang; Hui-yue Yang; Rui-jun Ju; Xue-tao Li (Chemical Engineering Journal, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

Targeted liposomes for macrophages-mediated pulmonary fibrosis therapy - Yujie Wang; Fang Zhao; Xiangyu Wang; Haojie Zuo; Yiming Ru; Xi Cao; Yang Wang (Drug Delivery and Translational Research, 2024)

Performance evaluation of vegetation concrete with carbonaceous mudstone aggregates in slope protection under wet-dry conditions - Ling Zeng; Jin-Tao Luo; Zi-Ru Yang; Hui-Cong Yu; Wei Wen; Qian-Feng Gao; Hong-Ri Zhang (Bulletin of Engineering Geology and the Environment, 2024)

Assessing spatial heterogeneity of nutrient loads in a large shallow lake using a lattice Boltzmann water quality model - Haifei Liu; Chuqi Zhang; Wei Yang; Zhiming Ru; Jiewei Ding; Yuetong Jing; Cheng Li (Journal of Environmental Management, 2024)

Study on factors influencing carbon dioxide emissions and carbon peak heterogenous pathways in Chinese provinces - Runpu Liu; Yan Ru Fang; Shuan Peng; Nihed Benani; Xuefang Wu; Yushuo Chen; Tao Wang; Qimin Chai; Pingjian Yang (Journal of Environmental Management, 2024)

Effect of heating treatment on processing characteristics of rice dough - Wan-ru Liu; Chun-min Ma; Yang Yang; Bing Wang; Xiao-fei Liu; Yan Wang; Xin Bian; Xiao-xue Guo; Guang Zhang; Na Zhang (Innovative Food Science & Emerging Technologies, 2024)

Digestion and absorption characteristics of iron-chelating silver carp scale collagen peptide and insights into their chelation mechanism - Qiannan Zhao; Wei Liang; Zhe Xiong; Chuan Li; Lu Zhang; Jianhua Rong; Shanbai Xiong; Ru Liu; Juan You; Tao Yin; Yang Hu (Food Research International, 2024)

Effect of guar gum, gelatin, and pectin on moisture changes in freeze-dried restructured strawberry blocks - Jiaqi Hu; Xiyun Sun; Hongwei Xiao; Chunju Liu; Feifei Yang; Wuyi Liu; Yulong Wu; Yaoyao Wang; Ru Zhao; Haiou Wang (Food Chemistry, 2024)

MGAtt-LSTM: A multi-scale spatial correlation prediction model of PM2.5 concentration based on multi-graph attention - Bo Zhang; Weihong Chen; Mao-Zhen Li; Xiaoyang Guo; Zhonghua Zheng; Ru Yang (Environmental Modelling & Software, 2024)

Bud shapes dictate tiller–rhizome transition in African perennial rice (Oryza longistaminata) - Kai Wang; Yufei Lu; Suwen Jing; Ru Yang; Xianjie Xu; Yourong Fan; Jiangyi Yang (Theoretical and Applied Genetics, 2024)

The role and mechanism of heme oxygenase-1 in arrhythmias - Huan-Huan Liu; Lei Zhang; Fan Yang; Ling-Ling Qian; Ru-Xing Wang (Journal of Molecular Medicine, 2024)

Distance-decay equations of antibiotic resistance genes across freshwater reservoirs - Zhao-Feng Guo; Kiranmoy Das; Wiebke J. Boeing; Yao-Yang Xu; Edoardo Borgomeo; Dong Zhang; Si-Cheng Ao; Xiao-Ru Yang (Water Research, 2024)

C-Phycocyanin improves the quality of goat oocytes after in vitro maturation and vitrification - Xing-Yue Wang; Yang Gao; Hao-Ran Liu; Teng Wang; Meng-Lei Feng; Fang-Rui Xue; Kang Ding; Qi Yang; Zhao-Yu Jiang; Dui Sun; Chun-Ru Song; Xiao-Jie Zhang; et al. (Theriogenology, 2024)

Enhancing propionic acid production in the anaerobic fermentation of high-strength starch wastewater facilitated by hydraulic retention time and FeCl3 under alkaline pH - Wenjing Yang; Wei Fang; Jianning Chang; Ru Zhang; Yajie Zhang; Maoqing Wang; Panyue Zhang (Journal of Water Process Engineering, 2024)

Formation mechanism, environmental sensitivity and functional characteristics of succinylated ovalbumin/ε-polylysine electrostatic complexes: The roles of succinylation modification and ε-polylysine combination - Ru-yi Zhang; Hui-min Zhang; Tian-zhu Guan; Zhi-rong Wang; Hua-xiang Li; Lei Yuan; Yan-jun Yang; Sheng-qi Rao (Food Chemistry, 2024)

Carbon-in-carbon: Hybrid carbonized nanomaterials with multifunctional activities for the treatment of endophthalmitis - Hong-Jyuan Jian; Yi-Ru Chiou; Anisha Anand; Chien-Fu Chen; David Hui-Kang Ma; Jui-Yang Lai; Chih-Ching Huang; Huan-Tsung Chang (Chemical Engineering Journal, 2024)

Adsorption Kinetics and Stabilization Effects of Various Forms of Phosphorus on Schwertmannite - Shuqin Bai; Ru Ya; Shuxuan Chen; Niqi Ao; Yiwen Wu; Qiyao Sun; Han Yang; Shuangfeng Zhao (Water, Air, & Soil Pollution, 2024)

Screening of Strain from Reconstituted Sheet Tobacco Making High-Yield Enzyme and Aroma - Chun-Xue Yang; Deng Zhang; Hui Ma; Xiao-Meng Guo; Na Yan; Xue-Ting Deng; Xiang-Ru Liao; Zheng-Bing Guan (Proceedings of the National Academy of Sciences, India Section B: Biological Sciences, 2024)

Genome-wide identification of the SAUR gene family and screening for SmSAURs involved in root development in Salvia miltiorrhiza - Wei Wang; Yuwei Zheng; Lin Qiu; Dongfeng Yang; Ziyang Zhao; Yuanyuan Gao; Ru Meng; Hongguang Zhao; Shuncang Zhang (Plant Cell Reports, 2024)

SIRT3-Mediated Deacetylation of SDHA Rescues Mitochondrial Bioenergetics Contributing to Neuroprotection in Rotenone-Induced PD Models - Yanhua Shen; Xueting Wang; Nan Nan; Xiaolong Fu; Ru Zeng; Yonggang Yang; Siting Xian; Jingshan Shi; Qin Wu; Shaoyu Zhou (Molecular Neurobiology, 2024)

Colonization ability and uniformity of resources and environmental factors determine biological homogenization of soil protists in human land‐use systems - Zhi‐Peng Li; Hua‐Yuan Shangguan; Haifeng Yao; Xiao‐Ru Yang; Yuri Mazei; Biao Zhu; Stefan Scheu; Xin Sun (Global Change Biology, 2024)
Humans have substantially transformed the global land surface, resulting in the decline in variation in biotic communities across scales, a phenomenon known as “biological homogenization.” However, different biota are affected by biological homogenization to varying degrees, but this variation and the underlying mechanisms remain little studied, particularly in soil systems. To address this topic, we used metabarcoding to investigate the biogeography of soil protists and their prey/hosts (prokaryotes, fungi, and meso‐ and macrofauna) in three human land‐use ecosystem types (farmlands, residential areas, and parks) and natural forest ecosystems across subtropical and temperate regions in China. Our results showed that the degree of community homogenization largely differed between taxa and functional groups of soil protists, and was strongly and positively linked to their colonization ability of human land‐use systems. Removal analysis showed that the introduction of widespread, generalist taxa (OTUs, operational taxonomic units) rather than the loss of narrow‐ranged, specialist OTUs was the major cause of biological homogenization. This increase in generalist OTUs seemingly alleviated the negative impact of land use on specialist taxa, but carried the risk of losing functional diversity. Finally, homogenization of prey/host biota and environmental conditions were also important drivers of biological homogenization in human land‐use systems, with their importance being more pronounced in phagotrophic than parasitic and phototrophic protists. Overall, our study showed that the variation in biological homogenization strongly depends on the colonization ability of taxa in human land‐use systems, but is also affected by the homogenization of resources and environmental conditions. Importantly, biological homogenization is not the major cause of the decline in the diversity of soil protists, and conservation and study efforts should target at taxa highly sensitive to local extinction, such as parasites.

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Visible-light-driven photocatalytic degradation of ibuprofen by Cu-doped tubular C3N4: Mechanisms, degradation pathway and DFT calculation - Zhi-Bang Lv; Jiao Feng; Ru-Jin Zhao; Jun-Jian Shen; Wen-Wen Yang (Chemosphere, 2024)

Sex-inclined microRNAs in serum exosomes for sex determination in the greater amberjack (Seriola dumerili) - Qiuxia Deng; Yang Huang; Can Zhao; Xiaoying Ru; Ruijuan Hao; Na Zhao; Bo Zhang; Chunhua Zhu (Aquaculture, 2024)

Poleward migration of tropical corals inhibited by future trends of seawater temperature and calcium carbonate (CaCO3) saturation - Ya-Yi Huang; Ting-Ru Chen; Kim Phuong Lai; Chao-Yang Kuo; Ming-Jay Ho; Hernyi Justin Hsieh; Yi-Chia Hsin; Chaolun A. Chen (Science of The Total Environment, 2024)

Urinary haloacetic acid concentrations and thyroid function among women: Results from the TREE study - Yang Wu; Yan-Ling Deng; Min Zhang; Yu Miao; Fei-Peng Cui; Jia-Yue Zeng; Xiao-Ying Liu; Cheng-Ru Li; A-Xue Liu; Jin-Qin Zhu; Yang-Juan Li; Chong Liu; et al. (Science of The Total Environment, 2024)

CIP1, a CIPK23-interacting transporter, is implicated in Cd tolerance and phytoremediation - Jiayi Wang; Huihui Zhu; Ru’nan Huang; Jiming Xu; Li Huang; Jianli Yang; Weiwei Chen (Journal of Hazardous Materials, 2024)

Dual-role KCl-assisted fabrication of porous carbon with controllable architecture from coal liquefaction residue for supercapacitors - Xiaoxia Yang; Guoxiao Sun; Fei Wang; Long Chen; Zhuangzhuang Zhang; Yanzhong Zhen; Danjun Wang; Feng Fu; Ru’an Chi (Fuel, 2024)

Enteral nutrition in the management of acute pancreatitis: Modulates gut microbiome and alleviates inflammation - Fang-Yuan Yang; Yi-Jing Cai; Xiao-Ying Niu; Shun-Fu Wang; Yu-Qi Wang; Sabola Eluby Esmie; Rui-Cong Chen; Sheng-Jie Dai; Hong-Ru Kong; Hong-Wei Sun; Ke-Qing Shi (Food Bioscience, 2024)

Ovalbumin amyloid-like fibrils/resveratrol self-assembling hydrogel: Preparation, characterization and formation mechanism - Ya-Ru Wang; Qin Yang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Halogenated aromatic pollutants in routine animal-derived food of south China: Occurrence, sources, and dietary intake risks - Li-Na Zhang; Ping-An Peng; Hui-Ru Li; Ming-Yang Liu; Jian-Fang Hu (Environmental Pollution, 2024)

Polymer composite membranes as SERS substrate materials: Recyclable and highly stable - Haonan Wang; Chuyi Wang; Qingling Nie; Ru Liu; Yixuan Yang; Jiayi Lin; Bohan Zhang; Ruiyun You; Yunzhen Liu; Xiufeng Xiao; Yudong Lu (Chemical Engineering Journal, 2024)

A freestanding rotating triboelectric nanogenerator with large area and high efficiency for triboelectric plasma CO2 reduction - Hongjie Cao; Qinglong Ru; Dongyang Fang; Sumin Li; Nannan Liu; Wei Jiang; Hui Hu; Yongcui Yang; Guangqin Gu; Bao Zhang; Gang Cheng; Sanjun Yang; et al. (Chemical Engineering Journal, 2024)

Delayed Chronic Acidic Postconditioning Improves Poststroke Motor Functional Recovery and Brain Tissue Repair by Activating Proton-Sensing TDAG8 - Yan-Ying Fan; Yu Li; Xiao-Ying Tian; Ying-Jing Wang; Jing Huo; Bao-Lu Guo; Ru Chen; Cai-Hong Yang; Yan Li; Hui-Feng Zhang; Bao-Long Niu; Ming-Sheng Zhang (Translational Stroke Research, 2024)

Potential use of maize–peanut intercropping to adapt to drought and nitrogen–shortage impacts - Fei Han; Shuqing Guo; Muhammad Asad Naseer; Ru Guo; Tie Cai; Peng Zhang; Zhikuan Jia; Dong Yang; XiaoLi Chen; Xiaolong Ren (Plant and Soil, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Candidate gene mining of GA-mediated regulation of pear fruit shape - Zeyu Xue; Ru Yang; Yadong Wang; Yuchen Ma; Yujing Lin; Zhengao Li; Yuqin Song; Xinxin Feng; Liulin Li (Horticulture, Environment, and Biotechnology, 2024)

Dissolved oxygen and ammonia affect ammonia production via GDH/AMPK signaling pathway and alter flesh quality in Chinese perch (Siniperca chuatsi) - Ru Yang; Xuange Liu; Yong Liu; Qingda Tian; Ziwei Wang; Dejie Zhu; Zhisong Qian; Yi Yi; Jiacheng Hu; Yan Li; Xu-Fang Liang; Liwei Liu; et al. (Fish Physiology and Biochemistry, 2024)

Addition of α-ketoglutaric acid (AKG) reduces deamination in Chinese perch (Siniperca chuatsi) fed with fermented soybean meal as a substitute for fishmeal - Yufei Zhang; Jiacheng Hu; Peisong Lu; Ru Yang; Xu-Fang Liang; Liwei Liu (Fish Physiology and Biochemistry, 2024)

Aconitum coreanum and processed products on its base prevent stroke via the PI3K/Akt and KEAP1/NRF2 in the in vivo study - Wan-ting Zeng; Li-ting Zhou; Ru Jia; Yue Liu; Qian Cai; Yang Qu (Metabolic Brain Disease, 2024)

Assessing climate/air quality synergies and cost-effectiveness for Beijing transportation: Insights into sustainable development - Xuefang Wu; Roy M. Harrison; Min Chen; Tao Wang; Ruihe Lyu; Shuan Peng; Runpu Liu; Yushuo Chen; Yan Ru Fang; Pingjian Yang (Sustainable Cities and Society, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Effect of bovine hide gelatin antifreeze peptides on the quality of frozen dough treated with freeze-thaw cycles and its steamed bread - Chun-Chun Zhang; Ya-Ru Wang; Qin Yang; Han-Qing Chen (Journal of Cereal Science, 2024)

Pretreatment with low-frequency magnetic fields can improve the functional properties of pea globulin amyloid-like fibrils - Qing-Qing Liu; Qin Yang; Ya-Ru Wang; Yi-Xuan Jiang; Han-Qing Chen (Food Chemistry, 2024)

Anhydride esterification to regulate water migration and reduce ice crystal formation in κ-carrageenan gel during freezing - Xinwei Xu; Feng Jiang; Kuncheng Lin; Jingjing Fang; Fuquan Chen; Yi Ru; Huifen Weng; Qiong Xiao; Qiuming Yang; Anfeng Xiao (Food Hydrocolloids, 2024)

Ultrasound-regulated fibrillation of arachin: Structural characteristics, foaming and emulsifying properties - Qin Yang; Ya-Ru Wang; Qing-Qing Liu; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Development, characteristics and biological activities of bilayer composite film based on gelatin/κ-carrageenan loading curcumin and ε-polylysine - Xihan Yang; Minzhen Zhang; Baoding Zhao; Xiaoyu Zou; Ru Song (Food Hydrocolloids, 2024)

Redirecting surface reconstruction of CoP-Cu heterojunction to promote ammonia synthesis at industrial-level current density - Li Gan; Xiaoxue Zhang; Lei Guo; Muhammad Ajmal; Ru Jia; Xiaolei Guo; Chengxiang Shi; Lun Pan; Faryal Idrees; Xiangwen Zhang; Zhen-Feng Huang; Guidong Yang; et al. (Chemical Engineering Journal, 2024)

Vital residues-orientated rational design of butenolide inhibitors targeting Of ChtI - Qing Han; Yun-Jiang Zi; Tian-Yu Feng; Nan Wu; Ren-Xuan Zou; Jing-Yu Zhang; Ru-Lei Zhang; Qing Yang; Hong-Xia Duan (Medicinal Chemistry Research, 2024)

Experiments and CFD simulation of downwash airflow and fog distribution discharged from a single-rotor UAV fitted with a pulse-jet thermal fogging machine - Jian Zhang; Qing Chen; Jian Liu; Yan Wang; Hongping Zhou; Fengbo Yang; Yu Ru (Biosystems Engineering, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Sulfur and nitrogen co-metabolism during composting: A role of sodium sulfide in regulating microbial communities and functional genes - Shuaipeng Liu; Heng Lu; Ao Wang; Xiaojing Chen; Hongmei Yang; Xueling Liang; Ru Sun; Xiaoli Wen; Qunliang Li (Journal of Environmental Chemical Engineering, 2024)

Interfacial behavior and micro-rheological performance of Pickering emulsions co-stabilized by β-cyclodextrin and xanthan gum - Wei Liang; Fanghui Deng; Yuhang Wang; Wei Yue; Die Hu; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Subsurface organic amendment of a saline soil increases ecosystem multifunctionality and sunflower yield - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Jing Wang; Aiping Chen; Yang Xu; Yu Liu; Jie Zhou; Yuyi Li (Science of The Total Environment, 2024)

Mainstream migration events of the Yellow River and anthropogenic responses during the Mid-Holocene - Tinglin Ru; Liwei Yang; Gesong Wei; Xinze Li; Zhanfang Hou; Yingying Chen; Shiyue Chen (Quaternary International, 2024)

Hotspot mapping and risk prediction of fluoride in natural waters across the Tibetan Plateau - Yi Yang; Ru Zhang; Yangzong Deji; Yonghua Li (Journal of Hazardous Materials, 2024)

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Enhanced solubility, thermal stability and antioxidant activity of resveratrol by complexation with ovalbumin amyloid-like fibrils: Effect of pH - Ya-Ru Wang; Qin Yang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Optimizing maize productivity: A sustainable approach integrating straw derivatives and film mulching in rainfed agriculture - Rui Qian; Zijun Ma; Yunyun Yang; Ru Guo; Fei Han; Jinjin Wang; Xiaoling Wang; Baoping Sun; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Field Crops Research, 2024)

Exposures to drinking water disinfection byproducts and kidney function in Chinese women - Cheng-Ru Li; Yan-Ling Deng; Yu Miao; Min Zhang; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Chong Liu; Qiang Zeng (Environmental Research, 2024)

Two-dimensional metal–organic framework nanocomposite membranes with shortened ion pathways for enhanced salinity gradient power harvesting - Van-Phung Mai; Amalia Rizki Fauziah; Chuan-Ru Gu; Zhen-Jie Yang; Kevin C.-W. Wu; Li-Hsien Yeh; Ruey-Jen Yang (Chemical Engineering Journal, 2024)

Efficient synthesis of squalene by cytoplasmic-peroxisomal engineering and regulating lipid metabolism in Yarrowia lipolytica - Yang Ning; Mengsu Liu; Ziyun Ru; Weizhu Zeng; Song Liu; Jingwen Zhou (Bioresource Technology, 2024)

Desynchronization of neural networks induced by transcranial magneto-acoustical stimulation: a modeling study - Zhenfang Ma; Yuhui Yang; Jianyang Xu; Yi Ru; Yu Yin (Neurophysiology, 2024)

Chiral zeolite beta used as stationary phase for enantioseparation in miniaturized open tubular capillary electrochromatography with amperometric detection - Li Yang; Ru Liu; Chaodan Li; Boning Gu; Jiannong Ye; Li Chen; Qingcui Chu (Analytica Chimica Acta, 2024)

Biological upcycling of nickel and sulfate as electrocatalyst from electroplating wastewater - Xian-Zhong Fu; Yu-Ru Yang; Tian Liu; Zhi-Yan Guo; Chen-Xuan Li; Hai-Yang Li; Kang-Ping Cui; Wen-Wei Li (Water Research, 2024)

Adaptive shifts in plant traits associated with nitrogen removal driven by phytoremediation strategies in subtropical river restoration - Yu Xin; Lin Liu; Xiao-Ru Yang; Le-Yang Yang; Shan-Bin Guang; Yu-Ming Zheng; Quan-Bao Zhao (Water Research, 2024)

Urinary biomarkers of drinking-water disinfection byproducts in relation to diminished ovarian reserve risk: A case-control study from the TREE cohort - Xiao-Ying Liu; Min Zhang; Xiao-Li Gu; Yan-Ling Deng; Chong Liu; Yu Miao; Yang Wu; Cheng-Ru Li; Jia-Yue Zeng; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; et al. (Science of The Total Environment, 2024)

Can straw recycling achieve sustainable agriculture at the smallholder level? A case in a semi-arid region - Rui Qian; Ru Guo; Qingxuan Yang; Muhammad Asad Naseer; Baoping Sun; Longlong Wang; Jian Zhang; Xiaolong Ren; Xiaoli Chen; Zhikuan Jia (Journal of Cleaner Production, 2024)

Maize/peanut rotation intercropping improves ecosystem carbon budget and economic benefits in the dry farming regions of China - Fei Han; Talha Javed; Sadam Hussain; Shuqing Guo; Ru Guo; Lihua Yang; Xiantong Liu; Tie Cai; Peng Zhang; Zhikuan Jia; Anis Ali Shah; Xiaoli Chen; et al. (Journal of Environmental Management, 2024)

Formation and structural characteristics of pea globulin amyloid-like fibrils pretreated with low-frequency magnetic field - Qing-Qing Liu; Qin Yang; Ya-Ru Wang; Yi-Xuan Jiang; Han-Qing Chen (Food Hydrocolloids, 2024)

Unraveling the electrical energy loss in silver nanowire electrodes for flexible and Large-Area organic solar cells - Hao Ren; Wei-Shuo Chen; Jing-De Chen; Jin-Peng Yang; Ye-Fan Zhang; Hong-Yi Hou; Shuo Tian; Heng-Ru Ge; Yan-Qing Li; Jian-Xin Tang (Chemical Engineering Journal, 2024)

Intravenous immunoglobulin for treatment of hospitalized COVID-19 patients: an evidence mapping and meta-analysis - Mei-xuan Li; Yan-fei Li; Xin Xing; Jun-qiang Niu; Liang Yao; Meng-ying Lu; Ke Guo; Mi-na Ma; Xiao-tian Wu; Ning Ma; Dan Li; Zi-jun Li; et al. (Inflammopharmacology, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Assessing production–living–ecological spaces and its urban–rural gradients in Xiangyang City, China: insights from land-use function symbiosis - Chao Liu; Qingke Yang; Fenghua Zhou; Ru Ai; Long Cheng (Environmental Science and Pollution Research, 2024)

Deciphering the influence of dietary synbiotics in white shrimp gut and its effects in regulating immune signaling pathways - Sofia Priyadarsani Das; Zaenal Abidin; Huai-Ting Huang; Yu-Ru Lin; Chih-Yang Huang; Yu-Sheng Wu; Yeh-Fang Hu; Fan-Hua Nan (Frontiers in Marine Science, 2024)
The health of the host is significantly influenced by the gut microbiota. Penaeus vannamei (white shrimp) is one of the most profitable aquaculture species globally. Synbiotics are typically used as a beneficial diet supplement for raising aquaculture species’ growth capacities and enhancing immunity against pathogenicity. However, the effects of synbiotics on the white shrimp intestinal microbiota remain poorly understood. In the present study, we targeted the V3–V4 region of 16S rRNA genes to analyze the effects of synbiotics on white shrimp gut microbiota. Dietary synbiotics, having Lactobacillus acidophilus , and Moringa oleifera leaf extract were added to the white shrimps’ feed in various proportions in the present study. In total, 490 operational taxonomic units yielding 23 phyla, 41 classes, 94 orders, 151 families, and 250 genera of microorganisms were obtained. The diet containing L. acidophilus at 1 × 10 7 CFU/g and M. oleifera at 2.5 g/kg led to an increase in the relative abundance of beneficial microorganisms through a significant decrease in the α diversity. Moreover, it upregulated several physiological pathways such as carbohydrate metabolism, signal transduction, lipid metabolism, nucleotide metabolism, amino acid metabolism, and environmental adaptation, which led to the upregulation of the AMPK, MAPK, P13K-Akt, lysosome, peroxisome, and ferroptosis signaling pathways; this enhanced growth and immunity in white shrimp. Whether a single species or a combination of different microorganisms improves growth and immunity remains unclear till now. Nevertheless, our results will facilitate further in-depth investigation into beneficial microbial communities for upliftment of white shrimp aquaculture.

Effects of Different Intensities and Wavelengths of Light on the Growth of Juvenile Tridacna noae - Rod Ping-Tsan Lee; Yu-Ru Lin; Chih-Yang Huang; Fan-Hua Nan (Molluscan Research, 2024)

Soil microbial diversity and network complexity drive the ecosystem multifunctionality of temperate grasslands under changing precipitation - Changchun Zhai; Lili Han; Chao Xiong; Anhui Ge; Xiaojing Yue; Ying Li; Zhenxing Zhou; Jiayin Feng; Jingyi Ru; Jian Song; Lin Jiang; Yunfeng Yang; et al. (Science of The Total Environment, 2024)

Effect of marine heatwaves on juvenile greater amberjack (Seriola dumerili) - Yali Tian; Hang Li; Dongying Zhang; Chen Wang; Ruijuan Hao; Xiaoying Ru; Qin Hu; Yang Huang; Chunhua Zhu (Marine Environmental Research, 2024)

Accelerated removal of naproxen in the iron-based peracetic acid activation system by chloride ions: Enhancement of reactive oxidative species via the formation of iron-chloride complexes - Si-Ying Yu; Yang Shi; Chuan-Shu He; Yu-Dan Dong; Si Sun; Ru-Yan Ning; Zhao-Kun Xiong; Peng Zhou; Heng Zhang; Bo Lai (Journal of Hazardous Materials, 2024)

Associations between urinary biomarkers of exposure to disinfection byproducts and semen parameters: A repeated measures analysis - Min Zhang; Xiao-Ying Liu; Yan-Ling Deng; Chong Liu; Jia-Yue Zeng; Yu Miao; Yang Wu; Cheng-Ru Li; Yang-Juan Li; A-Xue Liu; Jin-Qin Zhu; Qiang Zeng (Journal of Hazardous Materials, 2024)

Electrochemically mediated phosphorus and energy recovery from digested effluent - Ling-ling Lai; Si-zhuo Wan; Mahmood Qaisar; Yi-fan Yang; Ru Wang; Lin-jiang Yuan (Journal of Environmental Management, 2024)

Effects of freezing methods on physicochemical properties, protein/fat oxidation and odor characteristics of surimi gels with different cross-linking degrees - Xiaoying Luo; Kang Huang; Yongxin Niu; Xu Zhang; Yueqi An; Ru Liu; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

High internal phase emulsions of ω-3 fatty acids stabilized by fish scale gelatin particles: Application to lipid-enhanced surimi 3D printing - Yuhang Wang; Die Hu; Wei Yue; Juan You; Tao Yin; Jianhua Rong; Ru Liu; Shanbai Xiong; Yang Hu (Food Hydrocolloids, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Study and application of coupling relationship between water-salt-resistivity-soil structure in saline soils in arid and semi-arid areas of northwest China - Yang Liu; Feng-jie Li; Hong-li Liu; Yu-ru Hou; Nusrat Nazir (Environmental Research, 2024)

Urban green, blue spaces and their joint effect are associated with lower risk of emotional and behavior problem in children and adolescents, a large population-based study in Guangzhou, China - Jing-hong Liang; Ru-yu Yang; Mei-ling Liu; Ying-qi Pu; Wen-wen Bao; Yu Zhao; Li-xin Hu; Yu-shan Zhang; Shan Huang; Nan Jiang; Xue-ya Pu; Shao-yi Huang; et al. (Environmental Research, 2024)

High-strength ionic hydrogel constructed by metal-free physical crosslinking strategy for enhanced uranium extraction from seawater - Yuan-Hao Wang; Yu-Qin Xiang; Qian Huang; Xiao-Lan Yang; Shuang-Long Wang; Yue-Ru Zhou; Song Qin; Ling-Qiong Gou; Guo-Hong Tao; Ling He (Chemical Engineering Journal, 2024)

Comammox plays a functionally important role in the nitrification of rice paddy soil with different nitrogen fertilization levels - Kai Zhang; Hui-Feng Sun; You-Cai Kang; Ran Jiang; Yan-Ren Wang; Ru-Yi Zhang; Sheng-Nan Zhang; Yang-Yang Li; Peng Li; Fan Yang; Sheng Zhou; Zhe-Xue Quan (Applied Soil Ecology, 2024)

Supramolecular fluorescence sensor array used for the analysis of tyrosine kinase inhibitors in biological fluids and cell imaging - Hong-Ling Yi; Ru-Pei Yang; Qing Tang; Zhu Tao; Ying Huang (Analytica Chimica Acta, 2024)

Sympatric munias in tropical areas segregate spatially through different nest site selections to achieve coexistence - Chen-Wei Guo; Li-Li Li; Chen-Yang Liu; Ru-Chuan He; Rui-Chang Quan (Acta Oecologica, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Occurrence, ecological risk, and advanced removal methods of herbicides in waters: a timely review - Lingxiao Li; Yunsheng Wang; Lijuan Liu; Chen Gao; Shaoguo Ru; Liqiang Yang (Environmental Science and Pollution Research, 2023)

A Dual Functional Fluorescent Probe Based on Phenothiazine for Detecting Hg2+ and ClO− and its Applications - Cheng-lu Zhang; Chang Liu; Shi-ru Nie; Yang Zhang; Jing-hao Guo; Xiang-ling Li; Cui Liu (Journal of Fluorescence, 2023)

A novel hydrangea-like magnetic composite Fe3O4@MnO2@ZIF-67 for efficient selective adsorption of Pd(II) from metallurgical wastewater - Xue Jiang; Yu Zhou; Haiou Chen; Ru Zhang; Junhui Yu; Shixiong Wang; Fengzhi Jiang; Huiping Bai; Xiangjun Yang (Chemosphere, 2023)

Effect of swimming training on the flesh quality in Chinese Perch (Siniperca chuatsi) and its relationship with muscle metabolism - Tingyao Zhu; Ru Yang; Runguo Xiao; Weiqiang Ni; Liwei Liu; Jian Zhao; Zhangying Ye (Aquaculture, 2023)

Corrigendum to “Silica nanoparticles promote oxLDL-induced macrophage lipid accumulation and apoptosis via endoplasmic reticulum stress signaling” [Sci. Total Environ., 631-632 (2018): 570-579] - Caixia Guo; Ru Ma; Xiaoying Liu; Tian Chen; Yang Li; Yang Yu; Junchao Duan; Xianqing Zhou; Yanbo Li; Zhiwei Sun (Science of The Total Environment, 2023)

Clarification of the phosphorus release mechanism for recovering phosphorus from biofilm sludge in alternating aerobic/anaerobic biofilm system - Hao Zhang; Shuang-Shuang Zhang; Wei Zhang; Wu-Cheng Ma; Yang Pan; Lin Chen; Liang Zhu; Yi-Ping Li; Jing-Ru Li (Science of The Total Environment, 2023)

Artificial light at night, MRI-based measures of brain iron deposition and incidence of multiple mental disorders - Jianbo Jin; Wenxing Han; Teng Yang; Zhihu Xu; Jin Zhang; Ru Cao; Yuxin Wang; Jiawei Wang; Xin Hu; Tiantian Gu; Fan He; Jing Huang; et al. (Science of The Total Environment, 2023)

Fe2O3/TiO2/reduced graphene oxide-driven recycled visible-photocatalytic Fenton reactions to mineralize organic pollutants in a wide pH range - Ru Zheng; Dehong Yang; Yao Chen; Zhenfeng Bian; Hexing Li (Journal of Environmental Sciences, 2023)

A novel strategy for inhibiting AGEs in fried fish cakes: Grape seed extract surimi slurry coating - Yanlei Gao; Haonan Shi; Qing Xiong; Runlin Wu; Yang Hu; Ru Liu (Food Control, 2023)

Predicting energy consumption of chiller plant using WOA-BiLSTM hybrid prediction model: A case study for a hospital building - Yang Song; Hui Xie; Zhengwei Zhu; Ru Ji (Energy and Buildings, 2023)

Dietary soybean lecithin promoted growth performance and feeding in juvenile Chinese perch (Siniperca chuatsi) could be by optimizing glucolipid metabolism - Dongliang Wu; Di Peng; Xu-Fang Liang; Ruipeng Xie; Ming Zeng; Junliang Chen; Jie Lan; Ru Yang; Jiacheng Hu; Peisong Lu (Fish Physiology and Biochemistry, 2023)

Studying environmental and economic considerations on tourism activities in achieving sustainable development goals: implications for sustainability - Shuying Zhai; Ru Li; Yuange Yang (Environmental Science and Pollution Research, 2023)

Experimental study on vegetation performance improvement of carbonaceous mudstone aggregate vegetation concrete with its micromechanism - Ling Zeng; Zi-Ru Yang; Huan-Yi Zha; Wei Wen; Jie Liu (European Journal of Environmental and Civil Engineering, 2023)

Recent advances in the unlined cast iron pipe scale characteristics, cleaning techniques and harmless disposal methods: An overview - Ming Li; Dong Zhang; Ru Zhang; Fang Wang; Yang Song; Feiyong Chen; Juan Yang; Changming Li (Chemosphere, 2023)

Mechanisms of swelling inhibition and seepage promotion of weathered crust elution-deposited rare earth ore by hydroxypropyl methyl cellulose - Aoyang Sha; Huifang Yang; Zhengyan He; Qin Zuo; Zhigao Xu; Chenjie Wu; Ming Wu; Ru'an Chi (Minerals Engineering, 2023)

Mineralogy, petrology and P-T conditions of the spodumene pegmatites and surrounding meta-sediments in Lhozhag, eastern Himalaya - Jia-Min Wang; Kang-Shi Hou; Lei Yang; Xiao-Chi Liu; Ru-Cheng Wang; Guang-Ming Li; Jian-Gang Fu; Fang-Yang Hu; Yu-Lu Tian; Fu-Yuan Wu (Lithos, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Co-delivery of curcumin and quercetin in the bilayer structure based on complex coacervation - Le Ma; Chun-Ru Su; Shi-Ying Li; Shan He; Anindya Nag; Yang Yuan (Food Hydrocolloids, 2023)

Continuous exposure to bisphenol S increases the accumulation of endogenous metabolic toxicants by obstructing the glucuronic acid pathway - Ze Li; Shaoguo Ru; Jiali Li; Yunjia Yang; Weiwei Wang (Environmental Pollution, 2023)

Organophosphate esters (OPEs) in a heavily polluted river in South China: Occurrence, spatiotemporal trends, sources, and phase distribution - Yi-Shan Liu; Hui-Ru Li; Zhi-Lang Lao; Sheng-Tao Ma; Zi-Cong Liao; Ai-Min Song; Ming-Yang Liu; You-Sheng Liu; Guang-Guo Ying (Environmental Pollution, 2023)

Advances in understanding entire process of medium chain carboxylic acid production from organic wastes via chain elongation - Qingyan Wang; Nan Yang; Yajing Cai; Ru Zhang; Yan Wu; Weifang Ma; Chuan Fu; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

Urban greenspace types influence the microbial community assembly and antibiotic resistome more in the phyllosphere than in the soil - Xin-Rong Huang; Roy Neilson; Le-Yang Yang; Jing-Jun Deng; Shu-Yi-Dan Zhou; Hu Li; Yong-Guan Zhu; Xiao-Ru Yang (Chemosphere, 2023)

Deep insights into the population shift of n-DAMO and Anammox in granular sludge: From sidestream to mainstream - Sheng-Qiang Fan; Wan-Ru Wen; Guo-Jun Xie; Yang Lu; Bing-Feng Liu; De-Feng Xing; Jun Ma; Nan-Qi Ren (Water Research, 2023)

A new norditerpenoid and other components from Ajuga macrosperma and their bioactivity - Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Hong-Ping He; Rui Yang; Hua-Yi Jiang (Phytochemistry Letters, 2023)

The sulfate assimilation and reduction of marine microalgae and the regulation of illumination - Wen-Ying Dai; Lu Han; Pei-Feng Li; Qin-Dao Li; Li-Jun Xie; Chun-Ying Liu; Jun-Ru Kong; Ru Jia; Dan-Yang Li; Gui-Peng Yang (Marine Environmental Research, 2023)

Creep properties and energy evolution characteristics of weakly cemented rock under step loading - Shanchao Hu; Chenxi Zhang; Wenkai Ru; Jinming Han; Shihao Guo; Xuedong Zhou; Lei Yang (International Journal of Rock Mechanics and Mining Sciences, 2023)

Highly effective and selective recovery of Gd(III) from wastewater by defective MOFs-based ion-imprinted polymer: Performance and mechanism - Ming yang; Yuxin Zhou; Dandan Zhang; Fang Zhou; Hui Ning; Maoxia He; Ru-an Chi; Weiyan Yin (Chemical Engineering Journal, 2023)

Fungal strain improvement for efficient cellulase production and lignocellulosic biorefinery: Current status and future prospects - Jie Yang; Hou-Ru Yue; Li-Ya Pan; Jia-Xun Feng; Shuai Zhao; Surisa Suwannarangsee; Verawat Champreda; Chen-Guang Liu; Xin-Qing Zhao (Bioresource Technology, 2023)

Metagenomic analysis reveals the efficient digestion mechanism of corn stover in Angus bull rumen: Microbial community succession, CAZyme composition and functional gene expression - Jinsong Liang; Jianning Chang; Ru Zhang; Wei Fang; Le Chen; Weifang Ma; Yajie Zhang; Wenjing Yang; Yuehan Li; Panyue Zhang; Guangming Zhang (Chemosphere, 2023)

Biosorption and biotransformation behaviours of veterinary antibiotics under aerobic livestock wastewater treatment processes - Chih-Hung Chen; Yi-Chu Chiou; Chao-Lung Yang; Jen-Hung Wang; Wan-Ru Chen; Liang-Ming Whang (Chemosphere, 2023)

Functional characterization of African swine fever virus I329L gene by transcriptome analysis - Xianghan Duan; Yuan Wen; Panxue Wu; Jiangling Peng; Yanlong Zhou; Guoqiang Zhu; Dan Li; Yi Ru; Wenping Yang; Haixue Zheng (Veterinary Microbiology, 2023)

Ferritinophagy activation and sideroflexin1-dependent mitochondrial iron overload contribute to patulin-induced cardiac inflammation and fibrosis - Wen-Chang Sun; Ning-Ning Wang; Ru Li; Xian-Ce Sun; Jia-Wei Liao; Guang Yang; Shuang Liu (Science of The Total Environment, 2023)

Effects of contrasting tillage managements on the vertical distribution of plant- and microbial-derived carbon in rice paddy - Jian-Ying Qi; Xiang-Bin Yao; Mei-Yang Duan; Xiang-Wen Huang; Mei-Yi Fan; Ya Yang; Hao-Wen Luo; Xiang-Ru Tang (Science of The Total Environment, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

CDN1163, a SERCA activator, causes intracellular Ca2+ leak, mitochondrial hyperpolarization and cell cycle arrest in mouse neuronal N2A cells - Yi-Ping Huang; Wen-Wei Huang; Kun-Feng Tsai; Lian-Ru Shiao; Zih-He Yang; Shao-Yun Tseng; Yu-Hsien Lin; Cing-Yu Chen; Paul Chan; Yuk-Man Leung (NeuroToxicology, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Individual and joint associations of urinary phthalate metabolites with polycystic ovary and polycystic ovary syndrome: Results from the TREE cohort - Min Zhang; Chong Liu; Xiao-Qiong Yuan; Fei-Peng Cui; Yu Miao; Wen Yao; Dan-Yu Qin; Yan-Ling Deng; Pan-Pan Chen; Jia-Yue Zeng; Xiao-Ying Liu; Yang Wu; et al. (Environmental Toxicology and Pharmacology, 2023)

Toxic effects of perfluorocaproic acid (PFHxA) on crucian carp (Carassius auratus) and the response of the intestinal microbial community - Xue Jiao; Zheng yao Guo; Bing li Liu; Long tao Wang; Zhi nan Yang; Yuan ru Yang; Ai-dong Qian; Yue-hong Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

(±)-Sarcanan A, a pair of new enantiomeric dihydrobenzofuran neolignans from the aerial parts of Sarcandra glabra - Ju Liu; Qi-yin Wen; Hong-ru Tian; Bing-jin-feng Zhan; Long-ping Zhu; De-po Yang; Zhi-min Zhao (Natural Product Research, 2023)

A hybrid optimized model for predicting evapotranspiration in early and late rice based on a categorical regression tree combination of key influencing factors - Long Zhao; Shunhao Qing; Jiayi Bai; Haohao Hao; Hui Li; Yi Shi; Xuguang Xing; Ru Yang (Computers and Electronics in Agriculture, 2023)

Effects of dietary starch and metformin levels on the growth performance, body composition, hepatic glycolipid metabolism, and liver histology of juvenile largemouth bass Micropterus salmoides - Qin-Qin Liu; Ru Xia; Xin Deng; Hui-Jun Yang; Li Luo; Shi-Mei Lin; Chuan-Jie Qin; Yong-Jun Chen (Aquaculture, 2023)

Zinc supplementation promotes oocyte maturation and subsequent embryonic development in sheep - Yupei Yao; Yujie Tang; Haoqiang Qin; Ru Meng; Chengtu Zhang; Yingbing Zhang; Ying Yang; Peipei Qiao; Jun Liu; Jianmin Su (Theriogenology, 2023)

The sustainable treatment of chemical polishing wastewater under low-carbon economy: Pollutants removal, resource recovery and energy generation - Cong Ding; Meng-yu Liu; Si-zhuo Wan; Zhao-yang Cai; Lin-jiang Yuan; Ru Wang; Ping Zheng (Journal of Cleaner Production, 2023)

First transcriptome profiling in gill and hepatopancrease tissues of Metapenaeus ensis in response to acute ammonia-N stress - Yun-Dong Li; Meng-Ru Si; Shi-Gui Jiang; Qi-Bin Yang; Song Jiang; Li-Shi Yang; Jian-Hua Huang; Fa-Lin Zhou (Fish & Shellfish Immunology, 2023)

Pollinium development and sporoderm structure of Dendrobium officinale - Yi Feng Cui; Ting Zhou; Ya Ru Wei; De Quan Wang; Wen Yu Liang; Shu Juan Yang (Flora, 2023)

High transmittance, fast response, and high contrast ratio smart window with lateral driving electrophoretic display - Guangyou Liu; Jie Liu; Qitian Fan; Yunhe Liu; Zheng Zeng; Zhuohang Li; Xinzao Wu; Mingyang Yang; Bo-Ru Yang (Chemical Engineering Journal, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Contributions of abundant and rare bacteria to soil multifunctionality depend on aridity and elevation - Peng He; Ning Ling; Xiao-Tao Lü; Hai-Yang Zhang; Chao Wang; Ru-Zhen Wang; Cun-Zheng Wei; Jing Yao; Xiao-Bo Wang; Xing-Guo Han; Zhibiao Nan (Applied Soil Ecology, 2023)

Recent Progress in Atmospheric Chemistry Research in China: Establishing a Theoretical Framework for the “Air Pollution Complex” - Tong Zhu; Mingjin Tang; Meng Gao; Xinhui Bi; Junji Cao; Huizheng Che; Jianmin Chen; Aijun Ding; Pingqing Fu; Jian Gao; Yang Gao; Maofa Ge; et al. (Advances in Atmospheric Sciences, 2023)
Atmospheric chemistry research has been growing rapidly in China in the last 25 years since the concept of the “air pollution complex” was first proposed by Professor Xiaoyan TANG in 1997. For papers published in 2021 on air pollution (only papers included in the Web of Science Core Collection database were considered), more than 24 000 papers were authored or co-authored by scientists working in China. In this paper, we review a limited number of representative and significant studies on atmospheric chemistry in China in the last few years, including studies on (1) sources and emission inventories, (2) atmospheric chemical processes, (3) interactions of air pollution with meteorology, weather and climate, (4) interactions between the biosphere and atmosphere, and (5) data assimilation. The intention was not to provide a complete review of all progress made in the last few years, but rather to serve as a starting point for learning more about atmospheric chemistry research in China. The advances reviewed in this paper have enabled a theoretical framework for the air pollution complex to be established, provided robust scientific support to highly successful air pollution control policies in China, and created great opportunities in education, training, and career development for many graduate students and young scientists. This paper further highlights that developing and low-income countries that are heavily affected by air pollution can benefit from these research advances, whilst at the same time acknowledging that many challenges and opportunities still remain in atmospheric chemistry research in China, to hopefully be addressed over the next few decades.

CAT Interruption as a Protective Factor in Chinese Patients with Spinocerebellar Ataxia Type 1 - Ya-Ru Shao; Jin-Yang Yu; Yin Ma; Yi Dong; Zhi-Ying Wu (The Cerebellum, 2023)

Short-term exposure to enrofloxacin causes hepatic metabolism disorder associated with intestinal flora dysbiosis in adult marine medaka (Oryzias melastigma) - Meiru Wang; Yifan Qin; Yifan Liu; Hui Yang; Jun Wang; Shaoguo Ru; Pengfei Cui (Marine Pollution Bulletin, 2023)

Xanthine-derived reactive oxygen species exacerbates adipose tissue disorders in male db/db mice induced by real-ambient PM2.5 exposure - Leijian Chen; Huankai Li; Yi Ru; Yuanyuan Song; Yuting Shen; Lifang Zhao; Gefei Huang; Yi Chen; Zenghua Qi; Ruijin Li; Chuan Dong; Jiacheng Fang; et al. (Science of The Total Environment, 2023)

Silica nanoparticles promoted pro-inflammatory macrophage and foam cell transformation via ROS/PPARγ/NF-κB signaling - Caixia Guo; Xinying Zhao; Ru Ma; Lingnan Zhu; Yueyue Chen; Zhu Yang; Zongwei Cai; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Accumulation characteristics, driving factors, and model prediction of cadmium in soil-highland barley system on the Tibetan Plateau - Ruxia Li; Ru Zhang; Yi Yang; Yonghua Li (Journal of Hazardous Materials, 2023)

Effects of flow velocity on the growth performance, antioxidant activity, immunity and intestinal health of Chinese Perch (Siniperca chuatsi) in recirculating aquaculture systems - Tingyao Zhu; Ru Yang; Runguo Xiao; Liwei Liu; Songming Zhu; Jian Zhao; Zhangying Ye (Fish & Shellfish Immunology, 2023)

Ganglioside-focused Glycan Array Reveals Abnormal Anti-GD1b Auto-antibody in Plasma of Preclinical Huntington’s Disease - Tien-Wei Lin; Jung-Kai Chang; Yih-Ru Wu; Tsung-Hsien Sun; Yang-Yu Cheng; Chien-Tai Ren; Mei-Hung Pan; Jin-Lin Wu; Kuo-Hsuan Chang; Hwai-I Yang; Chiung-Mei Chen; Chung-Yi Wu; et al. (Molecular Neurobiology, 2023)

Applying expanded metal mesh for outdoor shades in outdoor thermal environments - Shing-Ru Yang; Shih-Tang Lan; Yi-Ting Wu; Tsuyoshi Honjo; Tzu-Ping Lin (International Journal of Biometeorology, 2023)

Factors influencing the spatial distribution and individual variation in urinary fluoride levels in Tibet, China - Ru Zhang; Yi Yang; Yangzong Deji; Hairong Li; Yonghua Li; Cangjue Nima; Shengcheng Zhao; Hongqiang Gong (Chemosphere, 2023)

Planning the temporary takeoff/landing site’s location for a pesticide spraying helicopter based on an intelligent fusion algorithm - Shuping Fang; Yu Ru; Chenming Hu; Fengbo Yang; Jiangkun Xue; Jie Zhou (Computers and Electronics in Agriculture, 2023)

Volatile fatty acid production in anaerobic fermentation of food waste saccharified residue: Effect of substrate concentration - Qingyan Wang; Guangming Zhang; Le Chen; Nan Yang; Yan Wu; Wei Fang; Ru Zhang; Xinyi Wang; Chuan Fu; Panyue Zhang (Waste Management, 2023)

The effect of metformin and drinking water quality variation on haloacetamide formation during chlor(am)ination of acetaminophen - Ming-Chuan Ho; Ru-Ying Yang; Guan-Fu Chen; Wei-Hsiang Chen (Journal of Environmental Management, 2023)

Effects of microbial transglutaminase on the gelling property and in vitro digestibility of fish scale gelatin from grass carp - Yonggang Chen; Yuhang Wang; Ru Liu; Shanbai Xiong; Yan Xu; Yang Hu (Food Bioscience, 2023)

Active packaging coatings based on agarose caffeate: Preparation, characterisation, and application in grass carp (Ctenopharyngodon idellus) preservation - Liling Fu; Yi Ru; Qinglin Hong; Yonghui Zhang; Huifen Weng; Qiuming Yang; Qiong Xiao; Anfeng Xiao (Food Packaging and Shelf Life, 2023)

A micromechanical investigation of sand–rubber mixtures using the discrete element method - Ru Fu; Bo Yang; Xinli Hu; Bo Zhou; Matthew Richard Coop (Engineering Geology, 2023)

Polybenzimidazole-reinforced polyethylene oxide-based polymer-in-salt electrolytes enabling excellent structural stability and superior electrochemical performance for lithium metal batteries - Lei Zou; Kun Shi; Honglei Liu; Yong Wu; Tao Xu; Qiang Wang; Zhangxian Chen; Zeheng Yang; Ru Song; Jianhui Su; Weixin Zhang (Chemical Engineering Journal, 2023)

Molybdenum carbide changes the abundance of antibiotic resistance genes and bacterial communities in bioelectrocatalytic systems treating wastewater contaminated by tetracycline - Yi Shao; Yu-Xiang Lu; Shi-Ru Gao; Bolun Xie; Xiao-Li Yang; Hai-Liang Song (Bioresource Technology Reports, 2023)

Chemical constituents from Ajuga macrosperma Wall. ex Benth. (Lamiaceae) and their chemotaxonomic significance - Hua-Yi Jiang; Yi-Huan Li; Qian-Ru Zhang; Dan Teng; Ming-Ming Li; Rui Yang; Hong-Ping He (Biochemical Systematics and Ecology, 2023)

Ndufa4 Regulates the Proliferation and Apoptosis of Neurons via miR-145a-5p/Homer1/Ccnd2 - Fang Fu; Chen Chen; Kun Du; Lu-shan Li; Ru Li; Ting-ying Lei; Qiong Deng; Dan Wang; Qiu-xia Yu; Xin Yang; Jin Han; Min Pan; et al. (Molecular Neurobiology, 2023)
The Dandy–Walker malformation (DWM) is characterized by neuron dysregulation in embryonic development; however, the regulatory mechanisms associated with it are unclear. This study aimed to investigate the role of NADH dehydrogenase 1 alpha subcomplex 4 (NDUFA4) in regulating downstream signaling cascades and neuronal proliferation and apoptosis. Ndufa4 overexpression promoted the proliferation of neurons and inhibited their apoptosis in vitro, which underwent reverse regulation by the Ndufa4 short hairpin RNAs. Ndufa4 -knockout (KO) mice showed abnormal histological alterations in the brain tissue, in addition to impaired spatial learning capacity and exploratory activity. Ndufa4 depletion altered the microRNA expressional profiles of the cerebellum: Ndufa4 inhibited miR-145a-5p expression both in the cerebellum and neurons. miR-145a-5p inhibited the proliferation of neurons and promoted their apoptosis. Ndufa4 promoted and miR-145a-5p inhibited the expression of human homer protein homolog 1 and cyclin D2 in neurons. Thus, Ndufa4 promotes the proliferation of neurons and inhibits their apoptosis by inhibiting miR-145a-5p, which directly targets and inhibits the untranslated regions of Homer1 and Ccnd2 expression.

Prenatal diagnosis in the fetal hyperechogenic kidneys: assessment using chromosomal microarray analysis and exome sequencing - Ruibin Huang; Fang Fu; Hang Zhou; Lu Zhang; Tingying Lei; Ken Cheng; Shujuan Yan; Fei Guo; You Wang; Chunling Ma; Ru Li; Qiuxia Yu; et al. (Human Genetics, 2023)

Study on Mechanical Property of Coal-Rock Combination Under Different Unloading Confining Pressure Rate - Shanchao Hu; Xuedong Zhou; Wenkai Ru; Jinming Han; Shihao Guo; Chenxi Zhang; Lei Yang (Geotechnical and Geological Engineering, 2023)

Spatial–Temporal Variation and Health Risk Assessment of Fluoride in Surface Water in the Tibetan Plateau - Yi Yang; Ru Zhang; Fengying Zhang; Yonghua Li (Exposure and Health, 2023)

Numerical calculation method of steam-liquid separation efficiency of the corrugated plate dryer based on the discrete phase model and the Euler water film model: A short communication - Zhang Jiayi; Wang Mengyao; Wang Yang; Chao Zhiyang; Hu Shaochun; Chen Bowen; Wang Bo; Li Ru (Annals of Nuclear Energy, 2023)

NOS2/miR-493-5p Signaling Regulates in the LPS-Induced Inflammatory Response in the RAW264.7 Cells - Xiaofei Li; Yongrui Yang; Nihong Lu; Feng Luo; Ru Fan; Niancai Peng (Biochemical Genetics, 2023)

Automatic back analysis of mechanical parameters using block discrete element method and PSO algorithm - Hang-Sheng Ma; Huan-Ling Wang; Ru-Bin Wang; Qing-Xiang Meng; Lan-Lan Yang (European Journal of Environmental and Civil Engineering, 2023)

Metabolomics for in situ monitoring of attached Crassostrea gigas and Mytilus edulis: Effects of offshore wind farms on aquatic organisms - Ting Wang; Zhaoming Gao; Xiaoshang Ru; Xu Wang; Bo Yang; Libin Zhang (Marine Environmental Research, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

Comparison of the assembly behavior and structural characteristics of arachin and conarachin amyloid-like fibrils - Qin Yang; Ya-Ru Wang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Remediating flooding paddy soils with schwertmannite greatly reduced arsenic accumulation in rice (Oryza sativa L.) but did not decrease the utilization efficiency of P fertilizer - Ru Wang; Yinglin Guo; Yang Song; Yuting Guo; Xiaomeng Wang; Quan Yuan; Zengping Ning; Chengshuai Liu; Lixiang Zhou; Guanyu Zheng (Environmental Pollution, 2023)

Planning of takeoff/landing site location, dispatch route, and spraying route for a pesticide application helicopter - Fang Shuping; Ru Yu; Hu Chenming; Yang Fengbo (European Journal of Agronomy, 2023)

Flexible, biocompatible, degradable silk fibroin based display - Zijie Xu; Zhi He; Jiani Huang; Wu Qiu; Leo N.Y. Cao; Aniruddha Patil; Bo-Ru Yang; Xiang Yang Liu; Wenxi Guo (Chemical Engineering Journal, 2023)

Seasonal changes in diurnal rainfall over Sri Lanka and possible mechanisms - Wan-Ru Huang; Suranjith Bandara Koralegedara; Po-Han Tung; Tzu-Yang Chiang (Atmospheric Research, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Cloning, heterologous expression, and functional characterization of a hydroxyphenylpyruvate reductase (HPPR) gene involved in rosmarinic acid biosynthesis in Prunella vulgaris - Mei Ru; Liuyan Chen; Jiali Liu; Tingting Lan; Chuchu Yang; Xiaoyao Tan; Chuanmei Wu; Pan Liang; Zongsuo Liang (Plant Cell, Tissue and Organ Culture (PCTOC), 2023)

Multidimensional identification of single and regional meteorological drought considering flash‐season synthesis employed daily standardized effective precipitation and drought index in Guangxi, China - Yang Yun‐chuan; Yang Jia‐zhen; Tian Yi; Liao Li‐ping; Gan Ru‐min; Wang Wei‐quan; Wang Ting‐yan; Mo Chong‐xun; Li Xun‐gui; Sun Gui‐kai (International Journal of Climatology, 2023)
The frequent occurrence of extreme drought events in Guangxi has caused huge losses to human beings and economy in the region for many years. Therefore, this study adopted run theory and the objective identification method of regional extreme events (OITREE) and then carried out the comprehensive feature identification of multidimensional elements such as intensity, duration and area of meteorological drought events based on the daily standardized effective precipitation and drought index (SWAP) sequence of Guangxi from 1979 to 2018a. By comparing the evolutionary characteristics of drought elements identified by grid SWAP statistical analysis and OITREE, an integrated optimization scheme combining the accuracy of grid analysis and area identification is formed in this study. It was confirmed that the above two analysis methods had good correlation and consistency in revealing the evolution process of multidimensional elements of drought events. In terms of the frequency of drought events over a long period of time and the comprehensive characteristics of each element, the identification results of the OITREE method can better reveal the comprehensive characteristics of drought in Guangxi. Furthermore, the study found that flash droughts and seasonal droughts occurred alternately and were superimposed concurrently in Guangxi, and there were significant differences in the multidimensional spatial and temporal characteristics of these two types of droughts. Specifically, the frequency of flash drought was 1.60–4.00 times·(a) −1 , the duration varied from 20 to 60 days·(a) −1 and the concentration point of drought had a region‐wide dispersion; while the frequency of seasonal drought was 0.82–1.65 times·(a) −1 , the duration varied from 40–105 days·(a) −1 and the concentration point of drought had a local concentration. The research results can provide effective scientific support for operational drought refined forecast and early warning, and smart regulation of drought disaster risk.

mRNA 3ʹ -UTR-mediate translational control through PAS and CPE in sheep oocyte - Chun-Ru Song; Ru-Jing Zhang; Fang-Rui Xue; Xiao-Jie Zhang; Xing-Yue Wang; Dui Sun; Kang Ding; Qi Yang; Xin-Yu Wang; Cheng-Guang Liang (Theriogenology, 2023)

Mechanical properties of auxetic circular and square tubes filled with aluminum foam - Ru Yuan Huo; Dong Han; Yi Zhang; Wei Jiang; Le Yang Fan; Xin Wei Peng; Ge Chen Jie Shi; Ming Hao Chu; Xiang Yu Zhang; Yi Min Xie; Xin Ren (Engineering Structures, 2023)

A Cre knockin mouse reveals specific expression of Agouti gene in mesenchymal lineage cells in multiple organs and provides a unique tool for conditional gene targeting - Xing-Ru Shen; He-Li Zhang; Xu-Bo Zhao; Yang-Ge Wang; Xiao-Yang Tan; Lipeng Gao; Ruilin Sun; Xin-Hua Liao (Transgenic Research, 2023)

An in-situ strategy to construct uracil-conjugated covalent organic frameworks with tunable fluorescence/recognition characteristics for sensitive and selective Mercury(II) detection - Xi-Rui Deng; A-Wei Hu; Sheng-Qian Hu; Wen-Li Yang; Chen Sun; Sai-Jin Xiao; Gui-Ping Yang; Qiong-Qing Zheng; Ru-Ping Liang; Li Zhang; Jian-Ding Qiu (Analytica Chimica Acta, 2023)

Efficient coupling of sulfadiazine removal with microalgae lipid production in a membrane photobioreactor - Feng Gao; Jin-Long Zhou; Yu-Ru Zhang; Ashiwin Vadiveloo; Qing-Guo Chen; Jun-Zhi Liu; Qiao Yang; Ya-Ming Ge (Chemosphere, 2023)

Characterization of microbial community, ecological functions and antibiotic resistance in estuarine plastisphere - Le-Yang Yang; Xin-Rong Huang; Roy Neilson; Shu-Yi-Dan Zhou; Zhao-Lei Li; Xiao-Ru Yang; Xiao-Xuan Su (Science of The Total Environment, 2023)

Plant identity shapes phyllosphere microbiome structure and abundance of genes involved in nutrient cycling - Jian Li; Ming-Kang Jin; Roy Neilson; Shi-Lin Hu; Yi-Jia Tang; Zhao Zhang; Fu-Yi Huang; Jing Zhang; Xiao-Ru Yang (Science of The Total Environment, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Direct emissions of particulate glyoxal and methylglyoxal from biomass burning and coal combustion - Ting Wang; Ru-Jin Huang; Lu Yang; Wenting Dai; Haiyan Ni; Yuquan Gong; Jie Guo; Haobin Zhong; Chunshui Lin; Wei Xu (Science of The Total Environment, 2023)

Managing straw and nitrogen fertilizer based on nitrate threshold for balancing nitrogen requirement of maize and nitrate residue - Ru Guo; Rui Qian; Fei Han; Abdul Khaliq; Sadam Hussain; Ling Yang; Peng Zhang; Xiaoli Chen; Xiaolong Ren (Journal of Environmental Management, 2023)

Effects of dual succinylation and ultrasonication modification on the structural and functional properties of ovalbumin - Ru-yi Zhang; Yang Wang; Yi Jiang; Er-hu Min; Sheng-qi Rao (Food Research International, 2023)

Chitosan can improve the storage stability of ovalbumin fibrils at pH higher than isoelectric point - Ya-Ru Wang; Qin Yang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Chronic exposure to di(2-ethylhexyl) phthalate (DEHP) weakens innate immunity and leads to immunosenescence in C. elegans - Pei-Ling Yen; Cai-Ru Yang; Mei-Lun Huang; Ting-An Lin; Vivian Hsiu-Chuan Liao (Environmental Toxicology and Pharmacology, 2023)

Self-oxidation cycle of oxidized red phosphorus for regeneration of binding sites enables efficient uranium extraction in tributylphosphate-kerosene system - Yingtong Lv; Ru Cheng; Guolin Yang; Wang Liu; Jingye Zhang; Xiaofang Yu; Wencai Bai; Rong He; Wenkun Zhu (Chemical Engineering Journal, 2023)

P2Y1R and P2Y2R: potential molecular triggers in muscle regeneration - Min-Jia Wang; Bi-Ru Yang; Xin-Yu Jing; Yao-Zheng Wang; Lu Kang; Kai Ren; Liang Kang (Purinergic Signalling, 2023)
Muscle regeneration is indispensable for skeletal muscle health and daily life when injury, muscular disease, and aging occur. Among the muscle regeneration, muscle stem cells’ (MuSCs) activation, proliferation, and differentiation play a key role in muscle regeneration. Purines bind to its specific receptors during muscle development, which transmit environmental stimuli and play a crucial role of modulator of muscle regeneration. Evidences proved P2R expression during development and regeneration of skeletal muscle, both in human and mouse. In contrast to P2XR, which have been extensively investigated in skeletal muscles, the knowledge of P2YR in this tissue is less comprehensive. This review summarized muscle regeneration via P2Y1R and P2Y2R and speculated that P2Y1R and P2Y2R might be potential molecular triggers for MuSCs’ activation and proliferation via the p-ERK1/2 and PLC pathways, explored their cascade effects on skeletal muscle, and proposed P2Y1/2 receptors as potential pharmacological targets in muscle regeneration, to advance the purinergic signaling within muscle and provide promising strategies for alleviating muscular disease.

Nitrogen Modulates the Effects of Heat, Drought, and Combined Stresses on Photosynthesis, Antioxidant Capacity, Cell Osmoregulation, and Grain Yield in Winter Wheat - Chen Ru; Kaifei Wang; Xiaotao Hu; Dianyu Chen; Wene Wang; Haosheng Yang (Journal of Plant Growth Regulation, 2023)

Inhibition of perilipin 2 attenuates cerebral ischemia/reperfusion injury by blocking NLRP3 inflammasome activation both in vivo and in vitro - Xu-Ying Liu; Qiu-Shi Li; Wen-Hai Yang; Yue Qiu; Fei-Fei Zhang; Xiu-Hui Mei; Qi-Wen Yuan; Ru-Bo Sui (In Vitro Cellular & Developmental Biology - Animal, 2023)

Whole exome sequencing improves genetic diagnosis of fetal clubfoot - Ruibin Huang; Hang Zhou; Chunling Ma; Fang Fu; Ken Cheng; You Wang; Ru Li; Tingying Lei; Qiuxia Yu; Dan Wang; Shujuan Yan; Xin Yang; et al. (Human Genetics, 2023)

Parameter optimization of coal face blasting for coal and gas outburst control - Wei Yang; Wenyuan Wang; Ru Jia; Gabriel Walton; Sankhaneel Sinha; Qinghe Chen; Baiquan Lin; Xiangdong Jiao (Bulletin of Engineering Geology and the Environment, 2023)

Effect of phenol formaldehyde-associated microplastics on soil microbial community, assembly, and functioning - Hu Li; Qiu-Ping Luo; Sha Zhao; Yan-Yan Zhou; Fu-Yi Huang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

Heat-induced arachin and basil seed gum composite gels improved by NaCl and microbial transglutaminase: Gelling properties and structure - Qin Yang; Ya-Ru Wang; Ya-Nan Du; Han-Qing Chen (Food Hydrocolloids, 2023)

Influence mechanisms of different setting time at low temperature on the gel quality and protein structure of Solenocera crassicornis surimi - Jingjing Tong; Ru Jia; Geran Xia; Xinxin Zhang; Shutong Zhang; Huamao Wei; Wenge Yang (Food Bioscience, 2023)

Bisphenol S disrupts opsins gene expression and impairs the light-sensing function via antagonizing TH-TRβ signaling pathway in zebrafish larvae - Shuhui Wei; Liguo Qiu; Shaoguo Ru; Yang Yang; Jun Wang; Xiaona Zhang (Food and Chemical Toxicology, 2023)

Precision nitrogen management regimes to obtain high yield and good eating quality of medium indica hybrid rice in mechanical transplanting with bowl-type nursery tray (MTB) based on the critical nitrogen concentration - Haibing He; Kun Yang; Haochong Xu; Bo Yao; Ganghua Li; Xuenan Zhang; Ru Yang; Cuicui You; Jian Ke; Liquan Wu (European Journal of Agronomy, 2023)

Intracellularly-photosensitized bio-hybrid with biogenic quantum dots for enhanced wastewater denitrification - Shuo Cui; Yang Si; Xian-Zhong Fu; Hui-Hui Li; Xue-Meng Wang; Wen-Zheng Du; Lang Teng; Ru-Li He; Hou-Qi Liu; Ruquan Ye; Wen-Wei Li (Chemical Engineering Journal, 2023)

Treatment of heavy metal ions-polluted water into drinkable water: Capture and recovery of Pb2+ by cellulose@CaCO3 bio-composite filter via spatial confinement effect - He-Xiang Zhao; Yan Wang; Jun-Jie Yang; Ji-Guo Zhang; Yuan-Ru Guo; Shujun Li; Qing-Jiang Pan (Chemical Engineering Journal, 2023)

Surface wrinkles enhancing electromagnetic interference shielding of copper coated polydimethylsiloxane: A simulation and experimental study - Qian-Ming He; Jun-Ru Tao; Dian Yang; Yi Yang; Ming Wang (Chemical Engineering Journal, 2023)

Heterogeneous Fenton for Removal Rhodamine-B by Iron-bearing Attapulgite Granular Catalysts - Peiguo Zhou; Wenjing Yang; Tianyu Lu; Xin Ru; Zongbiao Dai; Meshack Appiah Ofori; Jiaxin Hou (Water, Air, & Soil Pollution, 2023)

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Temporal dynamics of soil bacterial network regulate soil resistomes - Qian Xiang; Dong Zhu; Min Qiao; Xiao‐Ru Yang; Gang Li; Qing‐Lin Chen; Yong‐Guan Zhu (Environmental Microbiology, 2023)
Soil bacteria are diverse and form complicated ecological networks through various microbial interactions, which play important roles in soil multi‐functionality. However, the seasonal effects on the bacterial network, especially the relationship between bacterial network topological features and soil resistomes remains underexplored, which impedes our ability to unveil the mechanisms of the temporal‐dynamics of antibiotic resistance genes (ARGs). Here, a field investigation was conducted across four seasons at the watershed scale. We observed significant seasonal variation in bacterial networks, with lower complexity and stability in autumn, and a wider bacterial community niche in summer. Similar to bacterial communities, the co‐occurrence networks among ARGs also shift with seasonal change, particularly with respect to the topological features of the node degree, which on average was higher in summer than in the other seasons. Furthermore, the nodes with higher betweenness, stress, degree, and closeness centrality in the bacterial network showed strong relationships with the 10 major classes of ARGs. These findings highlighted the changes in the topological properties of bacterial networks that could further alter antibiotic resistance in soil. Together, our results reveal the temporal dynamics of bacterial ecological networks at the watershed scale, and provide new insights into antibiotic resistance management under environmental changes.

Combined effect of Cu- and ZnO- NPs on antibiotic resistance genes in an estuarine water - Yu-ru Chen; Rong-rong Sha; Xiao-li Sun; Xing-pan Guo; Yi Yang (Frontiers in Marine Science, 2023)
Most studies of whether and how nanoparticles (NPs) affect antibiotic resistance genes (ARGs) focus on testing single NPs type. In this study, we determined the combined effect of Cu- and ZnO- NPs in the water samples collected from the Yangtze River Estuary and found the effect differs greatly from that produced by individual NPs. The results showed that the Cu- and ZnO- NPs co-exposure resulted in an enrichment of ARGs, whereas individual Cu- and ZnO- NPs exposure decreased the abundance of ARGs. Furthermore, the co-exposure of Cu- and ZnO- NPs induced obvious changes in the microbial communities compared to the control communities. Redundancy analysis suggested that the microbial community contributed the most (43.5%) to the ARG profiles, followed by dissolved metal ions (25.7%), MRGs, (19.4%), and MGEs (4.4%). Network analysis found several potential hosts (such as Mycobacterium and Escherichia coli ) and implied the extent of the risk of ARG transmission into various environmental niches by these common microbes.

Identification of mercury species in coal combustion by-products from power plants using thermal desorption-atomic fluorescence spectrometry on-line coupling system - Kai-Qiang He; Xiao-Ru Zhang; Yuan-Peng Li; Xue-Lei Duan; Yan Li; Yang-Hong Jiang; Xiao-Dong Yuan; Ke-Gang Zhang; Chun-Gang Yuan (Chemosphere, 2023)

Examination of sex-related differences in intestinal and gonadal lipid metabolism in the sea cucumber Apostichopus japonicus - Shuangyan Zhang; Xiaoshang Ru; Libin Zhang; David Gonçalves; Hongsheng Yang (Aquaculture, 2023)

Evidence that offshore wind farms might affect marine sediment quality and microbial communities - Ting Wang; Xiaoshang Ru; Beini Deng; Chenxi Zhang; Xu Wang; Bo Yang; Libin Zhang (Science of The Total Environment, 2023)

Water–energy–carbon synergies and trade-offs: A daily nexus analysis for wastewater treatment plants - Xiaojing Ni; Xiangfeng Huang; Ru Guo; Jinhui Wang; Kaiming Peng; Wei Zhang; Yuyu Zhu; Weilan Yang; Liya Wang; Chen Cai; Jia Liu; Erwu Liu (Resources, Conservation and Recycling, 2023)

Transcriptomic analyses of carvone inhibited sprouting in sweet potato (Ipomoea batatas (L.) Lam cv ‘Yan 25′) storage roots - Shuxian Geng; Zihan Liu; John B. Golding; Penta Pristijono; Zunfu Lv; Guoquan Lu; Huqing Yang; Lei Ru; Yongxin Li (Postharvest Biology and Technology, 2023)

Insights into the influence on 2,4,6-trichlorophenol microbial reductive dechlorination process by exposure to microplastics - Jia-Qi Yang; Zhi-Ling Li; Bin Wu; Ya-Ru Jin; Di Cao; Jun Nan; Xue-Qi Chen; Wen-Zong Liu; Shu-Hong Gao; Ai-Jie Wang (Journal of Hazardous Materials, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Mechanism of bisphenol S exposure on color sensitivity of zebrafish larvae - Liguo Qiu; Shuhui Wei; Yixin Yang; Rui Zhang; Shaoguo Ru; Xiaona Zhang (Environmental Pollution, 2023)

Air pollution, greenness and risk of overweight among middle-aged and older adults: A cohort study in China - Wenxing Han; Zhihu Xu; Xin Hu; Ru Cao; Yuxin Wang; Jianbo Jin; Jiawei Wang; Teng Yang; Qiang Zeng; Jing Huang; Guoxing Li (Environmental Research, 2023)

Dynamic roles of inner membrane electron-transfer hub of Shewanella oneidensis MR-1 in response to extracellular reduction kinetics - Xiang Xiao; Chang-Xing Li; Jie-Ru Peng; Yang-Yang Fan; Wen-Wei Li (Chemical Engineering Journal, 2023)

Clustered regularly interspaced short palindromic repeats (CRISPR) technology and genetic engineering strategies for microalgae towards carbon neutrality: A critical review - Tse-Min Lee; Jia-Yi Lin; Tsung-Han Tsai; Ru-Yin Yang; I-Son Ng (Bioresource Technology, 2023)

Efficient microalgal lipid production driven by salt stress and phytohormones synergistically - Zi-Yan Yang; Kai-Xuan Huang; Yu-Ru Zhang; Lei Yang; Jin-Long Zhou; Qiao Yang; Feng Gao (Bioresource Technology, 2023)

Herbicide prometryn adversely affects the development and reproduction of Tigriopus japonicus by disturbing the ecdysone signal pathway and chitin metabolic pathway - Dong Wang; Guangxin Yang; Shaoguo Ru; Zhenzhong Zhang; Yuejiao Li; Jun Wang (Aquatic Toxicology, 2023)

Transcriptome‐based analyses of adaptive divergence between two closely related spruce species on the Qinghai–Tibet plateau and adjacent regions - Shuo Feng; Wei Wan; Yang Li; DongLei Wang; Guangpeng Ren; Tao Ma; Dafu Ru (Molecular Ecology, 2023)
Speciation among populations connected by gene flow is driven by adaptation to different environments, but underlying gene–environment associations remain largely unknown. Here, 162 individuals from 32 populations were sampled to obtain 191,648 independent single nucleotide polymorphisms (SNPs) across the genomes of two closely related spruce species, Picea asperata and Picea crassifolia , which occur on the Qinghai–Tibet Plateau and in surrounding regions. Using the SNP data set, genotype–environment associations and demographic modelling were used to examine local adaptation and genetic divergence between these two species. While morphologically similar, the two Picea species were genetically differentiated in multiple analyses. These species diverged despite continuous gene flow, and their initial divergence was dated back to the late Quaternary. The effective population sizes of both species have expanded since their divergence, as confirmed by niche distribution simulations. A total of 6365 genes were associated with the tested environmental variables; of these, 41 were positively selected in P. asperata and were mainly associated with temperature, while 83 were positively selected in P. crassifolia and were primarily associated with precipitation. These results deepen our understanding of the adaptive divergence and demographic histories of these two spruce species and highlight the importance of genomic data in deciphering the environmental selection underlying Quaternary interspecific divergence.

Lipocalin-2-Mediated Insufficient Oligodendrocyte Progenitor Cell Remyelination for White Matter Injury After Subarachnoid Hemorrhage via SCL22A17 Receptor/Early Growth Response Protein 1 Signaling - Qiang Li; Xufang Ru; Yang Yang; Hengli Zhao; Jie Qu; Weixiang Chen; Pengyu Pan; Huaizhen Ruan; Chaojun Li; Yujie Chen; Hua Feng (Neuroscience Bulletin, 2022)
Insufficient remyelination due to impaired oligodendrocyte precursor cell (OPC) differentiation and maturation is strongly associated with irreversible white matter injury (WMI) and neurological deficits. We analyzed whole transcriptome expression to elucidate the potential role and underlying mechanism of action of lipocalin-2 (LCN2) in OPC differentiation and WMI and identified the receptor SCL22A17 and downstream transcription factor early growth response protein 1 (EGR1) as the key signals contributing to LCN2-mediated insufficient OPC remyelination. In LCN-knockdown and OPC EGR1 conditional-knockout mice, we discovered enhanced OPC differentiation in developing and injured white matter (WM); consistent with this, the specific inactivation of LCN2/SCl22A17/EGR1 signaling promoted remyelination and neurological recovery in both atypical, acute WMI due to subarachnoid hemorrhage and typical, chronic WMI due to multiple sclerosis. This potentially represents a novel strategy to enhance differentiation and remyelination in patients with white matter injury.

Interactive Effects of Maize Straw-Derived Biochar and N Fertilization on Soil Bulk Density and Porosity, Maize Productivity and Nitrogen Use Efficiency in Arid Areas - Ru Guo; Rui Qian; Ling Yang; Abdul Khaliq; Fei Han; Sadam Hussain; Peng Zhang; Tie Cai; Zhikuan Jia; Xiaoli Chen; Xiaolong Ren (Journal of Soil Science and Plant Nutrition, 2022)

Identification and bioinformatic analysis of the CaCesA/Csls family members and the expression of the CaCslD1 in the flower buds of CMS/Rf system in pepper - Panpan Duan; Min Wei; Ru Zhang; Shufang Zhao; Yongfu Wang; Bingdiao Gou; Nan Yang; Tao Zhang; Gaoyuan Zhang; Bingqiang Wei (Functional & Integrative Genomics, 2022)

Nitrogen enrichment alters multiple dimensions of grassland functional stability via changing compositional stability - Qianna Xu; Xian Yang; Jian Song; Jingyi Ru; Jianyang Xia; Shaopeng Wang; Shiqiang Wan; Lin Jiang (Ecology Letters, 2022)
Anthropogenic nutrient enrichment is known to alter the composition and functioning of plant communities. However, how nutrient enrichment influences multiple dimensions of community‐ and ecosystem‐level stability remains poorly understood. Using data from a nitrogen (N) and phosphorus (P) addition experiment in a temperate semi‐arid grassland that experienced a natural drought, we show that N enrichment, not P enrichment, decreased grassland functional and compositional temporal stability, resistance and recovery but increased functional and compositional resilience. Compositional stability and species asynchrony, rather than species diversity, were identified as key determinants of all dimensions of grassland functional stability, except for recovery. Whereas grassland functional recovery was decoupled from compositional recovery, N enrichment altered other dimensions of functional stability primarily through changing their corresponding compositional stability dimensions. Our findings highlight the need to examine ecological stability at the community level for a more mechanistic understanding of ecosystem dynamics in the face of environmental change.

Recent advances in biotechnological production of polyunsaturated fatty acids by Yarrowia lipolytica - Yu-Lei Jia; Ling-Ru Wang; Zi-Xu Zhang; Yang Gu; Xiao-Man Sun (Critical Reviews in Food Science and Nutrition, 2022)

PITPNC1 promotes the thermogenesis of brown adipose tissue under acute cold exposure - Guoqing Tang; Chengxin Ma; Liangkui Li; Shaoyan Zhang; Fengsheng Li; Jin Wu; Yesheng Yin; Qing Zhu; Yan Liang; Ru Wang; He Huang; Tong-Jin Zhao; et al. (Science China Life Sciences, 2022)
Brown adipose tissue (BAT) plays an essential role in non-shivering thermogenesis. The phosphatidylinositol transfer protein, cytoplasmic 1 (PITPNC1) is identified as a lipid transporter that reciprocally transfers phospholipids between intracellular membrane structures. However, the physiological significance of PITPNC1 and its regulatory mechanism remain unclear. Here, we demonstrate that PITPNC1 is a key player in thermogenesis of BAT. While Pitpnc1 −/− mice do not differ with wildtype mice in body weight and insulin sensitivity on either chow or high-fat diet, they develop hypothermia when subjected to acute cold exposure at 4°C. The Pitpnc1 −/− brown adipocytes exhibit defective β-oxidation and abnormal thermogenesis-related metabolism pathways in mitochondria. The deficiency of lipid mobilization in Pitpnc1 −/− brown adipocytes might be the result of excessive accumulation of phosphatidylcholine and a reduction of phosphatidic acid. Our findings have uncovered significant roles of PITPNC1 in mitochondrial phospholipid homeostasis and BAT thermogenesis.

Bio-electrocatalytic degradation of tetracycline by stainless-steel mesh based molybdenum carbide electrode - Zhi-Hao Zhang; Jia-Ying Xu; Tao Li; Shi-Ru Gao; Xiao-Li Yang (Environmental Science and Pollution Research, 2022)

Complete genome sequence of Aconitum amalgavirus 1, a distinct member of the genus Amalgavirus - Jie Yang; Ping-Xiu Lan; Jin-Ming Li; Xiao-Jiao Chen; Guan-Lin Tan; Tai-Yun Wei; Ru-Hui Li; Fan Li (Archives of Virology, 2022)

A UAV-aided prediction system of soil moisture content relying on thermal infrared remote sensing - W. Li; C. Liu; Y. Yang; M. Awais; W. Li; P. Ying; W. Ru; M. J. M. Cheema (International Journal of Environmental Science and Technology, 2022)

Discovery of the oncogenic MDM2, a direct binding target of berberine and a potential therapeutic, in multiple myeloma - Chuting Li; Ru Su; Xiuyuan Wang; Guiping Huang; Yanjun Liu; Juhua Yang; Zhao Yin; Chunming Gu; Jia Fei (Functional & Integrative Genomics, 2022)

Deletions in GSN gene associated with growth traits of four Chinese cattle breeds - Ao Qi; Wenxiu Ru; Yangkai Liu; Yu Yang; Jia Tang; Haiyan Yang; Shuling Yang; Kaixing Qu; Xianyong Lan; Chuzhao Lei; Bizhi Huang; Hong Chen (Molecular Genetics and Genomics, 2022)

Vibrio salinus sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll in the western Pacific Ocean - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2022)

Spectral Kinetic-Energy Fluxes in the North Pacific: Definition Comparison and Normal- and Shear-Strain Decomposition - Yi Yang; Ru Chen (Journal of Marine Science and Engineering, 2022)
The spectral kinetic-energy flux is an effective tool to analyze the kinetic-energy transfer across a range of length scales, also known as the kinetic-energy cascade. Three methods to calculate spectral energy fluxes have been widely used, hereafter the ΠA, ΠF, and ΠQ definitions. However, the relations among these three definitions have not been examined in detail. Moreover, the respective contribution of the normal strain and shear strain of the flow field to kinetic-energy cascade has not been estimated before. Here, we use the kinetic energy equations to rigorously compare these definitions. Then, we evaluate the spectral energy fluxes, as well as its decomposition into the normal-strain and shear-strain components for the North Pacific, using a dynamically consistent global eddying state estimate. We find that the data must be preprocessed first to obtain stable results from the ΠF and ΠQ definitions, but not for the ΠA definition. For the upper 500 m of the North Pacific, in the wavenumber ranges with inverse kinetic-energy cascade, both the normal and shear-strain flow components contribute significantly to the spectral energy fluxes. However, at high wavenumbers, the dominant contributor to forward kinetic-energy cascade is the normal-strain component. These results should help shed light on the underlying mechanism of inverse and forward energy cascades.

The correlation of fibrinogen-like protein-1 expression with the progression and prognosis of hepatocellular carcinoma - Nanni Hua; Anxian Chen; Chen Yang; Hui Dong; Xianglei He; Guoqing Ru; Xiangmin Tong; Feifei Zhou; Shibing Wang (Molecular Biology Reports, 2022)
Background Fibrinogen-like-protein 1 (FGL1), a member of the fibrinogen-related protein (FREP) family, is a major ligand of the immune inhibitory receptor lymphocyte-activation gene 3 (LAG-3). While FGL1 is strongly implicated in the development and prognosis of a variety of diseases, its role in hepatocellular carcinoma (HCC) is still disputed. Therefore, the role of FGL1 expression in the progression and prognosis of HCC was investigated. Methods and results In the present study, bioinformatics analysis was first used to probe the expression profile of FGL1 in multiple malignant tumor tissues and paired normal tissues, and to explore the possible relationship between FGL1 and prognosis of HCC patients. Thereafter, the expression levels of FGL1 were determined and compared in human HCC cell lines, HCC tissues, peri-tumor tissues and normal liver tissues by western blot analysis. Furthermore, tissue microarrays were used to detect the expression of FGL1 through immunohistochemical staining and to verify whether the FGL1 expression level was associated with clinicopathological features and the prognosis of HCC patients. The results showed that FGL1 was downregulated significantly in most of the HCC cells lines and HCC tissues, corresponding to the results of the bioinformatics and western blot analyses. FGL1 expression level in HCC was found to be correlated to Edmondson grade and metastasis of the HCC. Additionally, high FGL1 expression was associated with better overall survival in HCC patients, suggesting that FGL1 could function as a tumor suppressor. Conclusions The expression level of FGL1 can be correlated with the progression and prognosis of HCC, suggesting its potential as a prognostic biomarker.

LncRNA ZNF883-Mediated NLRP3 Inflammasome Activation and Epilepsy Development Involve USP47 Upregulation - Lina Gong; Yaru Han; Ru Chen; Pu Yang; Chen Zhang (Molecular Neurobiology, 2022)

Traffic noise and adiposity: a systematic review and meta-analysis of epidemiological studies - Si-Yu Gui; Ke-Jia Wu; Yue Sun; Yue-Nan Chen; Huan-Ru Liang; Wen Liu; Yao Lu; Cheng-Yang Hu (Environmental Science and Pollution Research, 2022)

Lelliottia steviae sp. nov. isolated from Stevia rebaudiana Bertoni - Jing Lin; Ke Huang; Jing-Yu Huang; Yuan-Ru Xiong; Meng-Meng Wei; Na Xiao; Jia Gao; Xuan-Kai Ding; Zi-Yang Ma; Jun-Hao Sang; Ling-Xian Kong; Zhi-Yun Hong; et al. (Archives of Microbiology, 2022)

Spatiotemporal variations of seasonal temperature at different percentiles in the three provinces of northeast China from 1961 to 2019 - Yaxue Yang; Huixiao Wang; Changming Liu; Ru Feng; Yu Wang; Hongfang Li (International Journal of Climatology, 2022)
The three provinces of northeast China (NEPs) were one of the major grain producing areas in China and has undergone significant climate warming during past decades. However, nowadays researches on climate warming mostly focused on variations of mean temperature or temperature extremes, which missed much information in the other parts of temperature. Therefore, taken NEPs as study area, variations of maximum temperature (Tmax), minimum temperature (Tmin) and diurnal temperature range (DTR) at every 10% percentile from 1961 to 2019 in NEPs were analysed at seasonal scale. The abrupt changes and decadal shifts of Tmax, Tmin and DTR at different percentiles were further highlighted. Results show that (a) for either regional average or station cases, fluctuations of daily Tmax and daily Tmin both decreased in spring and winter, but increased in autumn. In summer, fluctuations of daily Tmin decreased while those of daily Tmax increased. (b) Spatially, Tmax heated up more in south of NEPs at lower percentiles, and in northwest of NEPs at higher percentiles in spring, summer and winter. Tmin and DTR overall showed consistent spatial differences that changes in north and northwest of NEPs were with greater magnitudes. (c) In spring and winter, the higher Tmax/Tmin had earlier abrupt changes than lower Tmax/Tmin, while in summer and autumn, the abrupt changes occurred earlier for lower Tmax/Tmin. (d) In winter, overwhelming positive shifts were significant before 2000, but turned negative after 2000. In summer, Tmax heated up quickly since 1990s and Tmin since 1980s. Shifts in spring and autumn varied during different periods and generally presented alternative warming at higher and lower percentiles. The research can help better depict the warming patterns and figure out the detailed warming procedures in NEPs, which is a strong supplement for current climate change research.

miR-211-3p enhances induction chemotherapy insensitivity by upregulating CSF2/CCL20/TNF signaling in hypopharyngeal squamous cell carcinoma - Lingwa Wang; Ru Wang; Tianqiao Huang; Yifan Yang; Ling Feng; Jugao Fang (Molecular Biology Reports, 2022)

Dataset-based assessment of heavy metal contamination in freshwater fishes and their health risks - Xiao-Bo Liu; Congtian Lin; Yang-Yu Wu; Hai-Ning Huang; Li-Ting Zhu; Ru Jiang; Qiansheng Huang (Environmental Science and Pollution Research, 2022)

High Levels of 25-OH-Vitamin D and Copper in Pregnant Women with Abnormal Glucose Challenge Test - Chien-Hua Chiang; Wan-Ju Kung; Chien-Hung Lee; Yeong-Hwa Zen; Cheng-Fa Lee; Hui-Ru Yang; Ching-Chiang Lin; Yeou-Lih Huang (Biological Trace Element Research, 2022)

Analyzing the mechanism of nitrous oxide production in aerobic phase of anoxic/aerobic sequential batch reactor from the perspective of key enzymes - Rui Yang; Lin-jiang Yuan; Ru Wang; Zhi-xian He; Lin Lei; Yan-chen Ma (Environmental Science and Pollution Research, 2022)

The genetic engineering of glycine betaine synthesis in tobacco improves the resistance of the photosynthetic apparatus to drought stress - Gui-Ping Wang; Xiao-Min Xue; Xing-hong Yang; Ru Chen; Xue-Ping Han (Plant Biotechnology Reports, 2022)

Moisture mediates temperature-growth couplings of high-elevation shrubs in the Tibetan plateau - Yang Han; Yafeng Wang; Bo Liu; Ru Huang; J. Julio Camarero (Trees, 2022)

circSVIL regulates bovine myoblast development by inhibiting STAT1 phosphorylation - Binglin Yue; Haiyan Yang; Jiyao Wu; Jian Wang; Wenxiu Ru; Jie Cheng; Yongzheng Huang; Xianyong Lan; Chuzhao Lei; Hong Chen (Science China Life Sciences, 2022)

NNMT is induced dynamically during beige adipogenesis in adipose tissues depot-specific manner - Ru Jia; Xiaojing Wei; Jianan Jiang; Zhao Yang; Jiaqi Huang; Jing Liu; Jianqun Yan; Xiao Luo (Journal of Physiology and Biochemistry, 2022)

Damage characterization of shale under uniaxial compression by acoustic emission monitoring - Huijun Lu; Ru Zhang; Li Ren; Anlin Zhang; Yiming Yang; Xiaopeng Li (Frontiers of Earth Science, 2021)

Identification and antimicrobial properties of a new alkaloid produced by marine-derived Verrucosispora sp. FIM06-0036 - Ming-Hong Chen; Yun-Yang Lian; Dong-Sheng Fang; Li Chen; Jia Jia; Wen-Long Zhang; Ru Lin; Yang Xie; Hong-Kai Bi; Hong Jiang (Natural Product Research, 2021)

Evolutionary origin of a tetraploid Allium species on the Qinghai–Tibet Plateau - Minjie Li; Zeyu Zheng; Juncheng Liu; Yongzhi Yang; Guangpeng Ren; Dafu Ru; Shangzhe Zhang; Xin Du; Tao Ma; Richard Milne; Jianquan Liu (Molecular Ecology, 2021)
Extinct taxa may be detectable if they were ancestors to extant hybrid species, which retain their genetic signature. In this study, we combined phylogenomics, population genetics and fluorescence in situ hybridization (GISH and FISH) analyses to trace the origin of the alpine tetraploid Allium tetraploideum (2 n = 4 x = 32), one of the five known members in the subgenus Cyathophora . We found that A. tetraploideum was an obvious allotetrapoploid derived from ancestors including at least two closely related diploid species, A. farreri and A. cyathophorum , from which it differs by multiple ecological and genomic attributes. However, these two species cannot account for the full genome of A. tetraploideum , indicating that at least one extinct diploid is also involved in its ancestry. Furthermore, A. tetraploideum appears to have arisen via homoploid hybrid speciation (HHS) from two extinct allotetraploid parents, which derived in turn from the aforementioned diploids. Other modes of origin were possible, but all were even more complex and involved additional extinct ancestors. Our study together highlights how some polyploid species might have very complex origins, involving both HHS and polyploid speciation and also extinct ancestors.

Plasticity of Locomotor Activity Permits Energy Homeostasis During Reproduction in a Female Sea Cucumber - Xiaoshang Ru; Libin Zhang; Hongsheng Yang (Frontiers in Marine Science, 2021)
Behavioral plasticity in animals allows for moment-by-moment behavioral adjustments to biotic and abiotic uncertainties in the environment. For most aquatic animals, reproduction involves gonadal development and other physiological changes, causing increasing demands in nutrients and energy for females. The aim of this report was to determine how the female sea cucumber, Apostichopus japonicus , accommodates increasing energy demands during reproduction by adopting a behavioral energy conservation strategy. Dynamic changes in feeding activity, total body mass, locomotor activity, energetic condition, and metabolic performance of the females were measured from the non-breeding stage up to the mature stage. Routine metabolic rate analysis showed that reproduction caused a significant increase in energy demands in the adult. However, reproduction also suppressed the appetite of adults resulting in decreased energy intake. Interestingly, combining time-lapse camera and behavioral analysis software, the results showed that sea cucumbers down-regulated their locomotor activities in order to conserve energy effectively. Energy budget analysis and unchanged cortisol level revealed that the reduction in motility offset the increased energy demand for reproduction while helping to maintain energy homeostasis in the maternal body. Altogether, our study suggests that plasticity in the locomotor behavior allows sea cucumbers to cope with the high energy demands of reproduction.

Pleosporalins H and I, two new heptaketides from the endophytic fungus Pleosporales sp. F46 by using OSMAC strategy - Hong-Xia Yang; Xiao-Ping Peng; Han Gao; Hui-Min Zhang; Zi-Ru Wang; Gang Li; Hong-Xiang Lou (Natural Product Research, 2021)

Sensitization to Airborne Fungal Allergens Associates with Asthma and Allergic Rhinitis Presentation and Severity in the Singaporean/Malaysian Population - Yang Yie Sio; Sze Lei Pang; Yee-How Say; Keng Foo Teh; Yi Ru Wong; Smyrna Moti Rawanan Shah; Kavita Reginald; Fook Tim Chew (Mycopathologia, 2021)
Fungal spores and conidia are the major components of total airspora in the tropical Asia environment, and their sensitization patterns are often associated with allergic diseases such as asthma, allergic rhinitis (AR), and atopic dermatitis. Hence, we recruited a cross-sectional cohort of 9223 Singapore/Malaysia Chinese adults and assessed their sensitization against Curvularia lunata allergen using the skin prick test approach. A subset of this cohort ( n = 254) was also screened for specific Immunoglobulin E (sIgE) titers against a panel of 11 fungal allergens. We found significant association of Curvularia lunata sensitization with the risk of asthma (OR = 1.66, 95% CI: 1.17–2.33 ; p = 0.00391) and AR (OR = 1.69, 95% CI: 1.18–2.41; p = 0.00396). Among asthmatic patients ( n = 1680), Curvularia lunata sensitization also increased frequencies of wheezing symptoms (OR = 1.81, 95% CI: 1.05–2.96; p = 0.0239), general practitioner/specialist visits (OR = 2.37, 95% CI: 1.13–4.61; p = 0.0157), and other asthma-related exacerbation events (OR = 2.14, 95% CI: 1.04–4.10; p = 0.0289). In our serum cohort, sensitization to Aspergillus spp. was the most common fungal sensitization, with 23.6% ( n = 60) had a class 3 and above sensitization (positive sensitization; sIgE titers of > 3.5 kU/L) against this allergen. Increasing sIgE titer against Aspergillus spp. was also correlated with increased AR risk and AR-related symptoms. In conclusion, our findings emphasize an important role of fungal sensitization in the manifestations of asthma and AR in the Southeast Asian Chinese population.

Recent progress of oridonin and its derivatives for cancer therapy and drug resistance - Yong-Feng Guan; Xiu-Juan Liu; Xiao-Jing Pang; Wen-Bo Liu; Guang -Xi Yu; Yin -Ru Li; Yan-Bing Zhang; Jian Song; Sai-Yang Zhang (Medicinal Chemistry Research, 2021)

Anti-miR33 therapy improved hepatopancreatic lipid and immune metabolism disorders in grass carp, Ctenopharyngodon idella - Rong-Hua Lu; Meng-Jun Lin; Feng Yang; Shen-zong Jia; Yu-Ru Zhang; Chao-Bin Qin; Xiao-Lin Meng; Guo-Xing Nie (Fish Physiology and Biochemistry, 2021)

The occurrence order and cross-talk of different tRNA modifications - Jing Li; Wen-Yu Zhu; Wen-Qing Yang; Cai-Tao Li; Ru-Juan Liu (Science China Life Sciences, 2021)

Present in-situ stress distribution characteristics of strike-slip in SH Oilfield, Tarim Basin - Teng Zhao; Wenge Hu; Rui Zhao; Min Yang; Qiang Wang; Huixi Lin; Zhixing Ru; Dian Bao; Fei Cao (Arabian Journal of Geosciences, 2021)

Vibrio nitrifigilis sp. nov., a marine nitrogen-fixing bacterium isolated from the lagoon sediment of an islet inside an atoll - Wei-Sheng Huang; Li-Ting Wang; Jwo-Sheng Chen; Yen-Ting Chen; Sean Ting-Shyang Wei; Yin-Ru Chiang; Pei-Ling Wang; Tzong-Huei Lee; Shih-Ting Lin; Lina Huang; Wung Yang Shieh (Antonie van Leeuwenhoek, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

An Infrared Touch System for Automatic Behavior Monitoring - Qingqing Liu; Xing Yang; Ru Song; Junying Su; Moxuan Luo; Jinling Zhong; Liping Wang (Neuroscience Bulletin, 2021)
Key requirements of successful animal behavior research in the laboratory are robustness, objectivity, and high throughput, which apply to both the recording and analysis of behavior. Many automatic methods of monitoring animal behavior meet these requirements. However, they usually depend on high-performing hardware and sophisticated software, which may be expensive. Here, we describe an automatic infrared behavior-monitor (AIBM) system based on an infrared touchscreen frame. Using this, animal positions can be recorded and used for further behavioral analysis by any PC supporting touch events. This system detects animal behavior in real time and gives closed-loop feedback using relatively low computing resources and simple algorithms. The AIBM system automatically records and analyzes multiple types of animal behavior in a highly efficient, unbiased, and low-cost manner.

The Knowledge and Attitude Towards Advance Care Planning Among Chinese Patients with Advanced Cancer - Xiao-Ting Hou; Yu-Han Lu; Hong Yang; Ren-Xiu Guo; Yun Wang; Li-Hong Wen; Ya-Ru Zhang; Hong-Yu Sun (Journal of Cancer Education, 2021)

A rapid and accurate method for identifying sexuality of Indarbela obliquifasciata Mell (Lepidoptera, Metarbelidae) adults and pupae - Li-Zhi Huo; Long-Hua Sun; Jing-Ai Zhang; Chao Wu; Ya-Hui Hou; Yong-Yue Wang; Zhi-Jie Li; Jia-Ru Deng; Si-Meng Yang; Ke-Ke Bi (International Journal of Tropical Insect Science, 2021)

Luteolin alleviates ulcerative colitis through SHP-1/STAT3 pathway - Bo-Lin Li; Dan-Yang Zhao; Peng-Li Du; Xiao-Tian Wang; Qian Yang; Yan-Ru Cai (Inflammation Research, 2021)

Application of Gaussian Weight to Improve Perturbation Features of Convection-Permitting Ensemble Forecast Based on Local Breeding of Growing Modes - Kun Li; Chaohui Chen; Hongrang He; Ru Yang; Yi Li; Yongqiang Jiang (Journal of Meteorological Research, 2021)

Anthropogenic Sound Exposure-Induced Stress in Captive Dolphins and Implications for Cetacean Health - Wei-Cheng Yang; Chi-Fang Chen; Yee-Chien Chuah; Chun-Ru Zhuang; I-Hua Chen; T. Aran Mooney; Jeff Stott; Myra Blanchard; I-Fan Jen; Lien-Siang Chou (Frontiers in Marine Science, 2021)
Many cetaceans are exposed to increasing pressure caused by anthropogenic activities in their marine environment. Anthropogenic sound has been recognized as a possible stressor for cetaceans that may have impacts on health. However, the relationship between stress, hormones, and cytokines secretion in cetaceans is complex and not fully understood. Moreover, the effects of stress are often inconsistent because the character, intensity, and duration of the stressors are variable. For a better understanding of how anthropogenic sounds affect the psychophysiology of cetaceans, the present study compared the changes of cortisol concentration and cytokine gene transcriptions in blood samples and behaviors of captive bottlenose dolphins ( Tursiops truncatus ) after sound exposures. The sound stimuli were 800 Hz pure-tone multiple impulsive sound for 30 min at three different sound levels (estimated mean received SPL: 0, 120, and 140 dB re 1 μPa) that likely cause no permanent and temporary hearing threshold shift in dolphins. Six cytokine genes (IL-2Rα, IL-4, IL-10, IL-12, TNF-α, and IFN-γ) were selected for analysis. Cortisol levels and IL-10 gene transcription increased and IFNγ/IL-10 ratio was lower after a 30-min high-level sound exposure, indicating the sound stimuli used in this study could be a stressor for cetaceans, although only minor behavior changes were observed. This study may shed light on the potential impact of pile driving-like sounds on the endocrine and immune systems in cetaceans and provide imperative information regarding sound exposure for free-ranging cetaceans.

Molecular epidemiological characteristics of echovirus 6 in mainland China: extensive circulation of genotype F from 2007 to 2018 - Wenjun Cheng; Tianjiao Ji; Shuaifeng Zhou; Yong Shi; Lili Jiang; Yong Zhang; Dongmei Yan; Qian Yang; Yang Song; Ru Cai; Wenbo Xu (Archives of Virology, 2021)
Echovirus 6 (E6) is associated with various clinical diseases and is frequently detected in environmental sewage. Despite its high prevalence in humans and the environment, little is known about its molecular phylogeography in mainland China. In this study, 114 of 21,539 (0.53%) clinical specimens from hand, foot, and mouth disease (HFMD) cases collected between 2007 and 2018 were positive for E6. The complete VP1 sequences of 87 representative E6 strains, including 24 strains from this study, were used to investigate the evolutionary genetic characteristics and geographical spread of E6 strains. Phylogenetic analysis based on VP1 nucleotide sequence divergence showed that, globally, E6 strains can be grouped into six genotypes, designated A to F. Chinese E6 strains collected between 1988 and 2018 were found to belong to genotypes C, E, and F, with genotype F being predominant from 2007 to 2018. There was no significant difference in the geographical distribution of each genotype. The evolutionary rate of E6 was estimated to be 3.631 × 10 -3 substitutions site -1 year -1 (95% highest posterior density [HPD]: 3.2406 × 10 -3 -4.031 × 10 -3 substitutions site -1 year -1 ) by Bayesian MCMC analysis. The most recent common ancestor of the E6 genotypes was traced back to 1863, whereas their common ancestor in China was traced back to around 1962. A small genetic shift was detected in the Chinese E6 population size in 2009 according to Bayesian skyline analysis, which indicated that there might have been an epidemic around that year.

Genome sequencing and functional annotation of Bacillus sp. strain BS-Z15 isolated from cotton rhizosphere soil having antagonistic activity against Verticillium dahliae - Zhong-Yi Chen; Xieerwanimu Abuduaini; Nuramina Mamat; Qi-Lin Yang; Meng-Jun Wu; Xin-Rui Lin; Ru Wang; Rong-Rong Lin; Wei-Jun Zeng; Huan-Chen Ning; He-Ping Zhao; Jin-Yu Li; et al. (Archives of Microbiology, 2021)

The gut microbiome and arsenic-induced disease—iAs metabolism in mice - Yifei Yang; Liang Chi; Yunjia Lai; Yun-Chung Hsiao; Hongyu Ru; Kun Lu (Current Environmental Health Reports, 2021)

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Haplotype networks of Phycocalidia tanegashimensis (Bangiales, Rhodophyta) indicate a probable invasion from the South China Sea to Brazil - Wan Zhao; Lei Dong; Dang Diem Hong; Juliet Brodie; Wei-Zhou Chen; Dam Duc Tien; Wei Zhou; Qin-Qin Lu; Mei-Ru Zhang; Li-En Yang (Marine Biodiversity, 2021)

Biomimetic Au nanodot synthesis using Escherichia coli secretion and interaction with α-ketoglutaric acid - Xiaoxiao Xie; Xiaoli Yang; Yi Chang; Xiangli Ru; Xiaoming Ma; Lin Yang (Science China Life Sciences, 2021)

FOXG1 Directly Suppresses Wnt5a During the Development of the Hippocampus - Yang Ni; Bin Liu; Xiaojing Wu; Junhua Liu; Ru Ba; Chunjie Zhao (Neuroscience Bulletin, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

Compound heterozygous mutation of the ASXL3 gene causes autosomal recessive congenital heart disease - Fang Fu; Ru Li; Ting-ying Lei; Dan Wang; Xin Yang; Jin Han; Min Pan; Li Zhen; Jian Li; Fa-tao Li; Xiang-yi Jing; Dong-zhi Li; et al. (Human Genetics, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Application and Progress of Reinforcement Technology for Chinese Ancient Buildings with Wood Structure - Ru-yuan Yang; You-fu Sun; Xiao-feng Zhang (Geotechnical and Geological Engineering, 2020)

Functional connectivity changes of nucleus Accumbens Shell portion in left mesial temporal lobe epilepsy patients - Ru Yang; Xixi Zhao; Jun Liu; Xufeng Yao; Feng Hou; Yikai Xu; Qianjin Feng (Brain Imaging and Behavior, 2020)

FW0622, a new siderophore isolated from marine Verrucosispora sp. by genomic mining - Wei Zhao; Fei Peng; Chuan-xi Wang; Yang Xie; Ru Lin; Zhi-kai Fang; Fei Sun; Yun-yang Lian; Hong Jiang (Natural Product Research, 2020)

Novel ACADVL variants resulting in mitochondrial defects in long-chain acyl-CoA dehydrogenase deficiency - Ting Chen; Fan Tong; Xiao-yu Wu; Ling Zhu; Qiu-zi Yi; Jing Zheng; Ru-lai Yang; Zheng-yan Zhao; Xiao-hui Cang; Qiang Shu; Ping-ping Jiang (Journal of Zhejiang University-SCIENCE B, 2020)

Emerging relationship between RNA helicases and autophagy - Miao-miao Zhao; Ru-sha Wang; Yan-lin Zhou; Zheng-gang Yang (Journal of Zhejiang University-SCIENCE B, 2020)

Grape seed proanthocyanidin extract ameliorates hepatic lipid accumulation and inflammation in grass carp (Ctenopharyngodon idella) - Rong-Hua Lu; Chao-Bin Qin; Feng Yang; Wen-Ya Zhang; Yu-Ru Zhang; Guo-Kun Yang; Li-Ping Yang; Xiao-Lin Meng; Xiao Yan; Guo-Xing Nie (Fish Physiology and Biochemistry, 2020)

The neural mechanisms of immediate and follow-up of the treatment effect of hypnosis on smoking craving - Xiaoming Li; Lijun Chen; Ru Ma; Haibao Wang; Li Wan; Junjie Bu; Wei Hong; Wanwan Lv; Yihong Yang; Hengyi Rao; Xiaochu Zhang (Brain Imaging and Behavior, 2020)

Colorimetric detection of Hg2+ using gold nanoparticles synthesized by Trichosporon montevideense WIN - Rouyi Wang; Henglin Zhang; Xiuhong Zhang; Zheng Li; Ying Yang; Ru Zheng; Yuanyuan Qu (Biotechnology Letters, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Endophytic colonization by Beauveria bassiana increases the resistance of tomatoes against Bemisia tabaci - Qiu-Yang Wei; Ya-Ying Li; Chen Xu; Yi-Xia Wu; Ya-Ru Zhang; Huai Liu (Arthropod-Plant Interactions, 2020)
Beauveria bassiana , an entomopathogenic fungus, can exist asymptomatically as an endophyte in many plants. This study aimed to determine the efficiency of B. bassiana colonization of tomato plants using different inoculation methods, and how colonization of the host plant affects the key pest of tomato, the whitefly Bemisia tabaci . To confirm fungal colonization efficiency, nested PCR technique was used to detect B. bassiana sequences in Solanum lycopersicum . Distribution of the fungus within the plant parts was determined by selective medium. Tomato growth parameters were determined with plants that had been inoculated using direct spraying or irrigation of the rhizosphere. B. tabaci performance assays were carried out in a cage, and preference to treatments was determined using Y-tube olfactometer studies. Results show that B. bassiana can effectively colonize tomato, with colonization rate using leaf spraying reaching 100% within 14 days. Fungal presence was not uniformly distributed among plant parts, but was biased towards the inoculation sites. For inoculation, conidial suspension sprayed at 1 × 10 8 conidia/ml resulted in the highest number of isolated colonies in leaf tissue, 8.5 ± 2.02 colonies per 2 g of fresh tissue ( F 4,19 = 2.779, P = 0.045), and reached the lowest with root treatment. Although only small differences were observed among the growth indicators, leaf spray inoculation resulted in a significant positive influence on plant growth (PC1 55.7% contributions scores = 2.645) in further Principal component analysis. As for the feeding selectivity, B. tabaci preferred uninoculated plants. In Y-tube olfactometer assay, 80.5% of adults selected uninoculated plants. These findings add to the understanding of the interactions between B. bassiana and plants and indicate the potential of expanding the use of entomopathogenic fungi for crop protection.

Pure qP-wave least-squares reverse time migration in vertically transverse isotropic media and its application to field data - Jian-Ping Huang; Xin-Ru Mu; Zhen-Chun Li; Qing-Yang Li; Shuang-Qi Yuan; Yun-Dong Guo (Applied Geophysics, 2020)

Betulinic acid attenuates lipopolysaccharide-induced vascular hyporeactivity in the rat aorta by modulating Nrf2 antioxidative function - Yao-Yao Bai; Dong Yan; Hui-Ying Zhou; Wei-Xin Li; Yang-Yun Lou; Xin-Ru Zhou; Ling-Bo Qian; Chi Xiao (Inflammopharmacology, 2020)

Applying multivariate statistics for identification of groundwater chemistry and qualities in the Sugan Lake Basin, Northern Qinghai-Tibet Plateau, China - Juan Xiang; Jun-ju Zhou; Jun-cang Yang; Mei-hua Huang; Wei Feng; Qiao-qiao Li; Dong-xiang Xue; Ya-ru Zhao; Guo-feng Zhu (Journal of Mountain Science, 2020)

Comprehensive transcriptome analysis of faba bean in response to vernalization - Bei Gao; Xiao-Chun Bian; Feng Yang; Mo-Xian Chen; Debatosh Das; Xiu-Ru Zhu; Yong Jiang; Jianhua Zhang; Yun-Ying Cao; Chun-Fang Wu (Planta, 2020)

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Collagen-binding basic fibroblast growth factor improves functional remodeling of scarred endometrium in uterine infertile women: a pilot study - Peipei Jiang; Xiaoqiu Tang; Huiyan Wang; Chenyan Dai; Jing Su; Hui Zhu; Minmin Song; Jingyu Liu; Ziqing Nan; Tong Ru; Yaling Li; Jingmei Wang; et al. (Science China Life Sciences, 2019)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

Isolation, purification and identification of two new alkaloids metabolites from marine-derived Verrucosispora sp. FIM06025 - Ming-Hong Chen; Wen-Long Zhang; Li Chen; Ru Lin; Yang Xie; Dong-Sheng Fang; Yun-Yang Lian; Hong Jiang (Natural Product Research, 2019)

Cytoplasmic SIRT1 inhibits cell migration and invasion by impeding epithelial–mesenchymal transition in ovarian carcinoma - Tong Yang; Ru Zhou; Shentong Yu; Shuhong Yu; Zhuqing Cui; Peizhen Hu; Jinsong Liu; Qing Qiao; Jing Zhang (Molecular and Cellular Biochemistry, 2019)

Evaluation of chromatophores as natural marks for delta smelt: the effects of life-stage and light intensity - Gonzalo C. Castillo; Marade E. Sandford; Tien-Chieh Hung; Wan-Ru Yang; Galen Tigan; Luke Ellison; Joan C. Lindberg; Erwin E. Van Nieuwenhuyse (Environmental Biology of Fishes, 2019)

Selenium (Se) Does Not Reduce Cadmium (Cd) Uptake and Translocation in Rice (Oryza sativa L.) in Naturally Occurred Se-Rich Paddy Fields with a High Geological Background of Cd - Bei-Bei Yang; Cheng Yang; Zong-Yuan Shao; Hao Wang; Shu-Ting Zan; Meng Zhu; Shou-Biao Zhou; Ru-Yi Yang (Bulletin of Environmental Contamination and Toxicology, 2019)

The transcription factor MYB15 is essential for basal immunity (PTI) in Chinese wild grape - Yangyang Luo; Ru Bai; Jing Li; Weidong Yang; Ruixiang Li; Qingyang Wang; Guifang Zhao; Dong Duan (Planta, 2019)

Collembolans accelerate the dispersal of antibiotic resistance genes in the soil ecosystem - Dong Zhu; Hong-Tao Wang; Fei Zheng; Xiao-Ru Yang; Peter Christie; Yong-Guan Zhu (Soil Ecology Letters, 2019)

The complete chloroplast genome of Calycanthus chinensis, an endangered species endemic to China - Xiaodan Chen; Jia Yang; Hao Zhang; Ru Bai; Xiao Zhang; Guoqing Bai; Panfeng Dai; Guifang Zhao (Conservation Genetics Resources, 2019)

The potential of a modified physiologically equivalent temperature (mPET) based on local thermal comfort perception in hot and humid regions - Tzu-Ping Lin; Shing-Ru Yang; Yung-Chang Chen; Andreas Matzarakis (Theoretical and Applied Climatology, 2019)

Heterologous overexpression of Lithospermum erythrorhizon LeERF-1 gene increases drought and pathogen resistance in Arabidopsis - Rong-Jun Fang; Ai-Qian Li; Ru-Nan Tian; Wen-Ju Zhang; Ai-Lan Zou; Feng-Yao Wu; Yong-Hui Liao; Xiao-Ming Wang; Yan-Jun Pang; Rong-Wu Yang; Gui-Hua Lu; Jin-Liang Qi; et al. (Acta Physiologiae Plantarum, 2019)

Development strategies for the sea cucumber industry in China - Xiaoshang Ru; Libin Zhang; Xiaoni Li; Shilin Liu; Hongsheng Yang (Journal of Oceanology and Limnology, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Reduced hsa-miR-124-3p levels are associated with the poor survival of patients with hepatocellular carcinoma - Hui-Deng Long; Yu-Shui Ma; Hui-Qiong Yang; Shao-Bo Xue; Ji-Bin Liu; Fei Yu; Zhong-Wei Lv; Ji-Yu Li; Ru-Ting Xie; Zheng-Yan Chang; Gai-Xia Lu; Wen-Ting Xie; et al. (Molecular Biology Reports, 2018)

Molecular and morphological data reveals new insights into genetic diversity and population structure of Chinese cherry (Prunus pseudocerasus Lindl.) landraces - Tao Chen; Yue-yang Hu; Qing Chen; Yan Wang; Jing Zhang; Hao-ru Tang; Xiao-rong Wang (Genetic Resources and Crop Evolution, 2018)

Population genomic analysis reveals that homoploid hybrid speciation can be a lengthy process - Dafu Ru; Yongshuai Sun; Donglei Wang; Yang Chen; Tianjing Wang; Quanjun Hu; Richard J. Abbott; Jianquan Liu (Molecular Ecology, 2018)
An increasing number of species are thought to have originated by homoploid hybrid speciation ( HHS ), but in only a handful of cases are details of the process known. A previous study indicated that Picea purpurea , a conifer in the Qinghai–Tibet Plateau ( QTP ), originated through HHS from P. likiangensis and P. wilsonii . To investigate this origin in more detail, we analysed transcriptome data for 114 individuals collected from 34 populations of the three Picea species from their core distributions in the QTP . Phylogenetic, principal component and admixture analyses of nuclear SNP s showed the species to be delimited genetically and that P. purpurea was admixed with approximately 60% of its ancestry derived from P. wilsonii and 40% from P. likiangensis . Coalescent simulations revealed the best‐fitting model of origin involved formation of an intermediate hybrid lineage between P. likiangensis and P. wilsonii approximately 6 million years ago (mya), which backcrossed to P. wilsonii to form P. purpurea approximately one mya. The intermediate hybrid lineage no longer exists and is referred to as a “ghost” lineage. Our study emphasizes the power of population genomic analysis combined with coalescent analysis for reconstructing the stages involved in the origin of a homoploid hybrid species over an extended period. In contrast to other studies, we show that these stages can in some instances span a relatively long period of evolutionary time.

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells - Kai Hong Wu; Su Yun Wang; Qian Ru Xiao; Yu Yang; Ning Ping Huang; Xu Ming Mo; Jian Sun (Cell and Tissue Research, 2018)

Characterisation of silver release from nanoparticle-treated baby products - Ru Ding; Pingjian Yang; Yuan Yang; Zhaoguang Yang; Li Luo; Haipu Li; Qiang Wang (Food Additives & Contaminants: Part A, 2018)

Structure elucidation and antitumour activity of a new macrolactam produced by marine-derived actinomycete Micromonospora sp. FIM05328 - Yi-Lei Nie; Yun-Dan Wu; Chuan-Xi Wang; Ru Lin; Yang Xie; Dong-Sheng Fang; Hong Jiang; Yun-Yang Lian (Natural Product Research, 2018)

Luteolin alleviates cardiac ischemia/reperfusion injury in the hypercholesterolemic rat via activating Akt/Nrf2 signaling - Jin-Ting Yang; Jue Wang; Xin-Ru Zhou; Chi Xiao; Yang-Yun Lou; Li-Hui Tang; Feng-Jiang Zhang; Ling-Bo Qian (Naunyn-Schmiedeberg's Archives of Pharmacology, 2018)

An integrated assessment of INDCs under Shared Socioeconomic Pathways: an implementation of C3IAM - Yi-Ming Wei; Rong Han; Qiao-Mei Liang; Bi-Ying Yu; Yun-Fei Yao; Mei-Mei Xue; Kun Zhang; Li-Jing Liu; Juan Peng; Pu Yang; Zhi-Fu Mi; Yun-Fei Du; et al. (Natural Hazards, 2018)

Absorption and subcellular distribution of cadmium in tea plant (Camellia sinensis cv. “Shuchazao”) - De-ju Cao; Xun Yang; Geng Geng; Xiao-chun Wan; Ru-xiao Ma; Qian Zhang; Yue-gan Liang (Environmental Science and Pollution Research, 2018)

Changes of functional connectivity of the anterior cingulate cortex in women with primary dysmenorrhea - Peng Liu; Yanfei Liu; Geliang Wang; Ru Li; Ying Wei; Yingying Fan; Yang Yu; Demao Deng; Wei Qin (Brain Imaging and Behavior, 2018)

Non-structural protein 1 from avian influenza virus H9N2 is an efficient RNA silencing suppressor with characteristics that differ from those of Tomato bushy stunt virus p19 - Ru Yu; Xiuli Jing; Wenjing Li; Jie Xu; Yang Xu; Liwei Geng; Changxiang Zhu; Hongmei Liu (Virus Genes, 2018)

Soil physicochemical properties and vegetation structure along an elevation gradient and implications for the response of alpine plant development to climate change on the northern slopes of the Qilian Mountains - Yong-sheng Yang; Li Zhang; Hong-qin Li; Hui-dan He; Ya-xi Wei; Jin Luo; Guang-ru Zhang; Yu-ru Huang; Ying-nian Li; Hua-kun Zhou (Journal of Mountain Science, 2018)

Echinacoside, a phenylethanoid glycoside from Cistanche deserticola, extends lifespan of Caenorhabditis elegans and protects from Aβ-induced toxicity - Wei Chen; Hong-Ru Lin; Cong-Min Wei; Xiao-Hua Luo; Meng-Lu Sun; Zhen-Zhou Yang; Xin-Yan Chen; Hong-Bing Wang (Biogerontology, 2018)

Pentapeptide-insertion scanning mutational analysis of turkey herpesvirus HVT063 reveals residues important for its RNA silencing suppression activity - Gang Jia; Wenjing Li; Meina Fan; Ru Yu; Yang Xu; Liwei Geng; Jiedao Zhang; Changxiang Zhu; Hongmei Liu (Archives of Virology, 2018)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

Metabolic benefits of rivaroxaban in non-valvular atrial fibrillation patients after radiofrequency catheter ablation - Jun Zhu; Rong-jun Gao; Qiang Liu; Ru-hong Jiang; Lu Yu; Ya-xun Sun; Pei Zhang; Jian-wei Lin; Yang Ye; Zu-wen Zhang; Shi-quan Chen; Hui Cheng; et al. (Journal of Zhejiang University-SCIENCE B, 2017)

Influence of Rapeseed Cake on Iron Plaque Formation and Cd Uptake by Rice (Oryza sativa L.) Seedlings Exposed to Excess Cd - Wen-Tao Yang; Hang Zhou; Jiao-Feng Gu; Qing-ru Zeng; Bo-Han Liao (Bulletin of Environmental Contamination and Toxicology, 2017)

Erratum to: Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

An overlooked nitrogen loss linked to anaerobic ammonium oxidation in estuarine sediments in China - Xiao-Ru Yang; Bo-Sen Weng; Hu Li; Christopher W. Marshall; Hong Li; Yong-Shan Chen; Shen Yu; Gui-Bing Zhu; Yong-Guan Zhu (Journal of Soils and Sediments, 2017)

Inhibitory effect of StCYP707A1 gene on tuberization in transgenic potato - Lu Liu; Rui-Jie Zhang; Wen-Jiao Zhu; Xin-Ru Liu; Ke Shi; Min Chen; Qing Yang (Plant Biotechnology Reports, 2017)

Repeated Neonatal Sevoflurane Exposure-Induced Developmental Delays of Parvalbumin Interneurons and Cognitive Impairments Are Reversed by Environmental Enrichment - Mu-huo Ji; Zhong-yun Wang; Xiao-ru Sun; Hui Tang; Hui Zhang; Min Jia; Li-li Qiu; Guang-fen Zhang; Yong G. Peng; Jian-jun Yang (Molecular Neurobiology, 2017)

Evaluation on subcellular partitioning and biodynamics of pulse copper toxicity in tilapia reveals impacts of a major environmental disturbance - Yun-Ru Ju; Ying-Fei Yang; Jeng-Wei Tsai; Yi-Hsien Cheng; Wei-Yu Chen; Chung-Min Liao (Environmental Science and Pollution Research, 2017)

Zircon U–Pb dating of eclogite from the Qiangtang terrane, north-central Tibet: a case of metamorphic zircon with magmatic geochemical features - Qing-guo Zhai; Bor-ming Jahn; Xian-hua Li; Ru-yuan Zhang; Qiu-li Li; Ya-nan Yang; Jun Wang; Tong Liu; Pei-yuan Hu; Suo-han Tang (International Journal of Earth Sciences, 2017)

Assessment of Photodegradation of Herbicide Prometryn in Soil - Chen Jiang; Xue Jing Li; Ya Ru Wang; Li Ya Ma; Ya Kun Wang; Yi Chen Lu; Hong Yang (Water, Air, & Soil Pollution, 2017)

Cd Content in Sugarcane and Its Relationship with Soil Factors - Hui-Ping Ou; Liu-Qiang Zhou; Xi-Hui Liu; Jin-Sheng Huang; Yan Zeng; Ru-Lin Xie; Xiao-Hui Zhu; Hong-Wei Tan; Yang-Rui Li (Sugar Tech, 2017)

Activation of the ventral tegmental area increased wakefulness in mice - Huan-Xin Sun; Dian-Ru Wang; Chen-Bo Ye; Zhen-Zhen Hu; Chen-Yao Wang; Zhi-Li Huang; Su-Rong Yang (Sleep and Biological Rhythms, 2017)

Comparison of Conventional Washing Processing and pH Shift Processing on Gelation Characteristics of Bighead Carp ( Aristichthys nobilis ) Muscle Proteins - Tong Chang; Chenjie Wang; Hong Yang; Shanbai Xiong; Youming Liu; Ru Liu (Journal of Aquatic Food Product Technology, 2017)

Inhibition of the Receptor for Advanced Glycation End-Products (RAGE) Attenuates Neuroinflammation While Sensitizing Cortical Neurons Towards Death in Experimental Subarachnoid Hemorrhage - Hua Li; Jia-Sheng Yu; Ding-Ding Zhang; Yi-Qing Yang; Li-Tian Huang; Zhuang Yu; Ru-Dong Chen; Hong-Kuan Yang; Chun-Hua Hang (Molecular Neurobiology, 2017)

An integrated earthquake early warning system and its performance at schools in Taiwan - Bing-Ru Wu; Nai-Chi Hsiao; Pei-Yang Lin; Ting-Yu Hsu; Chiou-Yun Chen; Shieh-Kung Huang; Hung-Wei Chiang (Journal of Seismology, 2017)

NOX2 Mediated-Parvalbumin Interneuron Loss Might Contribute to Anxiety-Like and Enhanced Fear Learning Behavior in a Rat Model of Post-Traumatic Stress Disorder - Fang-fang Liu; Lin-dong Yang; Xiao-ru Sun; Hui Zhang; Wei Pan; Xing-ming Wang; Jian-jun Yang; Mu-huo Ji; Hong-mei Yuan (Molecular Neurobiology, 2016)

Dynamic quantitative proteomics characterization of TNF-α-induced necroptosis - Yang Wang; Zhi-Hao Huang; Yang-Jia Li; Gui-Wei He; Ru-Yuan Yu; Jie Yang; Wan-Ting Liu; Bin Li; Qing-Yu He (Apoptosis, 2016)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Reactive Oxygen Species-mediated Loss of Phenotype of Parvalbumin Interneurons Contributes to Long-term Cognitive Impairments After Repeated Neonatal Ketamine Exposures - Hui Zhang; Xiao-ru Sun; Jing Wang; Zhen-zhen Zhang; Hong-ting Zhao; Hui-hui Li; Mu-huo Ji; Kuan-yu Li; Jian-jun Yang (Neurotoxicity Research, 2016)

RhoB/ROCK mediates oxygen–glucose deprivation-stimulated syncytiotrophoblast microparticle shedding in preeclampsia - Jian Han; Bo-ping Yang; Yi-lin Li; Hong-mei Li; Xiu-hui Zheng; Li-li Yu; Qiong Zhang; Ying-ru Zheng; Ping Yi; Li Li; Jian-xin Guo; Yuan-guo Zhou (Cell and Tissue Research, 2016)

Trans-cinnamaldehyde protected PC12 cells against oxygen and glucose deprivation/reperfusion (OGD/R)-induced injury via anti-apoptosis and anti-oxidative stress - Xue Qi; Ru Zhou; Yue Liu; Jing Wang; Wan-Nian Zhang; Huan-Ran Tan; Yang Niu; Tao Sun; Yu-Xiang Li; Jian-Qiang Yu (Molecular and Cellular Biochemistry, 2016)

Impacts of rapeseed dregs on Cd availability in contaminated acid soil and Cd translocation and accumulation in rice plants - Wen-Tao Yang; Jiao-Feng Gu; Jia-Ling Zou; Hang Zhou; Qing-Ru Zeng; Bo-Han Liao (Environmental Science and Pollution Research, 2016)

Norovirus outbreaks in Fengtai District, Beijing, China, 2014 - Jin-Song Li; Meng Qin; Xiao-Gen Dong; Jun-Yong Yang; Xiao-Xin Yang; Xiu-xia Wei; Zhao-e Wang; Hui-ru Feng; Qin-rui Wu; Ruo-xi Li; Jie Li; Zhao-Jun Duan (Archives of Virology, 2016)

Molecular Design, Structural Analysis and Antifungal Activity of Derivatives of Peptide CGA-N46 - Rui-Fang Li; Zhi-Fang Lu; Ya-Nan Sun; Shi-Hua Chen; Yan-Jie Yi; Hui-Ru Zhang; Shuo-Ye Yang; Guang-Hai Yu; Liang Huang; Chao-Nan Li (Interdisciplinary Sciences: Computational Life Sciences, 2016)

Influence of Soluplus on Solid-State Properties and Physical Stability of Indomethacin-Saccharin Co-crystal Formation Prepared by Air-Drying Process - Shan-Yang Lin; Hong-Liang Lin; Ying-Ting Chi; Ru-Ying Hung; Yu-Ting Huang; Wei-Hsien Hsieh; Chi-Yu Kao (Journal of Pharmaceutical Innovation, 2016)

Functional expression of human serum albumin-tandem thrombopoietin mimetic peptide fusion protein as a novel thrombopoietin analog in Pichia pastoris - Meizhu Wang; Dejuan Zhi; Jun Xian; Yi Ru; Suzhen Wei; Na Wang; Yiyao Liu; Haiqing Wang; Yuejuan Pei; Meijuan Song; Yang Li; Hongyu Li (Biotechnology Letters, 2016)

Effect of desiccation in shade on in vitro oocyte maturation and development of the sea cucumber Apostichopus japonicus (Echinodermata: Holothuroidea) - Shilin Liu; Yi Zhou; Tao Zhang; Lina Sun; Xiaoshang Ru; Junhua Li; Hongsheng Yang (Invertebrate Reproduction & Development, 2016)

Sodium Channel Voltage-Gated Beta 2 Plays a Vital Role in Brain Aging Associated with Synaptic Plasticity and Expression of COX5A and FGF-2 - Yan-Bin XiYang; You-Cui Wang; Ya Zhao; Jin Ru; Bing-Tuan Lu; Yue-Ning Zhang; Nai-Chao Wang; Wei-Yan Hu; Jia Liu; Jin-Wei Yang; Zhao-Jun Wang; Chun-Guang Hao; et al. (Molecular Neurobiology, 2016)

Hypermethylation of Hippocampal Synaptic Plasticity-Related genes is Involved in Neonatal Sevoflurane Exposure-Induced Cognitive Impairments in Rats - Ling-sha Ju; Min Jia; Jie Sun; Xiao-ru Sun; Hui Zhang; Mu-huo Ji; Jian-jun Yang; Zhong-yun Wang (Neurotoxicity Research, 2016)

Gomisin A is a Novel Isoform-Specific Probe for the Selective Sensing of Human Cytochrome P450 3A4 in Liver Microsomes and Living Cells - Jing-Jing Wu; Guang-Bo Ge; Yu-Qi He; Ping Wang; Zi-Ru Dai; Jing Ning; Liang-Hai Hu; Ling Yang (The AAPS Journal, 2016)

Customized rating assessment of climate suitability (CRACS): climate satisfaction evaluation based on subjective perception - Tzu-Ping Lin; Shing-Ru Yang; Andreas Matzarakis (International Journal of Biometeorology, 2015)

Low-Dose Topical 5-Aminolevulinic Acid Photodynamic Therapy in the Treatment of Different Severity of Acne Vulgaris - Shi-qin Tao; Fei Li; Lei Cao; Ru-shan Xia; Hua Fan; Ying Fan; Hui Sun; Cheng Jing; Li-jia Yang (Cell Biochemistry and Biophysics, 2015)

Environmental Enrichment Ameliorates Neonatal Sevoflurane Exposure-Induced Cognitive and Synaptic Plasticity Impairments - Mu-huo Ji; Xing-ming Wang; Xiao-ru Sun; Hui Zhang; Ling-sha Ju; Li-li Qiu; Jiao-jiao Yang; Min Jia; Jing Wu; Jianjun Yang (Journal of Molecular Neuroscience, 2015)

Protective effects of aloperine on neonatal rat primary cultured hippocampal neurons injured by oxygen–glucose deprivation and reperfusion - Ning-Tian Ma; Ru Zhou; Ren-Yuan Chang; Yin-Ju Hao; Lin Ma; Shao-Ju Jin; Juan Du; Jie Zheng; Cheng-Jun Zhao; Yang Niu; Tao Sun; Wei Li; et al. (Journal of Natural Medicines, 2015)

Tree bark as a biomonitor for the determination of polychlorinated biphenyls and polybrominated diphenyl ethers from Southern Jiangsu, China: levels, distribution, and possible sources - Li Zhou; Liang Dong; Ye-Ru Huang; Shuang-Xin Shi; Li-Fei Zhang; Xiu-Lan Zhang; Wen-Long Yang (Environmental Monitoring and Assessment, 2015)

Effect of microRNA-203 on tumor growth in human hypopharyngeal squamous cell carcinoma - Ru Wang; Jugao Fang; Hongzhi Ma; Lin Feng; Meng Lian; Fan Yang; Haizhou Wang; Qi Wang; Xiaohong Chen (Molecular and Cellular Biochemistry, 2015)

Changes of polybrominated diphenyl ethers and polychlorinated biphenyls in surface soils from urban agglomeration of the Yangtze River Delta, in China between 2003 and 2012 - Shuang-Xin Shi; Ye-Ru Huang; Li Zhou; Li-Fei Zhang; Liang Dong; Wen-Long Yang; Xiu-Lan Zhang (Environmental Science and Pollution Research, 2015)

Interaction of DRD2TaqI, COMT, and ALDH2 genes associated with bipolar II disorder comorbid with anxiety disorders in Han Chinese in Taiwan - Ming-Chuan Hu; Sheng-Yu Lee; Tzu-Yun Wang; Yun-Hsuan Chang; Shiou-Lan Chen; Shih-Heng Chen; Chun-Hsien Chu; Chen-Lin Wang; I Hui Lee; Po See Chen; Yen Kuang Yang; Ru-Band Lu (Metabolic Brain Disease, 2015)

Two new triterpenoids from Nauclea officinalis - Hai-Yang Wang; Ke Liu; Ru-Xia Wang; San-Hai Qin; Feng-Ling Wang; Jing-Yong Sun (Natural Product Research, 2015)

Paracercospora dictamnicola sp. nov. from China - Yang-Hui Ou; Ru-Jun Zhou; Jun-Fan Fu; Yue Yuan; Hai-Jiao Xu (Mycological Progress, 2015)

The relationship between the plant-encoded RNA-dependent RNA polymerase 1 and alternative oxidase in tomato basal defense against Tobacco mosaic virus - Yang-Wen-Ke Liao; Ya-Ru Liu; Jia-Yang Liang; Wen-Ping Wang; Jie Zhou; Xiao-Jian Xia; Yan-Hong Zhou; Jing-Quan Yu; Kai Shi (Planta, 2015)

Studies on mitogen-activated protein kinase signaling pathway in the alveolar macrophages of chronic bronchitis rats - Yan Huang; Xiao-Ming Meng; Guo-Lin Jiang; Ya-Ru Yang; Juan Liu; Xiong-Wen Lv; Jun Li (Molecular and Cellular Biochemistry, 2015)

Ligand-based 3D pharmacophore design, virtual screening and molecular docking for novel p38 MAPK inhibitors - Lijuan He; Ru Dai; Xuan R. Zhang; Si Y. Gao; Yan Y. He; Li B. Wang; Xang Gao; Lu Q. Yang (Medicinal Chemistry Research, 2015)

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

Genetic analysis and chromosome mapping of a thermo-sensitive genic male sterile gene in wheat - Zhen-Gang Ru; Li-Ping Zhang; Tie-Zhu Hu; Hong-Yu Liu; Qing-Kai Yang; Man-Li Weng; Bin Wang; Chang-Ping Zhao (Euphytica, 2015)

The influence of genetics factor on key growth traits and quantitative genetic analysis of sea cucumber Apostichopus Japonicus (Selenka) heat-resistant and fast-growing strain - Sicong Zhang; Hongsheng Yang; Shilin Liu; Libin Zhang; Xiaoshang Ru; Dongxue Xu (Aquaculture International, 2015)

Compounds from marine-derived Verrucosispora sp. FIM06054 and their potential antitumour activities - Nie Yi-Lei; Wu Yun-Dan; Wang Chuan-Xi; Lin Ru; Xie Yang; Fang Dong-Sheng; Jiang Hong; Lian Yun-Yang (Natural Product Research, 2014)

Efficacy of a high-growth reassortant H1N1 influenza virus vaccine against the classical swine H1N1 subtype influenza virus in mice and pigs - Feng Wen; Hai Yu; Fu-ru Yang; Meng Huang; Sheng Yang; Yan-Jun Zhou; Ze-Jun Li; Guang-Zhi Tong (Archives of Virology, 2014)

The role of epithelial tight junctions involved in pathogen infections - Ru-Yi Lu; Wan-Xi Yang; Yan-Jun Hu (Molecular Biology Reports, 2014)

Non-pulmonary vein foci induced before and after pulmonary vein isolation in patients undergoing ablation therapy for paroxysmal atrial fibrillation: incidence and clinical outcome - Hui Cheng; Yin-yin Dai; Ru-hong Jiang; Qiang Liu; Ya-xun Sun; Jian-wei Lin; Zu-wen Zhang; Shi-quan Chen; Jun Zhu; Xia Sheng; Chen-yang Jiang (Journal of Zhejiang University-SCIENCE B, 2014)

Gene order rearrangement of the M gene in the rabies virus leads to slower replication - Xian-Feng Yang; Jiao-Jiao Peng; Hong-Ru Liang; You-Tian Yang; Yi-Fei Wang; Xiao-Wei Wu; Jiao-Jiao Pan; Yong-Wen Luo; Xiao-Feng Guo (VirusDisease, 2014)

The Attenuation of Lung Ischemia Reperfusion Injury by Oxymatrine - Bing Zhu; Jian-Ru Yang; Shi-Feng Chen; Yue Quan Jiang (Cell Biochemistry and Biophysics, 2014)

Evaluation of Angiogenesis in Non-small Cell Lung Carcinoma by CD34 Immunohistochemistry - Zhu Bing; Yang Jian-ru; Jiang Yao-quan; Chen Shi-feng (Cell Biochemistry and Biophysics, 2014)

Rapid development of tissue bank achieved by International Atomic Energy Agency (IAEA) Tissue Banking Programme in China - Yu-Min Zhang; Jian-Ru Wang; Nai-Li Zhang; Xiao-Ming Liu; Mo Zhou; Shao-Ying Ma; Ting Yang; Bao-Xing Li (Cell and Tissue Banking, 2014)

Occurrence, sources, and ecological risks of PBDEs, PCBs, OCPs, and PAHs in surface sediments of the Yangtze River Delta city cluster, China - Ting Zhang; Wen-Long Yang; She-Jun Chen; Dian-Long Shi; Hu Zhao; Yi Ding; Ye-Ru Huang; Nan Li; Yue Ren; Bi-Xian Mai (Environmental Monitoring and Assessment, 2014)

Etanercept in the Treatment of Intestinal Behcet’s Disease - Dan Ma; Chao-Jun Zhang; Ru-Peng Wang; Lie Wang; Hua Yang (Cell Biochemistry and Biophysics, 2014)

Anti-tumor Effects of Gene Therapy with GALV Membrane Fusion Glycoprotein in Lung Adenocarcinoma - Bing Zhu; Jian-ru Yang; Xin-ping Fu; Yue-quan Jiang (Cell Biochemistry and Biophysics, 2014)

Gene Therapy of Lung Adenocarcinoma using Herpes Virus Expressing a Fusogenic Membrane Glycoprotein - Bing Zhu; Jian-ru Yang; Yue-quan Jiang; Shi-feng Chen; Xin-ping Fu (Cell Biochemistry and Biophysics, 2014)

Study on phosphorus loadings in ten natural and agricultural watersheds in subtropical region of China - Yuyuan Li; Cen Meng; Ru Gao; Wen Yang; Junxia Jiao; Yong Li; Yi Wang; Jinshui Wu (Environmental Monitoring and Assessment, 2014)

Nuclear factor-κB signaling pathway is involved in phospholipase Cε-regulated proliferation in human renal cell carcinoma cells - Hong-fei Du; Li-ping Ou; Xue-dong Song; Yan-ru Fan; Xue Yang; Bing Tan; Zhen Quan; Chun-Li Luo; Xiao-hou Wu (Molecular and Cellular Biochemistry, 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

SNP and haplotype analysis reveal IGF2 variants associated with growth traits in Chinese Qinchuan cattle - Yong-Zhen Huang; Zhao-Yang Zhan; Xin-Yi Li; Sheng-Ru Wu; Yu-Jia Sun; Jing Xue; Xian-Yong Lan; Chu-Zhao Lei; Chun-Lei Zhang; Yu-Tang Jia; Hong Chen (Molecular Biology Reports, 2014)

Development and Characterisation of Ursolic Acid Nanocrystals Without Stabiliser Having Improved Dissolution Rate and In Vitro Anticancer Activity - Ju Song; Yancai Wang; Yuelin Song; Hokman Chan; Chao Bi; Xiao Yang; Ru Yan; Yitao Wang; Ying Zheng (AAPS PharmSciTech, 2014)

Two new cytotoxic iridoid esters from the rhizomes and roots of Patrinia heterophylla Bunge - Bo Yang; Ru-Bin Cheng; Yi-Qi Wang; Li Shen; Ru-Song Zhang (Natural Product Research, 2013)

Expression of SOCSs in human prostate cancer and their association in prognosis - Jian-guo Zhu; Qi-shan Dai; Zhao-dong Han; Hui-chan He; Ru-jun Mo; Guo Chen; Yan-fei Chen; Yong-ding Wu; Sheng-bang Yang; Fu-neng Jiang; Wei-hong Chen; Zhao-lin Sun; et al. (Molecular and Cellular Biochemistry, 2013)

Fine structure and primary sensory projections of sensilla located in the labial-palp pit organ of Helicoverpa armigera (Insecta) - Xin-Cheng Zhao; Qing-Bo Tang; Bente G. Berg; Yang Liu; Yan-Ru Wang; Feng-Ming Yan; Gui-Rong Wang (Cell and Tissue Research, 2013)

A new sesquiterpene lactone from Sarcandra glabra - Xiao-Ru Hu; Hai-Feng Wu; Xiao-Po Zhang; Jun-Shan Yang; Zhong Dai; Rui-Chao Lin; Xu-Dong Xu (Natural Product Research, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

Molecular cloning, expression profiles and subcellular localization of cyclin B in ovary of the mud crab, Scylla paramamosain - Wen-Xing Li; Hui-Yang Huang; Jing-Ru Huang; Jin-Jin Yu; Jun Ma; Hai-Hui Ye (Genes & Genomics, 2013)

Oyster shell reduces PAHs and particulate matter from incense burning - Chi-Ru Yang; Tzu-Hsing Ko; Yuan-Chung Lin; Suen-Zone Lee; Yih-Feng Chang; Hsin-Ta Hsueh (Environmental Chemistry Letters, 2013)

Mutations in AP22.65 accelerate flowering in Arabidopsis thaliana - Ji Hong Xing; Feng Ru Wang; Jiao Jia; Jing Zhang; Li Li; Zhan Chen; Qiao Yun Weng; Ping Yang; Ye Zhang; Bin Zhao; He Long Si; Jin Gao Dong; et al. (Journal of Plant Biology, 2013)

Dextromethorphan Attenuated Inflammation and Combined Opioid Use in Humans Undergoing Methadone Maintenance Treatment - Shiou-Lan Chen; Sheng-Yu Lee; Pao-Luh Tao; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsien Chu; Po See Chen; I Hui Lee; Tzung Lieh Yeh; Yen Kuang Yang; Jau-Shyong Hong; Ru-Band Lu (Journal of Neuroimmune Pharmacology, 2012)

Erratum to: Inflammation in Patients with Schizophrenia: The Therapeutic Benefits of Risperidone Plus Add-On Dextromethorphan - Shiou-Lan Chen; Sheng-Yu Lee; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsieh Chu; Nian-Sheng Tzeng; I-Hui Lee; Po-See Chen; Tzung Lieh Yeh; San-Yuan Huang; Yen-Kuang Yang; Ru-Band Lu; et al. (Journal of Neuroimmune Pharmacology, 2012)

Cloning and sequence analysis of chitin synthase gene fragments of Demodex mites - Ya-e Zhao; Zheng-hang Wang; Yang Xu; Ji-ru Xu; Wen-yan Liu; Meng Wei; Chu-ying Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Inflammation in Patients with Schizophrenia: The Therapeutic Benefits of Risperidone Plus Add-On Dextromethorphan - Shiou-Lan Chen; Sheng-Yu Lee; Yun-Hsuan Chang; Shih-Heng Chen; Chun-Hsieh Chu; Nian-Sheng Tzeng; I-Hui Lee; Po-See Chen; Tzung Lieh Yeh; San-Yuan Huang; Yen-Kuang Yang; Ru-Band Lu (Journal of Neuroimmune Pharmacology, 2012)

Tomographic inversion for microseismic source parameters in mining - Hua-Xiang Miao; Fu-Xing Jiang; Xue-Juan Song; Shu-Hua Yang; Jun-Ru Jiao (Applied Geophysics, 2012)

The mitochondrial genome of the quiet-calling katydids, Xizicus fascipes (Orthoptera: Tettigoniidae: Meconematinae) - MING RU YANG; ZHI JUN ZHOU; YAN LIN CHANG; LE HONG ZHAO (Journal of Genetics, 2012)

Culture-independent characterization of the autochthonous gut microbiota of grouper Epinephelus coioides following the administration of probiotic Enterococcus faecium - Yun-Zhang Sun; Hong-Ling Yang; Ru-Long Ma; Kun-Peng Huang; Ji-Dan Ye (Aquaculture International, 2012)

Effect of Sulforaphane on Growth Inhibition in Human Brain Malignant Glioma GBM 8401 Cells by Means of Mitochondrial- and MEK/ERK-Mediated Apoptosis Pathway - Tzuu-Yuan Huang; Weng-Cheng Chang; Miin-Yau Wang; Yun-Ru Yang; Yi-Chiang Hsu (Cell Biochemistry and Biophysics, 2012)

Automatically positioning microseismic sources in mining by the stereo tomographic method using full wavefields - Hua-Xiang Miao; Fu-Xing Jiang; Xue-Juan Song; Jian-Yong Song; Shu-Hua Yang; Jun-Ru Jiao (Applied Geophysics, 2012)

Availability of dopamine and serotonin transporters in opioid-dependent users—a two-isotope SPECT study - Tzung Lieh Yeh; Kao Chin Chen; Shih-Hsien Lin; I. Hui Lee; Po See Chen; Wei Jen Yao; Sheng-Yu Lee; Yen Kuang Yang; Ru-Band Lu; Mei-Hsiu Liao; Nan-Tsing Chiu (Psychopharmacology, 2012)

Clozapine Protects Dopaminergic Neurons from Inflammation-Induced Damage by Inhibiting Microglial Overactivation - Xiaoming Hu; Hui Zhou; Dan Zhang; Sufen Yang; Li Qian; Hung-Ming Wu; Po-See Chen; Belinda Wilson; Hui-Ming Gao; Ru-band Lu; Jau-Shyong Hong (Journal of Neuroimmune Pharmacology, 2012)

Effects of hyperbaric oxygenation on oxidative stress in acute transient focal cerebral ischemic rats - Ray-Yau Wang; Heng-Chih Chang; Chun-Hao Chen; Yi-Wei Tsai; Yea-Ru Yang (European Journal of Applied Physiology, 2012)

QTL mapping of bio-energy related traits in Sorghum - Yan-an Guan; Hai-lian Wang; Ling Qin; Hua-wen Zhang; Yan-bing Yang; Feng-ju Gao; Ru-yu Li; Hong-gang Wang (Euphytica, 2011)

Functional characterization of a plasma membrane Na+/H+ antiporter from alkali grass (Puccinellia tenuiflora) - Xin Wang; Ru Yang; Baichen Wang; Guifeng Liu; Chuanping Yang; Yuxiang Cheng (Molecular Biology Reports, 2011)

Acute Phase Expression Pattern of ZnTs, LC3, and Beclin-1 in Rat Hippocampus and Its Regulation by 3-Methyladenine Following Recurrent Neonatal Seizures - Hong Ni; Xing Feng; Yong Gong; Lu-yang Tao; Xi-ru Wu (Biological Trace Element Research, 2011)

Effect of glucocorticoids pretreatment on steroidogenic capacity of adrenocortical cells isolated from Meishan piglets - Liu-An Li; Zhan-Wang Wu; Xiao-Jing Yang; Ying-Dong Ni; Nahid Parvizi; Ru-Qian Zhao (In Vitro Cellular & Developmental Biology - Animal, 2011)

Impacts of erucic acid and glucosinolate content on genetic relationships between protein content and fatty acids of rape seed across environments - Chun-Hai Shi; Wei-Dong Xu; Qian-Ru Yu; Hai-Zhen Zhang; Zhong-Wei Yang; Jian-Guo Wu (Euphytica, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Effect of neuronal excitotoxicity on Munc18-1 distribution in nuclei of rat hippocampal neuron and primary cultured neuron - Yan-Ping Zhang; Ping Wan; Hong-Quan Wang; Hong Zhao; Yu-Xia Xu; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2011)

Loudness dependence of auditory evoked potentials (LDAEP) correlates with the availability of dopamine transporters and serotonin transporters in healthy volunteers—a two isotopes SPECT study - I Hui Lee; Yen Kuang Yang; Po See Chen; Hui Chun Huang; Tzung Lieh Yeh; Ru-Band Lu; Nan-Tsing Chiu; Wei Jen Yao; Shih-Hsien Lin (Psychopharmacology, 2011)

Establishment of a transgene expression system for the marine microalga Schizochytrium by 18S rDNA-targeted homologous recombination - Ru-Bin Cheng; Xiang-Zhi Lin; Zhao-Kai Wang; Shan-Jun Yang; Hui Rong; Yong Ma (World Journal of Microbiology and Biotechnology, 2011)

PTEN status is related to cell proliferation and self-renewal independent of CD133 phenotype in the glioma-initiating cells - Ru-Bin Cheng; Rui-Juan Ma; Zhao-Kai Wang; Shan-Jun Yang; Xiang-Zhi Lin; Hui Rong; Yong Ma (Molecular and Cellular Biochemistry, 2011)

Special Distribution of Polybrominated Diphenyl Ethers in Brain Tissues of Free-range Domestic Hens and Ducks from a Village near an Electronic Waste Recycling Site in South China - Zhong-Zhi Yang; Yong-Fang Li; Shan Fu; Xing-Ru Zhao (Bulletin of Environmental Contamination and Toxicology, 2011)

TPH1 is associated with major depressive disorder but not with SSRI/SNRI response in Taiwanese patients - Hsuan-Chi Wang; Tzung Lieh Yeh; Hui Hua Chang; Po Wu Gean; Mei Hung Chi; Yen Kuang Yang; Ru-Band Lu; Po See Chen (Psychopharmacology, 2011)

Exploring the molecular mechanisms of OSU-03012 on vascular smooth muscle cell proliferation - Wei-Wen Kuo; Jing-Ru Weng; Chih-Yang Huang; Chang-Hai Tsai; Wei-Hung Liu; Cheng-Hao Wen; Shih-Chang Tsai; Chieh-Hsi Wu (Molecular and Cellular Biochemistry, 2010)

Characterization of human embryonic stem cell-derived hematopoietic progenitor phenotype - Hai-Yang Zhou; Xiao-Yi Yang; Li-Jian Tao; Yue-Tian Chang; Ru-Ping Dai (In Vitro Cellular & Developmental Biology - Animal, 2010)

Simulation of organic carbon dynamics at regional scale for paddy soils in China - Xue-Zheng Shi; Ru-Wei Yang; David C. Weindorf; Hong-Jie Wang; Dong-Sheng Yu; Yao Huang; Xian-Zhang Pan; Wei-Xia Sun; Li-Ming Zhang (Climatic Change, 2010)

Glutamate enhances the surface distribution and release of Munc18 in cerebral cortical neurons - Ping Wan; Yan-Ping Zhang; Jie Yan; Yu-Xia Xu; Hong-Quan Wang; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2010)

Differentiation of cryopreserved human umbilical cord blood-derived stromal cells into cells with an oligodendrocyte phenotype - Yong-Chun Luo; Hong-Tian Zhang; Hao-Yu Cheng; Zhi-Jun Yang; Yi-Wu Dai; Ru-Xiang Xu (In Vitro Cellular & Developmental Biology - Animal, 2010)

A Series of Novel Rare Earth Molybdotungstosilicate Heteropolyoxometalates Binding to Bovine Serum Albumin: Spectroscopic Approach - Yan-Jun Hu; Yu Ou-Yang; Ai-Min Bai; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Ectopic Expression of the Tomato Mi-1 Gene Confers Resistance to Root Knot Nematodes in Lettuce (Lactuca sativa) - Li-Ying Zhang; Yu-Yang Zhang; Ru-Gang Chen; Jun-Hong Zhang; Tao-Tao Wang; Han-Xia Li; Zhi-Biao Ye (Plant Molecular Biology Reporter, 2010)

Biological Activation of Heteropoly Complex of Molybdotungstosilicate Containing Lanthanum K10H3La(SiMo6W5O39)2⋅26H2O: Spectroscopic Approach and Microcalorimetry - Yan-Jun Hu; Yu Ou-Yang; Ru-Ming Zhao; Yi Liu (Biological Trace Element Research, 2010)

Spectral indices for estimating ecological indicators of karst rocky desertification - Yuemin Yue; Bing Zhang; Kelin Wang; Bo Liu; Ru Li; Quanjun Jiao; Qingqing Yang; Mingyang Zhang (International Journal of Remote Sensing, 2010)

Analysis of the genetic diversity in Saccharum spontaneum L. accessions from Guangxi Province of China with RAPD-PCR - Ge-min Zhang; Yang-Rui Li; Wei-Zhong He; Hong He; Xi-Hui Liu; Huan-Zhong Song; Hai-Bin Liu; Ru-Cai Zhu; Wei-Kuan Fang (Sugar Tech, 2010)

Synergistic up-regulation of muscle LIM protein expression in C2C12 and NIH3T3 cells by myogenin and MEF2C - Zhen-Xing Ji; Chao Du; Guo-Sheng Wu; Shu-Yan Li; Guo-Shun An; Yu-Xi Yang; Ru Jia; Hong-Ti Jia; Ju-Hua Ni (Molecular Genetics and Genomics, 2009)

Analysis of volatile components in a Chinese fish sauce, Fuzhou Yulu, by gas chromatography-mass spectrometry - Yuan-fan Yang; Shen-ru Chen; Hui Ni; Xing-qian Ye (Journal of Zhejiang University-SCIENCE B, 2008)

A new labdane-type diterpene from the bark of Juniperus chinensis Linn. - Chi-I Chang; Wen-Ching Chen; Yi-Yuan Shao; Guey-Ru Yeh; Ning-Sun Yang; Wenchang Chiang; Yueh-Hsiung Kuo (Natural Product Research, 2008)

Sorption of methyl-parathion and carbaryl by an organo-bentonite - Qing-ru Zeng; Bo-han Liao; Bo Yang; Hong-xiao Tang; Nan-dong Xue (Biology and Fertility of Soils, 2006)

Treatment and follow-up of children with transient congenital hypothyroidism - Ru-lai Yang; Zhi-wei Zhu; Xue-lian Zhou; Zheng-yan Zhao (Journal of Zhejiang University-SCIENCE B, 2005)

Occurrence of foliar rot of pak choy and Chinese mustard caused by Rhizoctonia solani AG1-IB in China - Gen-Hua Yang; Hai-Ru Chen; Shigeo Naito; Jian-Yu Wu; Xia-Hong He; Chun-Fang Duan (Journal of General Plant Pathology, 2005)

Histidines 345 and 378 of Bacillus stearotheromophilus leucine aminopeptidase II are essential for the catalytic activity of the enzyme - Guang-Yuh Hwang; Lih-Ying Kuo; Ming-Ru Tsai; Shin-Ling Yang; Long-Liu Lin (Antonie van Leeuwenhoek, 2005)

Sustainable development of marine economy in China - Yao-guang Zhang; Li-jing Dong; Jun Yang; Sheng-yun Wang; Xin-ru Song (Chinese Geographical Science, 2004)

Genetic analysis, molecular tagging and mapping of the thermo-sensitive genic male-sterile gene (wtms1) in wheat - Q. H. Xing; Z. G. Ru; C. J. Zhou; X. Xue; C. Y. Liang; D. E. Yang; D. M. Jin; B. Wang (Theoretical and Applied Genetics, 2003)

Myosin light chain kinase modulates hypotonicity-induced Ca2+ entry and Cl– channel activity in human cervical cancer cells - Meng-Ru Shen; Paola Furla; Cheng-Yang Chou; Clive J. Ellory (Pflügers Archiv - European Journal of Physiology, 2002)

Swelling-activated taurine and K + transport in human cervical cancer cells: association with cell cycle progression - Meng-Ru Shen; Cheng-Yang Chou; J. Clive Ellory (Pflügers Archiv - European Journal of Physiology, 2001)

Volume-sensitive KCl cotransport associated with human cervical carcinogenesis - Meng-Ru Shen; Cheng-Yang Chou; J. Clive Ellory (Pflügers Archiv - European Journal of Physiology, 2000)